Cylindrical lithium-sulfur battery

By using porous carbonaceous materials and protective layer technology in lithium-sulfur batteries, the battery capacity attenuation and mechanical damage caused by polysulfide diffusion is solved, and the cycle stability and safety is achieved, and the energy density of the battery is enhanced. .

CN119325650AActive Publication Date: 2025-01-17LYTEN INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202380045585.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-20
Filing Date
2023-04-21
Publication Date
2025-01-17
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

During the circulation process, existing lithium-sulfur batteries cause battery capacity attenuation and mechanical structure damage due to the diffusion of polysulfides, which affects the cycle stability and safety of the battery.

Method used

Using porous carbonaceous material as the bearing structure of the cathode, the elemental sulfur is defined microscopically and the formation of a porous network is inhibited, and a protective layer is provided on the anode and cathode to prevent the diffusion of polysulfides and the formation of lithium dendrites. .

Benefits of technology

It improves the cycle stability and safety of lithium-sulfur batteries, extends the battery life, and increases the volume and weight energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325650A_ABST
    Figure CN119325650A_ABST
Patent Text Reader

Abstract

A lithium-sulfur battery includes a housing having a length and a width, the housing including at least an anode and a cathode wound into a winding core oriented parallel to the length of the housing; the electrolyte is arranged in the lithium-sulfur battery; a negative terminal extending along the length of the housing; and a positive terminal extending along the length of the housing, the positive terminal and the negative terminal being parallel to each other.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This patent application claims priority to U.S. patent application No. 18 / 137,028, filed on April 20, 2023, entitled “CYLINDRICAL LITHIUM-SULFURBATTERIES,” which is a continuation-in-part application claiming priority to U.S. patent application No. 17 / 726,753, filed on April 22, 2022, entitled “LENGTH-WISE WELDED ELECTRODES INCORPORATED IN CYLINDRICALCELL FORMAT LITHIUM-SULFUR BATTERIES,” which is a continuation-in-part application claiming priority to U.S. patent application No. 17 / 726,753, filed on April 22, 2022, entitled “LITHIUM-SULFURBATTERY WITH A PROTECTIVE LAYER INCLUDING CARBON MATERIALSDECORATED WITH METAL-CONTAINING SUBSENTS”, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 709,156, entitled “METHOD OF MANUFACTURING TAB-LESS CYLINDRICAL CELLS”, filed on March 14, 2022, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 694,407, entitled “METHOD OF MANUFACTURING TAB-LESS CYLINDRICAL CELLS”, filed on March 14, 2022, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 672,960, entitled “PLASTICIZER-INCLUSIVE POLYMERIC-INORGANIC HYBRID LAYER FOR A LITHIUM ANODE IN A LITHIUM-SULFUR BATTERY”, filed on February 16, 2022, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 672,960, entitled “PLASTICIZER-INCLUSIVE POLYMERIC-INORGANIC HYBRID LAYER FOR A LITHIUM ANODE IN A LITHIUM-SULFUR BATTERY”, filed on February 8, 2022 ANODE”, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 666,753, filed on January 26, 2022, entitled “SOLID-STATE ELECTROLYTE FOR LITHIUM-SULFUR BATTERIES”, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 584,666, filed on January 26, 2022, entitled “SOLID-STATE ELECTROLYTE FOR LITHIUM-SULFUR BATTERIES”, which is a continuation-in-part application claiming priority to U.S. Patent Application No. 17 / 578, filed on January 18, 2022, entitled “LITHIUM-SULFUR BATTERY ELECTROLYTE COMPOSITIONS”240, which is a continuation-in-part application claiming priority to U.S. patent application No. 17 / 563,183, filed on December 28, 2021, entitled “LITHIUM-SULFUR BATTERY CATHODE FORMED FROM MULTIPLE CARBONACEOUS REGIONS”, and which is a continuation-in-part application claiming priority to U.S. patent application No. 17 / 383,803, filed on July 23, 2021, entitled “CARBONACEOUS MATERIALS FOR LITHIUM-SULFUR BATTERIES”. This patent application also claims priority to U.S. Patent Application No. 17 / 726,774, filed on April 22, 2022, entitled “WOUND CYLINDRICAL LITHIUM-SULFUR BATTERY INCLUDING ELECTRICALLY-CONDUCTIVE CARBONACEOUS MATERIALS” and U.S. Provisional Patent Application No. 63 / 235,892, filed on August 23, 2021, entitled “LITHIUM SULFUR BATTERY”. The disclosures of all prior applications are assigned to their assignees and are considered part of and are each incorporated by reference in their entirety into this patent application. , Technical Field

[0003] The present disclosure relates generally to a lithium-sulfur battery, and more particularly to a method of manufacturing a lithium-sulfur battery as a jellyroll in which a carbonaceous material replaces one or more anode tabs, thereby providing increased conductivity relative to conventional jellyroll batteries. Background Art

[0004] Recent advances in batteries have allowed consumers to use electronic devices in many new applications. However, battery technology needs further improvement. Summary of the invention

[0005] This Summary is provided to introduce some concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to limit the scope of the claimed subject matter.

[0006] One innovative aspect of the subject matter described in the present disclosure can be implemented as a lithium-sulfur battery. In some implementations, the lithium-sulfur battery includes a housing having a length and a width, the housing including at least an anode and a cathode wound into a roll oriented parallel to the length of the housing; an electrolyte disposed in the lithium-sulfur battery; a negative terminal extending along the length of the housing; and a positive terminal extending along the length of the housing, the positive terminal and the negative terminal being parallel to each other. The electrolyte is configured to inhibit the transport of lithium-containing polysulfide intermediates from the cathode to the anode. In some aspects, the roll is welded to one or both of the negative terminal and the positive terminal along the length of the housing. In other aspects, one or both of the negative terminal and the positive terminal are formed of nickel.

[0007] In various embodiments, the plurality of components further include an anode current collector coupled to the anode, a cathode current collector coupled to the cathode, and a ceramic separator disposed between the anode and the cathode. In some embodiments, the cathode current collector includes a carbonaceous support formed of a material oriented at one or more defined angles relative to the cathode. In some aspects, the ceramic separator includes a plurality of holes configured to allow lithium ions to propagate between the anode and the cathode via the ceramic separator. In some cases, the positive terminal is welded to the cathode current collector longitudinally along the length of the shell, and the negative terminal is welded to the anode current collector longitudinally along the length of the shell. In other cases, the anode is configured to be folded into the anode current collector, and the cathode is configured to be folded into the cathode current collector. In some other cases, the cathode is formed by a plurality of interconnected non-hollow carbonaceous particles. In some aspects, a plurality of interconnected non-hollow carbonaceous particles collectively define a plurality of porous channels, at least some of the plurality of porous channels being configured to retain elemental sulfur.

[0008] In various implementations, the cathode can be coupled to a cathode current collector as a cathode laminate. The cathode can include one or more structured layers of spherical agglomerates of carbonaceous particles disposed on a surface of the cathode current collector. When wound into a roll core in a cylindrical lithium-sulfur battery, the average size of the agglomerates in the one or more structured layers disposed on the side of the cathode current collector facing the battery housing can be greater than the average size of the agglomerates in the one or more structured layers disposed on the side of the cathode current collector facing the mandrel.

[0009] Details of one or more implementations of the subject matter described in the present disclosure are set forth in the accompanying drawings and the following description. Other features, aspects, and advantages become apparent from the description, drawings, and claims. Note that the relative sizes of the following figures may not be drawn to scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Diagrams are shown depicting exemplary batteries according to some implementations.

[0011] Figure 2A diagram is shown depicting another exemplary battery according to some implementations.

[0012] Figure 3 Diagram showing exemplary electrodes of a battery according to some implementations.

[0013] Figure 4 A diagram showing a portion of an exemplary battery including a protective lattice according to some implementations.

[0014] Figure 5 A diagram showing an anode structure including a tin fluoride (SnF2) layer according to some implementations.

[0015] Figure 6 According to some implementations, Figure 5 Schematic diagram of an enlarged portion of the anode structure.

[0016] Figure 7 A diagram showing a polymer network of a battery according to some implementations.

[0017] Fig. 8A A diagram illustrating an exemplary carbonaceous particulate having graded porosity according to some implementations.

[0018] Figure 8B A diagram illustrating an example of a three-segment particle according to some implementations.

[0019] Figure 8C FIG. 1 shows a diagram showing a method according to some implementations. Figure 8B An exemplary step function for a three-segment particle.

[0020] Fig.8D Shown is a graph depicting an exemplary distribution of pore volume versus pore width for an exemplary carbonaceous particulate according to some implementations.

[0021] Fig. 9A and Fig. 9B According to some implementations, Fig. 8A and / or Figure 8B Electron micrographs of exemplary carbonaceous particulates, aggregates and / or agglomerates are depicted.

[0022] Fig. 10A and Fig. 10B Transmission electron microscope (TEM) images of carbonaceous particulates treated with carbon dioxide (CO 2 ) according to some implementations are shown.

[0023] Fig.11 Shown are diagrams depicting the types of carbon pores found in anodes and / or cathodes of the present disclosure according to some implementations.

[0024] Fig.12Shown is a graph depicting the cumulative pore volume and pore width of dispersed micropores and mesopores in an anode or cathode of a battery according to some implementations.

[0025] Fig.13 A graph depicting battery performance as a function of cycle number according to some implementations is shown.

[0026] Fig.14 A bar graph depicting capacity by number of cycles according to some implementations is shown.

[0027] Fig.15 A graph depicting battery performance as a function of cycle number according to some implementations is shown.

[0028] Fig.16 A graph depicting battery discharge capacity as a function of cycle number according to some implementations is shown.

[0029] Fig.17 A graph depicting battery discharge capacity as a function of cycle number according to some implementations is shown.

[0030] Fig.18 Shown is a graph depicting cell specific discharge capacity for various TBT-containing electrolyte mixtures according to some implementations.

[0031] Fig.19 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Figure 1 A graph of the battery's specific discharge capacity according to the number of cycles.

[0032] Fig. 20 Shown is a diagram depicting a method according to other implementations Figure 2 A graph of battery specific discharge capacity and discharge capacity retention capability according to the number of cycles of a battery.

[0033] Fig.21 Shown is a diagram depicting a system according to some other implementations Figure 2 A graph of battery specific discharge capacity and discharge capacity retention capability according to the number of cycles of a battery.

[0034] Fig. 22 A diagram showing an exemplary cathode for a battery according to some implementations.

[0035] Fig.23 FIG. 25 shows a graph depicting specific discharge capacity as a function of cycle number according to some implementations.

[0036] Fig.26A Diagrams are shown depicting exemplary batteries according to some implementations.

[0037] Fig.26B A diagram is shown depicting another exemplary battery according to some implementations.

[0038] Fig. 27 A graph depicting voltage drop as a function of specific capacity according to some implementations is shown.

[0039] Fig.28 A diagram is shown depicting another exemplary battery according to some implementations.

[0040] Fig.29 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Fig.28 Schematic diagram of an exemplary cathode for a battery.

[0041] Fig.30 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Fig.28 Schematic diagram of the protective layer of a battery.

[0042] Fig.31A A photomicrograph of an exemplary baseline protective layer is shown according to some implementations.

[0043] Fig.31B According to some implementations, Fig.28 A micrograph of the protective layer of a battery.

[0044] Fig.32 According to some implementations, Fig.28 A micrograph of a cross-sectional view of the protective layer of a battery.

[0045] Fig.33A According to some implementations, Fig.28 An exemplary crosslinking density of a protective layer of a battery.

[0046] Fig.33B According to some implementations, Fig.28 Another exemplary crosslink density of a protective layer of a battery.

[0047] Fig.34 A triarylsulfonium salt (Ar3S + XOtM - )'s exemplary open-loop (ROP) mechanism.

[0048] Fig.35 is shown suitable for use as a Fig.28 Exemplary onium salts of cationic photoinitiators for the protective layer of the battery.

[0049] Fig.36 is shown suitable for forming a Fig.28 Exemplary monomers of various cationic photopolymerizable compositions for the protective layer of the battery.

[0050] Fig.37is shown suitable for forming a Fig.28 The protective layer of the battery is an ultraviolet (UV) curable monomer.

[0051] Fig.38 Various exemplary non-reactive diluents suitable for use as battery additives are shown according to some implementations.

[0052] Fig.39 Exemplary reactive diluents suitable for use as battery additives are shown according to some implementations.

[0053] Fig.40A A graph showing capacity (% of initial) versus cycle number according to some implementations.

[0054] Fig.40B A graph showing capacity (mAh / g) versus cycle number according to some implementations.

[0055] Fig.41A Another graph showing capacity (% of initial) versus cycle number according to some other implementations.

[0056] Fig.41B Another graph showing capacity (mAh / g) versus cycle number according to some other implementations.

[0057] Fig.42A Diagrams are shown depicting example batteries according to some other implementations.

[0058] Fig.42B According to some implementations, Fig.42A An enlarged portion of the battery.

[0059] Fig.43 An exemplary battery system is shown according to some implementations.

[0060] Fig.44 According to some implementations, Figure 1 An exemplary battery within a battery system.

[0061] Fig.45A Exemplary electrode films suitable for use in the batteries disclosed herein are shown according to some implementations.

[0062] Fig.45B Exemplary electrode films suitable for use in the batteries disclosed herein are shown according to some other implementations.

[0063] Fig.46 Micrographs of exemplary electrode films are shown according to some implementations.

[0064] Fig.47Exemplary agglomerates suitable for use in the batteries disclosed herein are shown according to some implementations.

[0065] Fig.48A Shown is a photomicrograph of exemplary secondary particles suitable for use in the batteries disclosed herein, according to some implementations.

[0066] Fig.48B A photomicrograph of another exemplary secondary particle suitable for use in the batteries disclosed herein is shown, according to some implementations.

[0067] Fig.49A A flow chart depicting exemplary operations for fabricating a rollable cathode according to some implementations is shown.

[0068] Fig.49B A flow chart depicting another exemplary operation for fabricating a rollable cathode according to some implementations is shown.

[0069] Fig.49C A flow chart depicting another exemplary operation for fabricating a rollable cathode according to some implementations is shown.

[0070] Fig.50A A flow chart depicting exemplary operations for fabricating a jellyroll Li-S battery according to some implementations is shown.

[0071] Fig.50B A flow chart depicting another exemplary operation for fabricating a jellyroll Li-S battery according to some implementations is shown.

[0072] Fig.50C A flow chart depicting another exemplary operation for fabricating a jellyroll Li-S battery according to some implementations is shown.

[0073] Fig.51 A diagram showing another lithium-sulfur battery according to other implementations.

[0074] Fig.52 A flow chart depicting example operations for fabricating a tabless cylindrical battery cell according to some implementations is shown.

[0075] Fig.53 A flow chart depicting exemplary operations for winding a core according to some implementations is shown.

[0076] Fig.54 A flow chart depicting exemplary operations for protecting an anode edge from lithium corrosion according to some implementations is shown.

[0077] Fig.55 A flow chart depicting exemplary operations for protecting an anode bottom edge according to some implementations is shown.

[0078] Fig.56 A flow chart depicting exemplary operations for preventing lithium delamination according to some implementations is shown.

[0079] Fig.57 A flow chart depicting example operations for nucleating a plurality of carbon particles according to some implementations is shown.

[0080] Fig.58 A flow chart depicting exemplary operations for functionalizing an adhesive carbon-containing layer according to some implementations is shown.

[0081] Fig.59 A flow chart depicting example operations for cross-linking carbon atoms of a graphenized material, according to some implementations, is shown.

[0082] Fig.60 A flow chart depicting example operations for producing a cohesive carbonaceous layer according to some implementations is shown.

[0083] Fig.61 A flow chart depicting exemplary operations for inserting a roll core into a can is shown according to some implementations.

[0084] Fig.62 A flow chart depicting example operations for welding a viscous carbonaceous layer according to some implementations is shown.

[0085] Fig.63 A flow chart depicting exemplary operations for dipping a core according to some implementations is shown.

[0086] Fig.64 A flow chart depicting example operations for configuring a viscous carbonaceous layer according to some implementations is shown.

[0087] Fig.65 A flow chart illustrating exemplary operations for crimping a core according to some implementations.

[0088] Fig.66 A flow chart depicting example operations for attaching one or more cathode tabs according to some implementations is shown.

[0089] Fig.67 A flow chart depicting example operations for welding or gluing one or more cathode tabs according to some implementations is shown.

[0090] Fig.68 A flow chart depicting exemplary operations for treating a viscous carbonaceous layer according to some implementations is shown.

[0091] Fig.69A flow chart depicting exemplary operations for functionalizing one or more exposed surfaces of one or more carbon allotropes, according to some implementations, is shown.

[0092] Fig.70 A flow chart depicting example operations for increasing one or more of the mechanical or electrical properties of a viscous carbonaceous layer according to some implementations is shown.

[0093] Fig.71 A diagram is shown depicting another exemplary battery according to some other implementations.

[0094] Fig.72 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Fig.71 Schematic diagram of an exemplary cathode for a battery.

[0095] Fig.73 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Fig.71 Schematic diagram of the protective layer of a battery.

[0096] Fig.74 Micrographs of wavy graphene and / or wrinkled graphene based on microwave energy are shown according to some implementations.

[0097] Fig.75 is a micrograph of a carbon-based growth decorated with cobalt suitable for use in the batteries disclosed herein, according to some implementations.

[0098] Fig.76 Exemplary geometries for batteries are shown according to some implementations.

[0099] Fig.77 Another exemplary geometry of a battery according to some implementations is shown.

[0100] Fig.78 Exemplary electrode films suitable for use in the batteries disclosed herein are shown according to some implementations.

[0101] Fig.79 Exemplary electrode films suitable for use in the batteries disclosed herein are shown according to some other implementations.

[0102] Fig.80 Exemplary electrode films suitable for use in the batteries disclosed herein are shown according to some other implementations.

[0103] Like reference numbers and designations throughout the various drawings refer to like elements. DETAILED DESCRIPTION

[0104] The following description relates to some exemplary implementations for the purpose of describing the innovative aspects of the present disclosure. However, it is generally recognized by those skilled in the art that the teachings herein can be applied in many different ways. The described implementations can be implemented in any type of electrochemical cell, battery, or battery pack, and can be used to compensate for various performance-related shortcomings. Therefore, the disclosed implementations are not limited to the examples provided herein, but cover all implementations covered by the attached claims. In addition, well-known elements of the present disclosure will not be described in detail or will be omitted so as not to confuse the relevant details of the present disclosure.

[0105] Batteries typically include multiple electrochemical cells that can be connected to each other to provide power to a wide variety of devices, such as (but not limited to) mobile phones, laptops, electric vehicles (EVs), factories, and buildings. Certain types of batteries, such as lithium-ion or lithium-sulfur batteries, can be limited in performance due to the type of electrolyte used or uncontrolled battery side reactions. Therefore, optimization of the electrolyte can improve the cyclability, specific discharge capacity, discharge capacity retention, safety, and life of the corresponding battery. For example, in an unused or "fresh" battery, the lithium cation (Li + ) are freely transported from the anode to the cathode after activation and later during the initial and subsequent discharge cycles. Then, during the battery charge cycle, the lithium cations (Li + ) migrate from their electrochemically favorable position in the cathode back to the anode where the ions are stored for later use.

[0106] This cyclic discharge-charge process associated with rechargeable batteries can result in the production of undesirable chemicals that can interfere with the lithium cation (Li cation) during the corresponding discharge and charge of the battery. + ) to and from the cathode. Specifically, when lithium cations (Li + ) interacts with elemental sulfur (or, in some configurations, lithium sulfide, Li2S) present in the cathode to produce lithium-containing polysulfide intermediate species (referred to herein as "polysulfides"). These polysulfides are soluble in the electrolyte and therefore diffuse throughout the battery during operating cycles, thereby causing loss of active material from the cathode. The generation of excessive concentration levels of polysulfides can lead to undesirable battery capacity fade and cell failure during operating cycles, thereby potentially reducing the drivable range of electric vehicles (EVs) and increasing the frequency with which such EVs need to be recharged.

[0107] In some cases, polysulfides participate in the formation of an inorganic layer in the solid electrolyte interface (SEI) provided in the battery. In one example, the anode can be protected by a stabilizing inorganic layer formed in the electrolyte and containing 0.020M Li2S5 (0.10M sulfur) and 5.0 wt% LiNO3.x ) can enrich the SEI and produce a 95% stable Coulombic efficiency after 233 cycles of the Li-Cu half-cell, while preventing the formation of lithium dendrites or other uncontrolled lithium growth that can extend from the anode to the cathode and cause cell failure or rupture. However, when polysulfides are produced at certain concentrations (such as greater than 0.50M sulfur), the formation of the SEI can be hindered. As a result, lithium metal from the anode can be undesirably etched, resulting in a rough and imperfect surface exposed to the electrolyte. This undesirable degradation (etching) of the anode due to relatively high concentrations of polysulfides may indicate that polysulfide dissolution and diffusion may limit battery performance.

[0108] In some implementations, the porosity of the carbonaceous cathode can be adjusted to achieve a desired balance between maximizing energy density and inhibiting polysulfide migration to and / or throughout the battery electrolyte. As used herein, a carbonaceous material may refer to a material containing or formed from one or more types or configurations of carbon. For example, cathode porosity may be higher in sulfur and carbon composite cathodes than in conventional lithium-ion battery electrodes. A denser electrode with relatively low porosity can minimize electrolyte uptake, parasitic weight, and cost. Sulfur utilization can be limited by the solubility of polysulfides and the conversion rate of those polysulfides to lithium sulfide (Li2S). The conversion rate of polysulfides to lithium sulfide can be based on the accessible surface area of ​​the cathode.

[0109] Various aspects of the subject matter disclosed herein relate to a lithium-sulfur battery including a liquid electrolyte, the electrolyte may include a ternary solvent package and one or more additives. In some embodiments, the lithium-sulfur battery may include a cathode, an anode positioned relative to the cathode, and an electrolyte. The cathode may include a plurality of regions, each of which may be defined by two or more carbonaceous structures adjacent to and in contact with each other. In some cases, the electrolyte may be dispersed throughout the cathode and in contact with the anode. In some aspects, the electrolyte may include a ternary solvent package and 4,4'-thiobisthiophenol (TBT). In other cases, the electrolyte may include a ternary solvent package and 2-mercaptobenzothiazole (MBT).

[0110] In various implementations, each carbonaceous structure may include a relatively high-density shell region and a relatively low-density core region. In some aspects, the core region may be formed in the inner portion of the shell region. The shell region may have a carbon density between about 1.0 grams per cubic centimeter (g / cc) and 3.5g / cc. The core region may have a carbon density between about 0.0g / cc and 1.0g / cc or lower than some other ranges of the first carbon density. In other implementations, each carbonaceous structure may include a shell region and a core region with the same or similar density, for example, so that the carbonaceous structure does not include a graded porosity. The various regions of the cathode may include microporous channels, mesoporous channels, and macroporous channels interconnected to form a porous network extending from the shell region to the core region. For example, in some aspects, the porous network may include pores each having a major size of about 1.5nm.

[0111] In some implementations, one or more portions of the porous network can temporarily microscopically confine an electroactive material within the cathode, such as, but not limited to, elemental sulfur, which can react with lithium cations (Li + ) composite to increase the battery specific capacity. In some aspects, the ternary solvent package can have adjustable polarity, adjustable solubility, and can transport lithium cations (Li + ). Additionally, the ternary solvent package can at least temporarily suspend polysulfides (PS) during the charge-discharge cycle of the battery.

[0112] In some implementations, the porous network formed by the interconnection of micropores, mesopores, and macropore channels within the cathode may include a plurality of pores having many different pore sizes. In some implementations, the plurality of pores may include micropores having a pore size less than about 2 nm, may include mesopores having a pore size between about 5 and 50 nm, and may include macropores having a pore size greater than about 50 nm. The micropores, mesopores, and macropores may collectively mitigate the undesired migration or diffusion of polysulfides throughout the electrolyte. Since the polysulfide shuttle effect may result in the loss of active material from the cathode, the ability to mitigate or reduce the polysulfide shuttle effect may increase battery performance.

[0113] In one implementation, the micropores may have a pore size of approximately 1.5 nm selected to microscopically confine elemental sulfur (S8, or smaller chains / fragments of sulfur, such as in the form of S2, S4, or S6) preloaded into the cathode. The microscopic confinement of elemental sulfur within the cathode may allow TBT or MBT complexes generated during battery cycling to inhibit the migration of long chain polysulfides within the mesopores of the cathode. The accumulation of these long chain polysulfides within the mesopores of the cathode may cause the cathode to expand in volume to hold the polysulfides and thereby reduce the polysulfide shuttling effect. Thus, the lithium cation (Li +) can continue to be freely transported between the anode and cathode through the electrolyte without being blocked or hindered by polysulfides. + ) move freely throughout the electrolyte, which increases battery performance.

[0114] Additionally or alternatively, one or more protective layers, sheaths, membranes, and / or regions (collectively referred to herein as "protective layers") may be disposed on the anode and / or cathode and / or separator and in contact with the electrolyte. The protective layers may include materials capable of binding to polysulfides to hinder polysulfide migration and prevent lithium dendrite formation. In some aspects, the protective layers may be arranged in different configurations and used with any of the electrolyte chemistries and / or compositions disclosed herein, thereby allowing for full tunability of the battery.

[0115] In one implementation, the carbonaceous material can be grafted with fluorinated polymer chains and deposited on one or more exposed surfaces of the anode. The fluorinated polymer chains can be cross-linked via the Wurtz reaction to form a polymer network in contact with lithium metal from the anode surface. The cross-linked polymer network formation can in turn inhibit the formation of lithium metal dendrites associated with the anode, and can also produce lithium fluoride. The fluorinated polymers within the polymer network can participate in chemical reactions during the battery operation cycle to produce lithium fluoride. The formation of lithium fluoride can involve the lithium cations (Li ions) from the electrolyte. + ) chemically combines with fluoride ions.

[0116] Additionally or alternatively, the polymer network may be combined with any electrolyte chemistry and / or composition disclosed herein and / or a protective sheath disposed on the cathode. In one implementation, the protective sheath may be formed by combining a compound containing a difunctional or higher functionality epoxy with an amine or amide compound. The intermolecular crosslinking of the compound results in the formation of a 3D network that is highly chemically resistant to dissolution in the electrolyte. The composition, for example, may include a trifunctional epoxy compound and a diamine oligomer-based compound that react with each other to produce a protective lattice that can bind to polysulfides produced in the cathode and prevent them from migrating or diffusing into the electrolyte. In addition, the protective lattice may diffuse through one or more cracks that may be formed in the cathode due to battery cycling. When the protective lattice diffuses in such cracks formed in the cathode, it can increase the structural integrity of the cathode and reduce potential rupture of the cathode associated with volume expansion.

[0117] In various implementations, one or more of the disclosed battery components may be combined with a conformal coating disposed on an edge or surface of an anode exposed to an electrolyte. In some implementations, the conformal coating may include a graded interface layer of a replaceable polymer network. In some aspects, the graded interface layer may include a tin fluoride layer and a tin-lithium alloy region formed between the tin fluoride layer and the anode. In response to an operating cycle of the battery, the tin-lithium alloy region may form a lithium fluoride layer uniformly dispersed between the anode and the tin fluoride layer.

[0118] In various implementations, lithium-sulfur batteries using various aspects of the present disclosure may include electroactive materials extracted from external sources, such as underground sources and / or extraterrestrial underground sources. In such implementations, the cathode may be prepared as a sulfur-free cathode including functional pores that can microscopically define the electroactive material within the cathode. In some aspects, the cathode may include aggregates including many carbonaceous particles bonded together, and may include agglomerates including many aggregates bonded together. In one implementation, the carbonaceous material used to form the cathode (and / or anode) may be tuned to define a unique pore size, pore size range, and volume. In some implementations, the carbonaceous particles may include non-three-segment particles with and without three-segment particles. In other implementations, the carbonaceous particles may not include three-segment particles. Each three-segment particle may include micropores, mesopores, and macropores, and the non-three-segment and three-segment particles may each have a major size in the approximate range of 20nm to 300nm. Each carbonaceous particle may include carbonaceous fragments that are nested in each other and separated from directly adjacent carbonaceous fragments by mesopores. In some aspects, each carbonaceous particle can have a deformable perimeter that changes in shape and agglomerates with adjacent material.

[0119] Some of the pores may be distributed in the deformable periphery of multiple carbonaceous fragments and / or carbonaceous particles. In various implementations, mesopores may be dispersed throughout the aggregates, and macropores may be dispersed throughout the multiple agglomerates. In one implementation, each mesopore may have a major dimension between 3.3 nanometers (nm) and 19.3 nm, each aggregate may have a major dimension in an approximate range between 10 nm and 10 micrometers (μm), and each agglomerate may have a major dimension in an approximate range between 0.1 μm and 1,000 μm. As further described below, a specific combination of pore sizes matched with a unique electrolyte formulation and a protective layer can be used to reduce or mitigate the deleterious effects of undesirable polysulfide diffusion, thereby further increasing battery performance.

[0120] In addition, commercial lithium-ion batteries have been made into cylindrical and core-wound prismatic form factors. Given that Li-S batteries have higher theoretical specific capacity and specific energy, it is desirable to manufacture cylindrical or core-wound prismatic Li-S batteries. Conventional cylindrical or core-wound prismatic battery cells require the cathode, anode, and separator to be formed into a core in a radially bent manner. The cathode and anode must have a strong mechanical structure to withstand the bending force during the winding process to avoid any internal short circuit or capacity drop. Li-S batteries, which can power electric vehicles, energy storage systems, or satellites due to their high theoretical energy density, have several undesirable characteristics. For example, the polysulfide shuttle effect may significantly reduce the cycle stability, lead to irreversible sulfur loss, and even cause severe lithium anode corrosion. During the discharge cycle of the Li-S battery, the volume expansion of the cathode active material caused by the cathode reaction can destroy the mechanical structure of the cathode and cause potential harm. To solve those problems, nanoscale porous carbon particles can be used as a cathode supporting structure to carry sulfur in its pores. When cast as a slurry film on a current collector, the porous carbon particles can provide the cathode with a conductive mechanical structure and electrolyte accessibility. At the same time, additives can be added to the porous carbon particles to chemically bind polysulfides and thereby reduce the polysulfide shuttling effect.

[0121] However, a Li-S battery with a cathode designed according to the above measures may have a low volumetric energy density due to high carbon content and small space for accommodating sulfur. Therefore, in order to increase the volumetric energy density, more nano-scale porous carbon particles need to be introduced, and the particles need to be densely stacked within a fixed given volume. Therefore, the densely stacked nano-scale porous particles greatly increase the torsion within the cathode, thereby compromising the ion mobility required for the Li-S battery to operate at a higher C rate. To solve this problem, ion conductive materials have been incorporated into the cathode manufacturing process. However, this practice will damage the weight energy density of the Li-S battery because the ion conductive material adds additional weight to the cathode. In order to increase the weight energy density of the Li-S battery, the battery may have a thicker cathode to increase the sulfur loading. However, thick cathodes generally result in low sulfur utilization, and cracking and delamination occur during the drying step of the manufacturing process. Aggregates or agglomerates made of porous carbon particles have been used to increase sulfur loading, improve sulfur utilization, and reduce cracking. However, during the slurry manufacturing process, the aggregates or agglomerates are easily deformed and therefore cannot withstand the bending forces involved in the core battery packaging process.

[0122] The implementation of the subject matter described in the present disclosure can be used to manufacture cylindrical Li-S batteries or core-wound prismatic Li-S batteries. Since both cylindrical and core-wound prismatic form factors require the electrodes and separators to be formed into a core, the disclosed invention can be described as a core-wound Li-S battery. The core-wound Li-S battery has a higher volumetric and gravimetric energy density, which can be maintained when operating at a higher C rate. In various implementations, the Li-S battery includes a core-wound in a battery shell. In some aspects, the Li-S battery may include one or more tabs to connect the cathode and anode of the Li-S battery to the positive terminal and negative terminal of the shell, respectively. In various implementations, the core-wound includes a cathode, a first barrier layer, an anode, and a second barrier layer rolled into a cylinder. The cross-section of the cylinder has a circular, rectangular, square, triangular, or any other geometric shape. The cathode of the Li-S battery may be a film formed by joining a plurality of micron-sized agglomerates together, and the plurality of agglomerates are produced by a suitable chemical method (e.g., a spray drying or atomization method). A plurality of agglomerates are arranged on one or both surfaces of the current collector, and a plurality of agglomerates have various sizes determined based on the thickness of the cathode. In some cases, the diameter of a relatively large agglomerate may be in a certain ratio with the thickness of the cathode, and the diameter of a relatively small agglomerate may be about one third (1 / 3) of the diameter of a relatively large agglomerate. In some aspects, a plurality of agglomerates have a uniform shape. The shape may be spherical, elliptical, or other well-defined three-dimensional shapes suitable for leaving a void space between adjacent agglomerates. The void space between adjacent agglomerates defines a first plurality of pores. In some aspects, the first plurality of pores may be micrometer-sized pores. In some aspects, the first plurality of pores are uniformly distributed in the cathode film.

[0123] In various implementations, each of the plurality of agglomerates includes a plurality of secondary particles connected to each other by a carbon layer, and each of the plurality of secondary particles includes a plurality of nanoscale primary particles covalently bonded to each other. The void spaces between adjacent secondary particles define a second plurality of pores. In some cases, the average size of the second plurality of pores may be smaller than the average size of the first plurality of pores. When the membrane is dried during the cathode manufacturing process, the first plurality of pores and the second plurality of pores provide channels for the slurry solvent to evaporate from the cast electrode membrane. In various implementations, each of the plurality of primary particles includes nanoscale pores that are configured to define a cathode electroactive material, such as sulfur or lithium sulfur.

[0124] In some aspects, each of the plurality of agglomerates can be encapsulated by a functional layer. The functional layer can be an ion conductive layer configured to enhance the ionic conductivity of the plurality of agglomerates. In some cases, the functional layer can include one or more functional groups, one or more polar and ion conductive additives, or a combination thereof.

[0125] Specific implementations of the subject matter described in the present disclosure may be implemented to achieve one or more of the following potential advantages. Existing cylindrical or prismatic batteries are limited to lithium-ion battery chemistries. Regardless of the research and development or breakthroughs in the constituent materials, such chemistries impose limitations on battery capacity and energy density. As a result, existing lithium-ion batteries may not be used in certain applications that require high energy density, such as energy storage systems for powering satellites or electric vehicles with longer range. In some implementations, the technology disclosed herein can be used to manufacture cylindrical or prismatic Li-S batteries with much higher battery capacity and energy density than commercial lithium-ion batteries. Specifically, the technology disclosed herein can be used to manufacture a cathode that can have a greater thickness for higher sulfur loadings than prior art Li-S batteries while maintaining a sturdy mechanical structure that can withstand the slurry preparation and winding process. In this way, the implementation of the subject matter disclosed herein can eliminate the cracking and delamination currently associated with Li-S batteries, thereby realizing a spiral Li-S battery. Given the advantages of Li-S chemistry and structural design, jellyroll Li-S batteries according to the subject matter disclosed herein can have higher volumetric and gravimetric energy densities, thus outperforming commercial cylindrical and jellyroll prismatic lithium-ion batteries.

[0126] Figure 1 An exemplary battery 100 according to some implementations is shown. The battery 100 may be a lithium-sulfur electrochemical cell, a lithium-ion battery, or a lithium-sulfur battery. The battery 100 may have a body 105, which includes a first substrate 101, a second substrate 102, a cathode 110, an anode 120 positioned opposite the cathode 110, and an electrolyte 130. In some aspects, the first substrate 101 may serve as a current collector for the anode 120, and the second substrate 102 may serve as a current collector for the cathode 110. The cathode 110 may include a first film 111 deposited on the second substrate 102, and may include a second film 112 deposited on the first film 111. In some implementations, the electrolyte 130 may be a liquid electrolyte including one or more additives such as lithium nitrate, tin fluoride, lithium iodide, lithium bis(oxalate)borate (LiBOB), cesium nitrate, cesium fluoride, ionic liquids, lithium fluoride, fluorinated ethers, TBT, MBT, DPT, etc. Suitable solvent packages for these exemplary additives may include various dilution ratios including 1:1:1 of 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), tetraethylene glycol dimethyl ether (TEGDME), and the like.

[0127] Although not shown for simplicity, in one implementation, a lithium layer can be electrodeposited on one or more exposed carbon surfaces of anode 120. In some cases, the lithium layer can include elemental lithium provided by ex situ electrodeposition of lithium on the exposed surfaces of anode 120. In some aspects, the lithium layer can include lithium, calcium, potassium, magnesium, sodium, and / or cesium, wherein each metal can be ex situ deposited on the exposed carbon surfaces of anode 120. During the operating cycles of battery 100, the lithium layer can provide lithium cations (Li + ), which lithium cations can be used for transport to and from cathode 110. Thus, battery 100 may not require an additional source of lithium for operation. Instead of using lithium sulfide, elemental sulfur (S8) can be preloaded in various pores or porous networks formed in cathode 110. During the operating cycle of the battery, elemental sulfur can form lithium-sulfur complexes that can microscopically confine (at least temporarily) a larger amount of lithium than conventional cathode designs. Thus, battery 100 can outperform batteries that rely on such conventional cathode designs.

[0128] In various implementations, during a discharge cycle of the battery 100, the lithium layer may dissociate and / or separate into lithium cations (Li + )125 and electrons 174. Lithium cations (Li + ) 125 can migrate from the anode 120 toward the cathode 110 through the electrolyte 130 to its electrochemically favorable position within the cathode 110, such as Figure 1 As shown in the example. + ) 125 moves through the electrolyte 130, and the electrons 174 are transferred from the lithium cation (Li + ) 125 and become available to carry charge and thus conduct current between anode 120 and cathode 110. Thus, electrons 174 can travel from anode 120 to cathode 110 through an external circuit to power an external load 172. External load 172 can be any suitable circuit, device, or system, such as, but not limited to, a light bulb, consumer electronics, or an electric vehicle (EV).

[0129] In some implementations, the battery 100 may include a solid electrolyte interface layer 140. In some cases, the solid electrolyte interface layer 140 may be artificially formed on the anode 120 during the operating cycle of the battery 100. In such cases, the solid electrolyte interface layer 140 may also be referred to as an artificial solid electrolyte interface or A-SEI. The solid electrolyte interface layer 140 may include tin, manganese, molybdenum, and / or a fluorine compound when formed as an A-SEI. Specifically, molybdenum may provide cations, and the fluorine compound may provide anions. The cations and anions may interact with each other to produce salts such as tin fluoride, manganese fluoride, silicon nitride, lithium nitride, lithium nitrate, lithium phosphate, manganese oxide, lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) etc. In some cases, the A-SEI can respond to lithium cations (Li + ) 125 is formed by exposure to an electrolyte 130, which may include a solvent-based solution including tin and / or fluorine.

[0130] In various implementations, the solid electrolyte interface layer 140 may be artificially provided on the anode 120 before activation of the battery 100. Alternatively, in one implementation, the solid electrolyte interface layer 140 may be naturally formed on the anode 120, for example, during an operating cycle of the battery 100. In some cases, the solid electrolyte interface layer 140 may include an outer shielding material layer that may be applied as a microcoating to the anode 120. In this way, the formation of the solid electrolyte interface layer 140 on the portion of the anode 120 facing the electrolyte 130 may be caused by the electrochemical reduction of the electrolyte 130, which in turn may reduce uncontrolled decomposition of the anode 120.

[0131] In some implementations, the battery 100 may include a barrier layer 142 disposed on the side of the solid electrolyte interface layer 140, such as Figure 1 As shown. The barrier layer 142 may include a mechanical strength enhancer 144 coated and / or deposited on the anode 120. In some aspects, the mechanical strength enhancer 144 may provide structural support for the battery 100, may prevent the formation of lithium dendrites from the anode 120, and / or may prevent lithium dendrites from extending into the entire battery 100. In some implementations, the mechanical strength enhancer 144 may be formed as a protective coating on the anode 120 and may include one or more carbon allotropes, carbon nano-onions (CNO), nanotubes (CNTs), reduced graphene oxide, graphene oxide (GO) and / or carbon nano-diamonds. In some cases, the solid electrolyte interface phase layer 140 may be formed within the mechanical strength enhancer 144.

[0132] In some implementations, the first substrate 101 and / or the second substrate 102 may be a solid copper metal foil and may affect the energy capacity, rate performance, life, and long-term stability of the battery 100. For example, in order to control the energy capacity and other performance attributes of the battery 100, the first substrate 101 and / or the second substrate 102 may be subjected to etching, carbon coating, or other suitable treatments to increase the electrochemical stability and / or conductivity of the battery 100. In other implementations, depending on the end-use application and / or performance requirements of the battery 100, the first substrate 101 and / or the second substrate 102 may include or may be formed of some aluminum, copper, nickel, titanium, stainless steel, and / or carbonaceous materials. For example, the first substrate 101 and / or the second substrate 102 may be individually tuned or customized so that the battery 100 meets one or more performance requirements or metrics.

[0133] In some aspects, the first substrate 101 and / or the second substrate 102 may be at least partially based on or derived from a foam, and may be selected from any one or more of a metal foam, a metal mesh, a metal screen, a porous metal, or a sheet-based three-dimensional (3D) structure. In other aspects, the first substrate 101 and / or the second substrate 102 may be a metal fiber mat, a metal nanowire mat, a conductive polymer nanofiber mat, a conductive polymer foam, a conductive polymer coated fiber foam, a carbon foam, a graphite foam, or a carbon aerogel. In some other aspects, the first substrate 101 and / or the second substrate 102 may be a carbon xerogel, a graphene foam, an oxidized graphene foam, a reduced oxidized graphene foam, a carbon fiber foam, a graphite fiber foam, an exfoliated graphite foam, or any combination thereof.

[0134] Figure 2 Another exemplary battery 200 is shown according to some implementations. The battery 200 can be similar in many respects to Figure 1 The battery 100 of FIG. 1 is a battery 200 of FIG. 1 , so that the description of the same elements is not repeated here. In some implementations, the battery 200 can be a next generation battery, such as a lithium metal battery and / or a solid-state battery with a solid electrolyte. In other implementations, the battery 200 can include an electrolyte 230 and can therefore include any protective layer and / or electrolyte chemistry or composition disclosed herein.

[0135] In some other implementations, the electrolyte 230 may be solid or substantially solid. For example, in some cases, the electrolyte 230 may start out in a gel phase and then solidify after activation of the battery 200. The battery 200 may reduce the specific capacity or energy loss associated with the polysulfide shuttle effect by replacing a conventional carbon support anode with a single solid metallic lithium layer deposited in an initially empty cavity. For example, while Figure 1 The anode 120 of the battery 100 may include a carbon support, but Figure 2The anode 220 of the battery 200 may be a lithium metal anode that does not contain any carbon material. In one implementation, the lithium metal anode may be formed as a single solid lithium metal layer and is referred to as a "lithium metal anode."

[0136] The energy density increase associated with various cathode materials may be based on whether lithium metal is preloaded in the cathode 210 and / or whether the lithium metal is dominant in the electrolyte 230. The cathode 210 and / or the electrolyte 230 may provide lithium that can be used to lithiate the anode 220. For example, a battery with a high-capacity cathode may require a thicker or more energy-dense anode to supply the increased amount of lithium required for the use of a high-capacity cathode. In some implementations, the anode 220 may include a scaffold carbonaceous structure that can be gradually filled with lithium deposited therein. These carbonaceous structures may be able to hold a larger amount of lithium in the anode 220 compared to conventional graphite anodes, which may be limited to only carrying lithium embedded between alternating graphene layers or can be electroplated with lithium. For example, a conventional graphite anode may use six carbon atoms to hold a single lithium atom. In contrast, by using a pure lithium metal anode, such as the anode 220, the battery disclosed herein may reduce or even eliminate the use of carbon in the anode 220, which may allow the anode 220 to store a larger amount of lithium in a relatively small volume compared to conventional graphite anodes. In this way, the energy density of battery 200 may be greater than conventional batteries of similar size.

[0137] Lithium metal anodes such as anode 220 can be prepared to function with solid electrolytes designed to inhibit the formation and growth of lithium dendrites from the anode. In some aspects, separator 250 can further limit dendrite formation and growth. Figure 1 The separator 250 may have similar ionic conductivity while still reducing the formation of lithium dendrites in the electrolyte 130. In some aspects, the separator 250 may be formed of a material containing ceramics and may therefore not be able to chemically react with metallic lithium. Therefore, the separator 250 may be used to control the transport of lithium ions through the pores distributed in the separator 250 while preventing short circuits by hindering the flow of electrons through or through the electrolyte 230.

[0138] In one implementation, void space (not shown for simplicity) may be formed in the battery 200 at or near the anode 220. In this implementation, operating cycles of the battery 200 may cause lithium to be deposited into the void space. Thus, the void space may become or transform into a lithium-containing region (such as a solid lithium metal layer) and serve as the anode 220. In some aspects, the void space may be generated in response to a chemical reaction between a metal-containing non-electroactive component and a graphene-containing component of the battery 200. Specifically, during an operating cycle, the graphene-containing component may chemically react with the lithium deposited into the void space and produce lithiated graphite (LiC6) or patterned lithium metal. The lithiated graphite produced by the chemical reaction may produce or result in lithium cations (Li + ) and / or the generation and / or release of ions or electrons, which can be used to carry charge or “current” between anode 220 and cathode 210 during a discharge cycle of battery 200.

[0139] Moreover, in implementations where anode 220 is a solid lithium metal layer, battery 200 may be able to retain more electroactive material and / or lithium per unit volume (e.g., compared to batteries with scaffolding carbon and / or embedded lithiated graphite anodes). In some aspects, anode 220, when prepared as a solid lithium metal layer, may result in battery 200 having a higher energy density and / or specific capacity than batteries with scaffolding carbon and / or embedded lithiated graphite anodes, thereby resulting in longer discharge cycle times and additional power output per unit time. In situations where the use of a solid electrolyte is not desirable or optimal, Figure 2 The electrolyte 230 of the battery 200 can be prepared using any liquid electrolyte chemistry and / or composition disclosed herein. Additionally or alternatively, the electrolyte 230 may include lithium and / or lithium cations (Li + ), which can be used for cyclic transport from the anode 220 to the cathode 210 and vice versa during the discharge and charge cycles, respectively.

[0140] In order to reduce the migration of polysulfides 282 generated from elemental sulfur 281 pre-loaded in the cathode 210 into the electrolyte 230, the battery 200 may include one or more unique polysulfide retention features. For example, given that polysulfides can be dissolved in the electrolyte 230, it is expected that some polysulfides can drift or migrate from the cathode 210 to the anode 220 due to differences in electrochemical potentials, chemical gradients, and / or other phenomena. The migration of polysulfides 282 (especially long-chain polysulfides) may hinder the lithium cation (Li + ) from the anode 220 to the cathode 210, thereby potentially reducing the number of electrons available to generate current that can power a load 272 such as an electric vehicle (EV). +) 225 can be transported from one or more starting locations 226 at or near the anode 220 along the transport channel to one or more final locations 227 at or near the cathode 210, such as Figure 2 is depicted in the example.

[0141] In some implementations, the polymer network 285 may be disposed on the anode 220 to reduce uncontrolled migration of the polysulfide 282 from the anode 220 to the cathode 210. The polymer network 285 may include one or more carbonaceous material layers grafted with fluorinated polymer chains that are cross-linked to each other via a Woods reaction after exposure to the lithium anode surface. The carbonaceous materials of the polymer network 285, which may include (but are not limited to) graphene, few-layer graphene FLG, and multi-layer graphene MLG, may be chemically grafted with fluorinated polymer chains containing carbon-fluorine (CF) bonds. These CF bonds may chemically react with lithium metal from the surface of the anode 220 to produce highly ionic carbon-lithium bonds (C-Li). These formed C-Li bonds may in turn react with the CF bonds of the polymer chains to form new carbon-carbon bonds, which may also cross-link the polymer chains into (and thereby form) a polymer network and produce lithium fluoride (LiF).

[0142] The resulting lithium fluoride can be evenly distributed along the entire periphery of the polymer network 285, so that during battery cycling, lithium cations (Li + ) is uniformly consumed, thereby producing an interfacial layer 283 that may form or otherwise include lithium fluoride. The interfacial layer 283 may extend along the surface or portion of the anode 220 that faces the cathode 210, such as Figure 2 Therefore, lithium cation (Li + ) 225 are less likely to combine and / or react with each other and are more likely to combine and / or react with fluorine atoms that may be provided by fluorinated polymer chains in the polymer network 285. The resulting reduction in lithium-lithium chemical reactions reduces lithium-lithium bonding that causes undesirable lithium-metal dendrite formation. Additionally, in some implementations, the polymer network 285 can replace the interfacial phase layer 240 that is naturally or artificially formed between the anode 220 and the electrolyte 230.

[0143] In one implementation, the interface layer 283 of the polymer network 285 is in contact with the anode 220, and the protective layer 284 is disposed on top of the interface layer 283 (such as between the interface layer 283 and the interface phase layer 240). In some aspects, the interface layer 283 and the protective layer 284 can collectively define a gradient having different densities of cross-linked fluoropolymer chains, for example, as described in reference Figure 7 described.

[0144] In some other implementations, the battery 200 may include a protective lattice 280 disposed on the cathode 210. The protective lattice 280 may include a trifunctional epoxy compound and a diamine oligomer-based compound, which may chemically react with each other to produce nitrogen and oxygen atoms. The nitrogen and oxygen atoms that may be provided by the protective lattice 280 may be combined with the polysulfide 282, thereby confining the polysulfide 282 within the cathode 210 and / or the protective lattice 280. Either the cathode 210 and / or the protective lattice 280 may include carbon-carbon bonds and / or regions that are capable of flexing and / or expanding in volume during an operating cycle of the battery 200, thereby confining the polysulfide 282 generated during an operating cycle to the cathode 210.

[0145] Figure 1 The electrolyte 130 and Figure 2 The electrolyte 230 may be prepared according to one or more formulations disclosed herein. For example, a ternary solvent package for electrolyte 130 and / or electrolyte 230 may include DME, DOL, and TEGDME. In one implementation, the solvent mixture may be prepared by mixing 5800 μL DME, 2900 μL DOL, and 1300 μL TEGDME and stirring at room temperature (77°F or 25°C). Next, 0.01 mol (2,850.75 mg) of LiTFSI may be weighed. Thereafter, 0.01 mol of LiTFSI may be dissolved in the solvent mixture by stirring at room temperature to prepare approximately 10 mL of 1M LiTFSI in DME:DOL:TEGDME (volume:volume:volume 1:4:1). Finally, approximately 223 mg of LiNO 3 can be added to 10 mL of the solution to produce 10 mL of 1 M LiTFSI in DME:DOL:TEGDME (v:v:v=58:29:13) with approximately 2 wt % LiNO 3 .

[0146] Additionally or alternatively, the ternary solvent package for electrolyte 130 and / or electrolyte 230 may include DME, DOL, TEGDME and TBT or MBT. The solvent mixture may be prepared by mixing 2,000 μL DME, 8,000 μL DOL and 2,000 μL TEGDME and stirring at room temperature (68°F or 25°C). Next, 0.01 mol (2,850.75 mg) of LiTFSI may be weighed and dissolved in approximately 3 mL of the solvent mixture by stirring at room temperature. Next, the dissolved LiTFSI and additional solvent mixture (approximately 8,056 mg) may be mixed in a 10 mL volumetric flask to produce approximately 1 M LiTFSI in DME:DOL:TEGDME (volume:volume:volume 1:4:1). Finally, approximately 0.05 mmol (approximately 12.5 mg) of TBT or MBT may be added to a 10 mL solution to produce a 10 mL 5 M TBT or MBT solution.

[0147] Figure 3 2 shows an exemplary electrode 300 according to some implementations. In various implementations, the electrode 300 may be Figure 1 An example of a cathode 110 and / or an anode 120 of a battery 100. In some other implementations, the electrode 300 may be Figure 2 When the electrode 300 is implemented as a cathode (e.g. Figure 1 When the cathode 110 of the battery 100 is formed, the electrode 300 can temporarily microscopically confine the electroactive material such as elemental sulfur, which can reduce the amount of sulfur available to react with lithium to produce polysulfides. In some aspects, the electrode 300 can provide an excess supply of lithium and / or lithium cations (Li + ), thereby compensating for the first cycle operating losses associated with lithium-based batteries.

[0148] In some implementations, the electrode 300 can be porous and can receive a liquid electrolyte, such as Figure 1 Electrolyte 130. Electroactive materials suspended in electrolyte 130, such as lithium cations (Li + ) 125, can chemically react with elemental sulfur preloaded into the pores of electrode 300 to produce polysulfides, which in turn can be trapped in electrode 300 during battery cycling. In some aspects, electrode 300 can expand in volume along one or more flexure points to hold additional amounts of polysulfides produced during battery cycling. By confining polysulfides within electrode 300, aspects of the subject matter disclosed herein can allow lithium cations (Li +) 125 flows freely from the anode 120 to the cathode 110 through the electrolyte 130 during a discharge cycle of the battery 100 (e.g., without being hindered by polysulfides). For example, when the lithium cation (Li + ) 125 arrives at cathode 110 and reacts with elemental sulfur contained in or associated with cathode 110, the sulfur is reduced to lithium polysulfide (Li2S x ): Li2S8→Li2S6→Li2S4→Li2S2→Li2S, where 2≤x≤8). Higher-order polysulfides can dissolve in various types of solvents and / or electrolytes, thereby interfering with the lithium ion transport necessary for healthy battery operation. Such higher-order polysulfides are retained by the electrode 300, thereby allowing lithium cations (Li + )125 flows more freely through the electrolyte 130, which in turn increases the number of electrons available to carry charge from the anode 120 to the cathode 110.

[0149] The electrode 300 may include a body 301 defined by a width 305, and may include a first film 310 and a second film 320. The first film 310 may include a plurality of first aggregates 312 bonded together to form a first porous structure 316 of the electrode 300. In some cases, the first porous structure 316 may have a conductivity between about 0 and 500 S / m. In other cases, the first conductivity may be between about 500 and 1,000 S / m. In some other examples, the first conductivity may be greater than 1,000 S / m. In some aspects, the first aggregate 312 may include carbon nanotubes (CNTs), carbon nano onions (CNOs), flake graphene, wrinkled graphene, graphene grown on carbonaceous materials, and / or graphene grown on graphene.

[0150] In some implementations, the first aggregate 312 may be decorated with a plurality of first nanoparticles 314. In some cases, the first nanoparticles 314 may include tin, lithium alloys, iron, silver, cobalt, semiconductor materials, and / or metals such as silicon. In some aspects, CNTs may be used as a support material for the first nanoparticles 314 due to their ability to provide high exposed surface area per unit volume and stability at relatively high temperatures (such as above 77°F or 25°C). For example, the first nanoparticles 314 may be fixed (such as by decoration, deposition, surface modification, or the like) on the exposed surfaces of CNTs and / or other carbonaceous materials. The first nanoparticles 314 may react with chemically available carbon on the exposed surfaces of CNTs and / or other carbonaceous materials.

[0151] The second film 320 may include a plurality of second aggregates 322 joined together to form a second porous structure 326. In some cases, the conductivity of the first porous structure 316 and / or the second porous structure 326 may be between about 0 S / m and 250 S / m. In the case where the first porous structure 316 includes a higher concentration of aggregates than the second porous structure 326, the first porous structure 316 may have a higher conductivity than the second porous structure 326. In one implementation, the first conductivity may be between about 250 S / m and 500 S / m, and the second conductivity may be between about 100 S / m and 250 S / m. In another implementation, the second conductivity may be between about 250 S / m and 500 S / m. In another implementation, the second conductivity may be greater than 500 S / m. In some aspects, the second aggregate 322 can include CNTs, CNOs, flake graphene, wrinkled graphene, graphene grown on a carbonaceous material, and / or graphene grown on graphene.

[0152] The second aggregate 322 can be decorated with a plurality of second nanoparticles 324. In some implementations, the second nanoparticles 324 may include iron, silver, cobalt, semiconductor materials and / or metals such as silicon. In some cases, CNTs may also be used as a support material for the second nanoparticles 324. For example, the second nanoparticles 324 may be fixed (such as by decoration, deposition, surface modification or the like) on the exposed surface of CNTs and / or other carbonaceous materials. The second nanoparticles 324 may react with the chemically available carbon on the exposed surface of CNTs and / or other carbonaceous materials.

[0153] In some aspects, the first film 310 and / or the second film 320 (and any additional films disposed on their respective immediately preceding films) can be formed as layers or regions of materials and / or aggregates. The layers or regions can have a thickness ranging from a fraction of a nanometer to a few microns, such as between about 0 and 5 microns, between about 5 and 10 microns, between about 10 and 15 microns, or greater than 15 microns. Any material and / or aggregate (such as CNO) disclosed herein can be incorporated into the first film 310 and / or the second film 320 to produce the described thickness levels.

[0154] In some implementations, the first film 310 may be deposited by chemical deposition, physical deposition, or Figure 1The first thin film 310 may be deposited on the second substrate 102 by epitaxy or other suitable thin film deposition methods involving epitaxial growth of materials. The second thin film 320 and / or subsequent thin films may be deposited on their respective immediately preceding thin films in a manner similar to that described with reference to the first thin film 310.

[0155] In various implementations, each of the first aggregate 312 and / or the second aggregate 322 may be a relatively large particle formed by bonding or fusing together many relatively small particles. Thus, the surface area of ​​the relatively large particle may be significantly less than the combined surface area of ​​the many relatively small particles. The forces holding the aggregates together may be, for example, covalent, ionic, or other types of chemical bonds resulting from sintering or complex physical entanglement of previous primary particles.

[0156] As discussed above, the first aggregates 312 may be joined together to form the first porous structure 316, and the second aggregates 322 may be joined together to form the second porous structure 326. The conductivity of the first porous structure 316 may be based on the concentration level of the first aggregates 312 within the first porous structure 316, and the conductivity of the second porous structure 326 may be based on the concentration level of the second aggregates 322 within the second porous structure 326. In some aspects, the concentration level of the first aggregates 312 may cause the first porous structure 316 to have a relatively high conductivity, and the concentration level of the second aggregates 322 may cause the second porous structure 326 to have a relatively low conductivity (such that the first porous structure 316 has a greater conductivity than the second porous structure 326). The resulting difference in the conductivity of the first porous structure 316 and the second porous structure 326 may produce a conductivity gradient across the electrode 300. In some implementations, the conductivity gradient may be used to control or adjust the conductivity of the entire electrode 300 and / or Figure 1 One or more operations of the battery 100.

[0157] As used herein, relatively small source particles may be referred to as "primary particles" and relatively large aggregates formed by primary particles may be referred to as "secondary particles". Figure 1, Figures 8 to 10 and shown elsewhere throughout the present disclosure, primary particles may be or include multiple graphene flakes, layers, regions and / or nanosheets that are fused and / or joined together. Therefore, in some cases, carbon nano onions (CNO), carbon nanotubes (CNT) and / or other adjustable carbon materials can be used to form primary particles. In some aspects, some aggregates may have a major dimension (such as length, width and / or diameter) between about 500nm and 25μm. In addition, some aggregates may include a smaller collection of primary particles called "natural particles" of graphene flakes, layers, regions and / or nanosheets joined together at orthogonal angles. In some cases, these natural particles may each have a corresponding size between about 50nm and 250nm.

[0158] The surface area and / or porosity of such native particles may be imparted by a secondary process, such as carbon activation by thermal, plasma, or combined thermal-plasma processes using one or more of steam, hydrogen gas, carbon dioxide, oxygen, ozone, KOH, ZnCl2, H3PO4, or other similar chemicals, alone or in combination. In some implementations, the first porous structure 316 and / or the second porous structure 326 may be produced from a carbonaceous gaseous substance that may be controlled by a gas-solid reaction under non-equilibrium conditions. Producing the first porous structure 316 and / or the second porous structure 326 in this manner may involve the recombination of carbon-containing radicals formed by controlled cooling of a carbon-containing plasma substance (which may be produced by excitation or compaction of a carbon-containing feed gaseous and / or plasma substance in a suitable chemical reactor).

[0159] In some implementations, the first aggregate 312 and / or the second aggregate 322 may have a percentage of carbon to elements other than hydrogen within each respective aggregate greater than 99%. In some cases, the median particle size of each aggregate may be between approximately 0.1 microns and 50 microns. The first aggregate 312 and / or the second aggregate 322 may also include a metal organic framework (MOF).

[0160] In some implementations, the first porous structure 316 and the second porous structure 326 can collectively define a main structure 328, for example, as Figure 3 In some cases, the primary structure 328 may be based on a carbon scaffold and / or may include decorative carbon, for example, as shown in FIG8 . The primary structure 328 may provide structural definition for the electrode 300 . In some cases, the primary structure 328 may be fabricated as a positive electrode and used for Figure 1 In other implementations, the main structure 328 can be manufactured as a negative electrode and used Figure 1anode 120. In some other implementations, the main structure 328 may include pores of different sizes, such as micropores, mesopores, and / or macropores as defined by IUPAC. In some cases, at least some of the micropores may have a width of about 1.5 nm, which may be large enough to allow sulfur to be preloaded into the electrode 300 and still small enough to confine the polysulfide within the electrode 300.

[0161] The main structure 328 is provided as Figure 3 When the electrode 300 is shown, it can include microporous, mesoporous and / or macroporous channels created through the exposed surface and / or contour of the first porous structure 316 and / or the second porous structure 326. These channels can allow the main structure 328 to receive electrolytes, for example, by introducing lithium cations (Li + ) is transported to the cathode 110 of the battery 100. Specifically, the electrolyte 130 can infiltrate the various porous channels of the main structure 328 and be evenly dispersed throughout the electrode 300 and / or other portions of the battery 100. The infiltration of the electrolyte 130 into such areas of the main structure 328 can allow lithium cations (Li ions) to migrate from the anode 120 to the cathode 110. + ) 125 reacts with elemental sulfur associated with cathode 110 to form a lithium-sulfur complex. Thus, elemental sulfur can hold an additional amount of lithium cations (Li + ), which can also be achieved using non-sulfur chemistries such as lithium cobalt oxide (LiCoO) or other lithium-ion cells.

[0162] In some aspects, each of the first porous structure 316 and / or the second porous structure 326 can have a porosity based on one or more of a thermal, plasma, or combined thermal-plasma process using one or more of steam, hydrogen gas, carbon dioxide, oxygen, ozone, KOH, ZnCl2, H3PO4, or other similar chemical agents, alone or in combination. For example, in one implementation, the macroporous channels can have a major dimension greater than 50 nm, the mesoporous channels can have a major dimension between about 20 nm and 50 nm, and the microporous channels can have a major dimension less than 4 nm. Thus, the macroporous channels and the mesoporous channels can provide a porous structure for transporting lithium cations (Li + )125, and the microporous channels can define the active materials within the electrode 300.

[0163] In some implementations, the electrode 300 may include one or more additional films (not shown for simplicity). Each of the one or more additional films may include individual aggregates interconnected to each other across different films, where at least some of the films have different concentration levels of aggregates. Thus, the concentration level of any film may be varied (such as by a gradient) to achieve a particular resistance (or conductance) value. For example, in some implementations, the concentration level of aggregates may step down between the first film 310 and the last film (such as at Figure 1 In some aspects, a relatively high concentration of aggregates corresponds to a relatively low resistance, and a relatively low concentration of aggregates corresponds to a relatively high resistance.

[0164] The main structure 328 can be prepared to have multiple active sites on the exposed surface of the first aggregate 312 and / or the second aggregate 322. These active sites and the exposed surface of the first aggregate 312 and / or the second aggregate 322 can facilitate ex situ electrodeposition before the electrode 300 is incorporated into the battery 100. Electroplating is a process that can produce a lithium layer 330 (including lithium on the exposed surface of the main structure 328) by chemical reduction of metal cations by applying and / or regulating an electric current. Figure 1 In an implementation of anode 120 of battery 100 in FIG. 1 , primary structure 328 may be plated such that lithium layer 330 has a thickness between approximately 1 and 5 micrometers (μm), between 5 μm and 20 μm, or greater than 20 μm. In some cases, ex situ electrodeposition may be performed at a location independent of battery 100 prior to assembly of battery 100.

[0165] In various implementations, the excess lithium provided by the lithium layer 330 can increase the lithium cations (Li + )125, thereby increasing the storage capacity, life and performance of the battery 100 (compared to traditional lithium-ion and / or lithium-sulfur batteries).

[0166] In some aspects, the lithium layer 330 can produce lithium intercalated graphite (LiC6) and / or lithiated graphite based on chemical reactions with the first aggregate 312 and / or the second aggregate 322. Due to differences in electrochemical gradients during the operating cycles of the battery 100, the lithium intercalated between the alternating graphene layers can migrate or transport within the electrode 300, which in turn can increase the energy storage and power delivery of the battery 100.

[0167] Figure 4A diagram showing a portion of an exemplary battery 400 including a protective lattice 402 according to some implementations. In some implementations, the protective lattice 402 can be disposed on the anode 220 of the battery 200. In other implementations, the protective lattice 402 can be disposed on the cathode 210 of the battery 200 (or other suitable battery). In some aspects, the protective lattice 402 can be Figure 2 The protective lattice 402 may be used with many components (e.g., anodes, cathodes, associated current collectors, carbonaceous materials, electrolytes, and separators) to form a protective lattice 280. Figure 1 The battery 100 and / or Figure 2 The battery 200 functions in a similar manner.

[0168] The protective lattice 402 may include a trifunctional epoxy compound and a diamine oligomer-based compound, which may chemically react with each other to produce a 3D lattice structure (e.g., Figure 6 8). In some aspects, the protective lattice 402 can prevent polysulfide migration within the cell 400 by providing nitrogen and oxygen atoms that can chemically bond with lithium present in the polysulfide, thereby hindering the migration of the polysulfide through the electrolyte 130. + )125 can be more freely Figure 1 anode 120 and cathode 110 transport, thereby increasing battery performance metrics.

[0169] Cycling of the cathode 110 may result in the formation of cracks 404 that extend at least partially into the cathode 110. In one implementation, the protective lattice 402 may be dispersed throughout the cracks 404, thereby reducing the susceptibility of the cathode 110 to cracking during volume expansion of the cathode 110 caused by polysulfide remaining within the cathode 110 during cycling. In one implementation, based on the chemical reaction between a difunctional or higher functionality epoxy compound and an amine or amide compound, Figure 4 The protective lattice 402 may have a cross-linked 3D structure. For example, the difunctional or higher-functional epoxy compound may be trimethylolpropane triglycidyl ether (TMPTE), tris(4-hydroxyphenyl)methane triglycidyl ether, or tris(2,3-epoxypropyl)isocyanurate, and the difunctional or higher-functional amine compound may be one of dihydrazide sulfoxide (DHSO) or polyetheramine, such as one characterized by repeating oxypropylene units in the main chain. D-230.

[0170] In various implementations, the chemical compounds may be combined and reacted with one another in a variety of quantities, amounts, ratios, and / or compositions to achieve different performance capabilities with respect to bonding with polysulfides generated during operation of the cell 400. For example, in one implementation, 113 mg TMPTE and 134 mg D-230 polyetheramine can be mixed together and diluted with 1 mL to 10 mL of tetrahydrofuran (THF) or any other solvent. Exemplary ratios of D-230 polyetheramine, additional amounts of TMPTE and / or JEFFAMINE can be mixed together and diluted in THF or any other solvent. For the implementation described, proof of concept (POC) data show that Figure 4 The protective lattice 402 has Figure 1 The cathode 110 or Figure 2 The protective lattice 402 may have a defined weight of about 2.6 weight percent of the cathode 210. In other implementations, the protective lattice 402 may have a weight of about 2 weight percent to 21 weight percent of the cathode 110 and / or the cathode 210, wherein an increase in the impedance of the cathode 110 and / or the cathode 210 may be expected at a weight level of about 10 weight percent or more of the protective lattice 402.

[0171] In various implementations, the protective lattice 402 can be manufactured based on the moles and / or molar ratios of -NH2 groups and epoxy groups, and can further accommodate various cross-linking forms between difunctional or higher functionality epoxy compounds and amine or amide compounds. In some aspects, such cross-linking forms can include a fully cross-linked stage, for example, where one -NH2 group is chemically bonded to two epoxy groups and can be further extended to a configuration including one NH2 group chemically bonded to only one epoxy group. Still further, in one or more implementations, a mixture including an excessive number (higher than the ratios presented herein) of -NH2 groups can be prepared to provide additional polysulfide binding capacity to the protective lattice 402.

[0172] In some other implementations, the 201g TMPTE can be combined with a 109g to 283g D-230 polyetheramine is mixed to prepare the protective lattice 402. The resulting mixture can then be diluted with 1L to 20L of a selected solvent (such as THF). The resulting diluted solution can be deposited and / or otherwise disposed on the cathode 110 to achieve a crosslinker content between 1 wt% and 10 wt%. With 201g TMPTE / 109g to 283g Exemplary ratios of D-230 polyetheramine, additional TMPTE and / or JEFFAMINE may be mixed together and diluted in THF or another suitable solvent.

[0173] In yet other implementations, the protective lattice 402 can be prepared by mixing 201 g of TMPTE with between 74 g and 278 g of DHSO. The resulting mixture can then be diluted with 1 L to 20 L of a selected solvent, such as THF. The resulting diluted solution can be deposited and / or otherwise disposed on the cathode 110 to achieve a crosslinker content between 1 wt % and 10 wt %. With 201 g TMPTE / 201 g to 278 g DHSO, the crosslinker content can be between 1 wt % and 10 wt %. Exemplary ratios of D-230 polyetheramine, additional TMPTE and / or JEFFAMINE may be mixed together and diluted in THF or another suitable solvent.

[0174] In one implementation, the difunctional or higher functional epoxy compound can be chemically reacted with the difunctional or higher functional amine compound to produce a 3D cross-linked protective lattice 402, which can include the functional epoxy compound and the amine-containing molecules. In some aspects, the protective lattice 402 is deposited on Figure 1 The cathode 110 or Figure 2 When on the cathode 210, it can have a thickness between about 1 nm and 5 μm.

[0175] In some implementations, the protective lattice 402 can increase the structural integrity of the cathode 110 or cathode 210, can reduce surface roughness, and can retain polysulfides in the cathode. For example, in one implementation, the protective lattice 402 can act as a sheath on the exposed surface of the cathode and bind to the polysulfides to prevent them from migrating and diffusing into the electrolyte 130. In this way, aspects of the subject matter disclosed herein can prevent (or at least reduce) battery capacity decay by inhibiting the polysulfide shuttle effect. In some aspects, the protective lattice 402 can also fill in the Figure 4 In various implementations, the protective lattice 402 can be prepared by a drop casting process in the presence of a solvent, wherein the resulting solution can penetrate into the cracks 404 of the cathode 110 and bind to the polysulfides in the cathode 110 to prevent them from migrating and / or diffusing throughout the electrolyte 130.

[0176] In various implementations, the protective lattice 402 can provide nitrogen atoms and / or oxygen atoms that can chemically bond with lithium in polysulfides generated during operating cell cycles. In one example, the polysulfides can bond with available nitrogen atoms provided by, for example, DHSO. In another example, the polysulfides can bond with available oxygen atoms provided by, for example, DHSO. In yet another example, the polysulfides can bond with other available oxygen atoms.

[0177] In some other implementations, the above-described formulation may be modified by replacing TMPTE with tris(4-hydroxyphenyl)methane triglycidyl ether 910 and / or tris(2,3-epoxypropyl)isocyanurate. In various implementations, the diamine oligomer-based compound may be (or may include) D-230, or other polyetheramines containing a polyether backbone typically based on propylene oxide (PO), ethylene oxide (EO), or a mixed PO / EO structure, such as D-400, T-403. The protective lattice 402 may also include various concentration levels of inert molecules, for example, polyethylene glycol chains of various lengths, which may allow fine tuning of the mechanical properties of the protective lattice and the chemical bonding of various atoms to the lithium present in the polysulfide.

[0178] Figure 5 A diagram of an anode structure 500 including a tin fluoride (SnF2) layer according to some implementations is shown. Specifically, the figure depicts a cross-sectional schematic diagram of the anode structure 500, wherein all components associated with a first region A have the same counterparts in a second region B, wherein the first region A and the second region B have opposite orientations around the current collector 520. Therefore, the description below with reference to components of the first region A is also applicable to components of the second region B. In some aspects, the anode 502 can be Figure 1 The anode 120 and / or Figure 2 An example of an anode 220 .

[0179] As discussed, lithium-sulfur batteries, such as Figure 1 The battery 100 and Figure 2 The battery 200 is operated as a conversion chemistry type electrochemical cell, wherein sulfur preloaded into the cathode can be rapidly dissolved into the electrolyte before and during operation. Lithium, which may be provided by the lithiated anode and / or may be predominant in the electrolyte, dissociates into lithium cations (Li + ), which is suitable for transport from the anode to the cathode through the electrolyte. + ) is associated with the corresponding release of electrons, which can flow through an external circuit to power a load, as shown in Figure 1 However, when lithium dissociates into lithium cations (Li + ) and electron (e - ) when some lithium cations (Li + ) may react undesirably with polysulfides produced in the cathode and thus may no longer be available to generate output current or voltage. + ) reduces the overall capacity of the host cell or battery and may also facilitate corrosion of the anode, which can lead to cell failure.

[0180] In some implementations, the protective layer 516 can be provided as a passivation coating that can reduce the chemical reactivity of the anode 502 during battery cell assembly or formation. In some aspects, the protective layer 516 can be + ) and protects the anode 502 from lithium cations (Li + ) and polysulfide corrosion caused by chemical reactions. In other implementations, the protective layer 516 may be an artificial solid electrolyte interface phase (A-SEI), which may replace the naturally occurring SEI and / or other types of conventional A-SEI. In various implementations, the protective layer 516 may be deposited as a liner on top of one or more membranes disposed on the anode 502. In some aspects, the protective layer 516 may be a self-generated layer formed during an electrochemical reaction associated with an operating cycle of the battery. In some aspects, the protective layer 516 may have a thickness of less than 5 microns. In other aspects, the protective layer 516 may have a thickness between 0.1 and 1.0 microns.

[0181] In various implementations, one or more engineered additives that can facilitate the formation and / or deposition of the protective layer 516 on the anode 502 can be provided within the electrolyte of the battery. In other implementations, the engineered additive can be an active component of the protective layer 516. In some aspects, the protective layer 516 can provide tin ions and / or fluoride anions that can prevent undesirable lithium growth from the first edge 5181 and the second edge 5182 of the anode.

[0182] The graded layer 514 can be formed and / or deposited onto the anode 502 below the protective layer 516. In various implementations, the graded layer 514 can prevent lithium contained in or associated with the anode 502 from participating in undesirable chemical interactions and / or reactions with the electrolyte 540 that can cause lithium-containing dendrites to grow from the anode 502. The graded layer 514 can also facilitate the separation of lithium ions (Li + ) and fluoride ions to produce lithium fluoride. As discussed, the presence of lithium fluoride in or near the anode 502 can reduce the polysulfide shuttling effect. For example, the formation of lithium fluoride (e.g., by utilizing lithium cations (Li + ) and fluoride ions) can occur uniformly across the entire first edge 5181 and / or second edge 5182 of the anode. In this way, local areas of high lithium concentration in the electrolyte 540 near the anode 502 are substantially suppressed. Therefore, the lithium-lithium bonds that lead to the formation of lithium-containing dendrite structures extending longitudinally from the anode are correspondingly suppressed, thereby causing the lithium cations (Li +) is freely transported from the anode 502 to the electrolyte (e.g., as encountered during battery operation cycles). In some aspects, uniform distribution of lithium throughout the graded layer 514 can increase the uniformity of lithium ion flux during battery operation cycles. In some aspects, the graded layer 514 can be approximately 5 nanometers (nm) thick.

[0183] In one or more implementations, the graded layer 514 can structurally strengthen the main battery in a manner that not only reduces or prevents lithium-containing dendrite growth from the anode 502, but also increases the ability of the anode 502 to expand and contract without rupture during operating cycles of the main battery. In some aspects, the graded layer 514 has a 3D architecture with a graded concentration gradient (e.g., one or more constituent materials and / or components, including carbon, tin, and / or fluorine) that facilitates rapid lithium ion transport. Thus, the graded layer 514 significantly improves overall battery efficiency and performance.

[0184] In some implementations, the graded layer 514 can provide an electrochemically desirable surface on which the protective layer 516 can be grown or deposited. For example, in some aspects, the graded layer 514 can include compounds and / or organometallic compounds of, including but not limited to, aluminum, gallium, indium, nickel, zinc, chromium, vanadium, titanium, and / or other metals. In other aspects, the graded layer 514 can include oxides, carbides, and / or nitrides of aluminum, gallium, indium, nickel, zinc, chromium, vanadium, titanium, and / or other metals.

[0185] In some implementations, the graded layer 514 may include a carbonaceous material, including, but not limited to, flake graphene, few-layer graphene (FLG), carbon nano-onion (CNO), graphene nanosheets, or carbon nanotubes (CNT). In other implementations, the graded layer 514 may include carbon, oxygen, hydrogen, tin, fluorine, and / or other suitable chemical compounds and / or molecules derived from tin fluoride and one or more carbonaceous materials. The graded layer 514 may be prepared and / or deposited directly or indirectly on the anode 502 at different concentration levels. For example, the graded layer 514 may include 5 wt% carbonaceous material and the remainder 95 wt% tin fluoride, which may result in a relatively uniform dissociation of fluorine atoms and / or fluoride anions from tin fluoride.

[0186] Other suitable ratios include: 5% carbonaceous material to 95% tin fluoride; 10% carbonaceous material to 90% tin fluoride, 15% carbonaceous material to 85% tin fluoride, 20% carbonaceous material to 80% tin fluoride, 25% carbonaceous material to 75% tin fluoride, 30% carbonaceous material to 70% tin fluoride, 35% carbonaceous material to 65% tin fluoride, 40% carbonaceous material to 60% tin fluoride, 45% carbonaceous material to 55% tin fluoride, 50% carbonaceous material to 50% tin fluoride. % tin fluoride, 55% carbonaceous material and 45% tin fluoride, 55% carbonaceous material and 45% tin fluoride, 60% carbonaceous material and 40% tin fluoride, 65% carbonaceous material and 35% tin fluoride, 70% carbonaceous material and 30% tin fluoride, 75% carbonaceous material and 25% tin fluoride, 80% carbonaceous material and 20% tin fluoride, 85% carbonaceous material and 15% tin fluoride, 90% carbonaceous material and 10% tin fluoride, 95% carbonaceous material and 5% tin fluoride. Then, the fluorine atoms and / or fluoride anions can react with lithium cations (Li + ) uniformly react and combine to form lithium fluoride, as further discussed below.

[0187] In some implementations, between the anode 502 and the cathode ( Figure 5 The lithium cations (Li + ) can produce a tin-lithium alloy region 512 within the graded layer 514. In some aspects, operating cycles of the main battery can result in the lithium fluoride being uniformly dispersed within the tin-lithium alloy region 512. The uniform dispersion of the lithium fluoride can facilitate a defluorination reaction of at least some of the tin (II) fluoride (SnF2) within the tin fluoride layer 510 (and additional tin fluoride that can be dispersed into the graded layer 514 and / or the protective layer). The fluorine atoms and / or fluoride anions that can be provided by the defluorination reaction can react with at least some of the lithium cations (Li cations) present in or near the anode 502. + ) to produce lithium fluoride (LiF) and thereby correspondingly prevent at least some lithium cations (Li + ) are bonded to each other and result in lithium dendrite growth from the anode 502.

[0188] For example, at least a portion of the fluorine atoms and / or fluorine anions present in tin fluoride may dissociate from the protective layer 516 and generate tin cations (Sn 2+ ) and fluoride anion (2F - The fluorine atoms and / or fluorine anions dissociated from the protective layer 516 may chemically bond to at least some of the lithium cations (Li ) present in the electrolyte 540 and / or dispersed throughout the protective layer 516 or the graded layer 514. + ). In some aspects, the dissociated fluorine atoms can form Li—F bonds or Li—F compounds in the tin-lithium alloy region 512. In other aspects, the dissociated fluorine atoms can form a tin fluoride layer 510 within the graded layer 514.

[0189] Additionally, in one implementation, at least some of the defluorinated tin fluoride can be uniformly dispersed throughout the graded layer 514 to produce lithium fluoride (LiF) crystals. The lithium fluoride crystals can act as an electrical insulator and prevent electrons from flowing from the anode 502 through the first edge 5181 and / or the second edge 5182 of the anode 502 into the electrolyte 540.

[0190] In various implementations, the graded layer 514 can be deposited on the anode 502 by one or more of atomic layer deposition (ALD), chemical vapor deposition (CVD), or physical vapor deposition (PVD). For example, ALD can be used to deposit a protective film on the anode 502, such as, for example, an ALD film that at least partially reacts with the electrolyte 540 during a high pressure bonding process. Thus, the ALD film can be used to create the protective layer 516 or the graded layer 514 using atomic planes that can be used for lithium transfer. This lithium transfer can be similar in principle to the transfer observed for few-layer graphene (FLG) or graphite, where alternating graphene layers in the FLG or graphite embed various forms of lithium cations (Li + ), including in the form of lithium titanium oxide (LTO), lithium iron phosphate (PO3) (LFP). The described forms of intercalated lithium (e.g., LTO and / or LFP) can be oriented to facilitate rapid lithium atom and / or lithium ion transport and / or diffusion, which can be beneficial to the formation and / or synthesis of lithium fluoride (e.g., in the tin fluoride layer 510 and / or elsewhere), as previously described. Additional forms of intercalated lithium (e.g., perovskite lithium lanthanum titanate (LLTO)) can also function to store lithium within the anode 502.

[0191] In some implementations, the graded layer 514 may include a variety of different types and / or forms of carbon and / or carbonaceous materials, each having one or more physical properties that may be selected or configured to adjust the reactivity of the carbon with contaminants (such as polysulfides) present in the electrolyte 540 and / or the anode 502. In some aspects, the selectable physical properties may include, but are not limited to, porosity, surface area, surface functionalization, or conductivity. Additionally, the graded layer 514 may include a binder or other additive that may be used to adjust one or more physical properties of the carbonaceous material to achieve the desired reactivity of the carbon supplied by the carbonaceous material with polysulfides present in the electrolyte 540 and / or the anode 502.

[0192] In one implementation, the carbonaceous material within the graded layer 514 can entrap undesirable contaminants and thereby prevent the contaminants from chemically reacting with available lithium at the exposed surfaces of the anode 502. Alternatively, undesirable contaminants (e.g., polysulfides) can chemically react with various exposed surfaces of the carbonaceous material within the graded layer 514 (e.g., through carbon-lithium interactions). In some implementations, the carbonaceous material within the graded layer 514 can bind to available lithium. + ) can be selected or varied via a chemical reaction induced during preparation of the graded layer 514.

[0193] In some implementations, various carbon allotropes may be incorporated into the graded layer 514 (such as in one or more portions of the tin-lithium alloy region 512 and / or the tin fluoride layer 510). These carbon allotropes may be functionalized with one or more reactants and used to form a sealant layer and / or region at the interface of the carbon nanodiamonds and the electrolyte 540 within the graded layer 514. In some aspects, the carbon nanodiamonds may increase the mechanical robustness of the anode 502 and / or the graded layer 514. In other aspects, the carbon nanodiamonds may also provide exposed carbonaceous surfaces that may be used to reduce polysulfide shuttling effects by microscopically confining and / or bonding polysulfides present in the electrolyte 540 in a manner that keeps the polysulfides within a defined region outside the anode 502 of the cell.

[0194] Alternatively, in other implementations, the carbon nanodiamonds in the graded layer 514 may be replaced with a nanodiamond having a specific L A Size (e.g., sp 2 In some aspects, the use of the carbonaceous materials disclosed herein in the battery can increase the carbon stacking and layer formation within the hierarchical layer 514. The stripped and oxidized carbonaceous materials can also produce a more uniform layered structure within the hierarchical layer 514 (compared to the unstripped and oxidized carbonaceous materials). In some aspects, solvents such as tetrabutylammonium hydroxide (TBA) and / or dimethylformamide (DMF) treatment can be applied to the carbonaceous materials disclosed herein to increase the wetting of the exposed carbonaceous surfaces within the hierarchical layer 514.

[0195] In some implementations, the slurry used to form the graded layer 514 can be doped to improve or otherwise affect the crystal structure of the carbonaceous material within the graded layer 514. For example, the addition of certain dopants can affect the crystal structure of the carbonaceous material in some corresponding manner, and functional groups can be added within the graded layer 514 (e.g., via grafting onto exposed carbon atoms within the carbonaceous material).

[0196] In some implementations, a carbonaceous material having an exposed surface functionalized with one or more of fluorine-containing or silicon-containing functional groups may be included within the graded layer 514. In other implementations, a carbonaceous material having an exposed surface functionalized with one or more of fluorine-containing or silicon-containing functional groups may be deposited below the graded layer 514 to form a stable SEI at the interface between the graded layer 514 and the anode 502. In one implementation, the stable SEI may replace the protective layer 516. In some implementations, the graded layer 514 may be slurry cast and / or deposited onto the anode 502 having a lithium and carbon interfacial phase using other techniques, either of which may be functionalized with silicon and / or nitrogen to inhibit polysulfide diffusion and migration to the exposed surface of the anode 502. Additionally, specific polymers and / or crosslinkers may be incorporated into the graded layer 514 to mechanically strengthen the graded layer 514, improve lithium ion transport across the graded layer 514, or increase the uniformity of lithium ion flux across the graded layer 514. Exemplary polymers and / or polymeric materials suitable for incorporation into the graded layer 514 may include poly(ethylene oxide) and poly(ethylene imine). Exemplary crosslinking agents suitable for incorporation into the graded layer 514 may include inorganic crosslinking agents (e.g., borates, aluminates, silicates), multifunctional organic molecules (e.g., diamines, diols), polyureas, or high molecular weight (MW) (e.g., >10,000 Daltons) carboxymethyl cellulose (CMC).

[0197] Various manufacturing methods can be used to produce the graded layer 514. In one implementation, direct coating of the interface between the anode 502 and the electrolyte 540 can be performed by dispersing carbonaceous materials and other chemicals dissolved in a carrier (e.g., solvents, binders, polymers) prior to depositing and / or forming the graded layer 514. In another implementation, the deposition of the graded layer 514 can be performed as a separate operation, or various other active ingredients (e.g., metals, carbonaceous materials, tin fluoride, etc.) can be added to the slurry, which can be cast onto the anode 502. Alternatively, in another implementation, the protective layer 516 can be directly transferred to the anode 502 by a calendaring roller lamination process. The protective layer 516 and / or the graded layer 514 can also be incorporated with a partially cured lithium ion conductive epoxy resin to, for example, better increase adhesion to lithium during the calendaring roller lamination process.

[0198] In one implementation, the carbon-containing layered structure ( Figure 5 ) may be disposed on anode 502 to replace hierarchical layer 514. The carbonaceous layered structure may include atomic planes that can be used for lithium transfer and may transfer lithium cations (Li ) provided by electrolyte 540 in a manner that can direct the formation of lithium fluoride in various parts of the battery. +) is uniformly transferred to the entire protective layer 516. In various implementations, the carbon-containing layered structure may include one or more arrangements of few-layer graphene (FLG) or graphite and / or may be intercalated with lithium and produce one or more reaction products including lithium tin oxide (LTO), lithium iron phosphate (LFP), or lithium lanthanum titanate perovskite (LLTO).

[0199] In some implementations, the tin fluoride layer 510 can act as a protective layer against corrosion, including corrosion of the protective layer 516, the graded layer 514, or the copper-containing surface and / or region of the anode 502. In some aspects, the tin fluoride layer 510 can also provide a uniform seed layer suitable for lithium deposition, and thereby inhibit dendrite formation. In addition, in some implementations, the tin fluoride layer 510 may include one or more lithium ion intercalation compounds, any one or more of which have a low voltage penalty. Suitable lithium ion intercalation compounds may include graphitic carbon (e.g., graphite, graphene, reduced graphene oxide rGO). In one implementation, during the manufacture of the anode 502, lithium cations (Li ) are deposited on the exposed carbonaceous surface within the tin fluoride layer 510 before being plated. + ) may tend to intercalate. In this way, before commencing lithium plating and / or electroplating operations, the tin fluoride layer 510 has a uniform Li distribution ready to act as a seed layer.

[0200] In one implementation, one or more conformal coatings may be applied to portions of the anode 502 such that the resulting conformal coating contacts and conforms to the first edge 5181 and / or the second edge 5182 of the anode 502. In some aspects, the conformal coating may begin as a first spacer edge protection region 5301 and a second spacer edge protection region 5302 that react or otherwise combine with one or more of the protective layer 516, the tin-lithium alloy region 512, and / or the tin fluoride layer 510 to form a conformal coating 544 that at least partially seals and protects the surface and / or interface between the lithium in the anode 502 and various species (e.g., copper (Cu)) suspended in the electrolyte. In some aspects, the dissociation of fluorine atoms from the tin fluoride present in the conformal coating 544 may react with the lithium in the anode 502 to form lithium fluoride, rather than forming or growing into lithium dendrites. In this way, the conformal coating 544 may reduce the formation or growth of lithium dendrites from the anode 502.

[0201] The conformal coating 544 can be deposited or disposed on the anode 502 at many different thicknesses. In some aspects, the conformal coating 544 can be less than 5 μm thick. In other aspects, the conformal coating 544 can be less than 2 μm thick. In some other aspects, the conformal coating 544 can be less than 1 μm thick. During battery cycling, these thickness levels can hinder the migration of polysulfides to the anode 502, thereby preventing at least some lithium cations (Li +) reacts with polysulfides. Lithium cations (Li + ) can be used to transfer from the anode to the cathode during the battery discharge cycle.

[0202] The conformal coating 544 (as well as the protective layer 516 and the graded layer 514) can uniquely regulate the flux of lithium ions toward the first edge 5181 and / or the second edge 5182 of the anode 502 and thereby prevent corrosion of the anode 502. This regulation can function in a manner similar to the gate spacers used during the manufacture of polysilicon (poly-Si) gates. Specifically, during the manufacture of integrated circuits (ICs), gate spacers or gate sidewall constructs can be used to protect and mechanically support polysilicon gates. Similarly, the conformal coating 544 can be used to provide a protective layer for the anode 502. Figure 5 The edge protection provided by the anode 502 regulates the flux of lithium ions toward the first edge 5181 and / or the second edge 5182 of the anode 502 and thereby prevents corrosion of the anode 502. This type of edge protection provided to the anode 502 by the conformal coating 544 can be equally applicable to other battery and / or electrochemical cell formats and / or configurations, such as (but not limited to) cylindrical cells, stacked cells, etc., with various constructs specifically engineered to fit the parameters of each of such designs.

[0203] In some implementations, the fabrication and / or deposition of the conformal coating 544, protective layer 516, and / or graded layer 514 on the anode 502 may depend on the type of battery or cell construct incorporating the anode 502, for example, a cylindrical cell versus a pouch cell and / or a prismatic cell. In one implementation, for a cylindrical cell, the metal anode may be comprised of an electroactive material, typically metallic lithium and / or a lithium-containing alloy, such as graphite and / or other carbonaceous composites including lithium, as well as any fully uniform or multilayered material sheet. In one example, a solid metallic lithium foil used as the anode 502 may be attached to a copper substrate used as a current collector 520 to facilitate the transfer of electrons to an external load, such as through a tab 546. Figure 5 In other implementations, the anode structure 500 can include the anode 502 without the current collector 520, wherein the carbonaceous material contained within the anode 502 can provide a conductive medium coupled to the circuit.

[0204] In some embodiments, the anode structure 500 can be incorporated into an electrochemical cell and / or battery by winding around a mandrel. Cylindrical cell layouts typically use double-sided anodes, such as the anode structure 500. In some embodiments, a cylindrical cell configuration using the anode structure 500 can use a conformal coating 544 to protect the first edge 5181 and / or the second edge 5182 of the anode 502. The uniform protection provided by the conformal coating 544 may be referred to herein as "edge protection". In one embodiment, edge protection can be incorporated into a cell using the anode structure 500 by extending the size and / or area of ​​the protective layer 516 to be superimposed on any geometrically induced edge effects (e.g., surface roughness) of the anode.

[0205] In other implementations, the anode structure 500 may be incorporated into a pouch cell and / or a prismatic battery. In general, two constructions of pouch cells and / or prismatic cells may be manufactured, including (1): a jellyroll cell (e.g., known in the industry as a lithium-polymer cell), where two mandrel-wound electrodes may be produced in a manner similar to cylindrical cells as previously discussed; and (2): a stacked plate cell, which may be cut from a precast and / or prelaminated anode sheet, such that, for example, the unprotected edges of the anode 502 (when prepared in a stacked plate configuration) are exposed and susceptible to corrosion, rapid ion flux, and exposure to the cell. In a stacked plate configuration, the conformal coating 544 may protect the anode 502 and prevent lithium oversaturation in the electrolyte 540. In this way, the conformal coating 544 may control lithium plating on the anode 502 during the operating cycle of the battery.

[0206] In some implementations, during cell assembly or cell rest periods, one or more chemical reactions may occur between the electrolyte 540 and the anode 502 (involving solvent decomposition and / or addition reactions). These chemical reactions may help produce the conformal coating 544. In some aspects, higher and / or lower temperatures (e.g., relative to room temperature and / or 20° C.) may be used as a stimulus for lithium-induced polymerization of the conformal coating 544. For example, lithium-induced polymerization may occur in the presence of one or more catalysts and / or by using lithium metal and its associated chemical reactivity as an inducer to initiate free radical-based polymerization of component substances within any one or more layers in the anode structure 500 and / or the conformal coating 544. In addition, electrochemical reactions under electrical bias in the forward or reverse direction may be used to manufacture and / or deposit the conformal coating 544 on the anode 502, and auxiliary metals and / or salts may also be used as additives that may decompose to form an alloy on the first edge 5181 and / or second edge 5182 of the metallic lithium in the anode 502 exposed to the electrolyte 540. For example, a suitable additive may contain one or more metallic species, for example, that are desired to co-alloy with lithium or to be used as a barrier layer to reduce lithium transfer to the first edge 5181 and / or the second edge 5182 of the anode 502 .

[0207] Figure 6 According to some implementations, Figure 5 Schematic diagram of an enlarged portion 600 of the anode structure 500. The enlarged portion 600 shows the first spacer edge protection region 5301 and the second spacer edge protection region 5302 ( Figure 6 The arrangement of the edge protection area 530) in a direction orthogonal to the first edge 5181 and / or the second edge 5182 is as follows: Figure 5 Thus, the edge protection region 530, which may include a carbonaceous material 610 organized into a structure and / or lattice, may prevent lithium cations (Li + ) undesirably escapes the anode 502 across the edge protection region 530. In this way, lithium ion dissociation, flux, transport and / or other movement can be Figure 6 The entire enlarged portion 600 (and Figure 5 The anode structure 500 of the embodiment of the present invention is effectively guided to the anode structure 500, thereby generating an optimal battery operation cycle. In some implementations, the carbonaceous material 610 used to generate the edge protection region may include few-layer graphene (FLG), multi-layer graphene (MLG), graphite, carbon nanotubes (CNT), carbon nano onions (CNO), etc. The carbonaceous material 610 (for example, Fig. 8A , Figure 8B , Fig. 9A , Fig. 9B , Fig. 10A and / or Fig. 10B) can be synthesized at different concentration levels, self-nucleated, or otherwise joined together to provide full tunability of the edge protection region 530. For example, the density, thickness, and / or composition can be designed to minimize lithium ion penetration compared to the protective layer 516 or the graded layer 514 to guide the lithium ion penetration accordingly. In some implementations, the edge protection region 530 may be less than 5 μm thick. In other aspects, the edge protection region 530 may be less than 2 μm thick. In some other aspects, the edge protection region 530 may be less than 1 μm thick. In some implementations, as with the binder 620, a conductive additive 640 may be added to the carbonaceous material 610.

[0208] Figure 7 Schematic diagram of a polymer network 710 according to some implementations. In some aspects, the polymer network 710 can be Figure 2 The polymer network 710 may be disposed on the anode 702. The anode 702 may be formed as an alkali metal layer having one or more exposed surfaces including a plurality of nanostructures or microstructures containing an alkali metal. The alkali metal may include, but is not limited to, lithium, sodium, zinc, indium, and / or gallium. During the operating cycle of the battery, the anode 702 may release alkali metal cations.

[0209] The carbonaceous material layer 714 can be grafted with a fluorinated polymer chain and deposited on one or more exposed surfaces of the anode 702. The grafting can be based on (e.g., starting with) activating the carbonaceous material with one or more free radical initiators, such as benzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN), followed by reaction with monomer molecules. The polymer network 710 can be based on the carbonaceous material of the fluorinated polymer chain and the layer 714 cross-linked to each other, so that the layer 714 is consumed during the generation of the polymer network 710. In some implementations, the polymer network 710 may have a thickness between about 0.001 μm and 5 μm and include a fluorinated polymer chain between about 0.001 wt % and 2 wt %. In some other implementations, the polymer network 710 may include a variety of carbonaceous materials grafted with a fluorinated polymer chain between about 5 wt % and 100 wt % and the rest is a fluorinated polymer or one or more non-fluorinated polymers or one or more cross-linkable monomers or a combination thereof. In one implementation, the carbonaceous material grafted with fluorinated polymer chains can include 5 to 50 wt% fluorinated polymer chains with the remainder being carbonaceous material.

[0210] During battery cycling, the carbon-fluorine bonds within the polymer network 710 can chemically react with the newly formed lithium metal and convert into carbon-lithium bonds (C-Li). These C-Li bonds can in turn react with the carbon-fluorine bonds within the polymer network 710 via the Woods reaction 750 to further crosslink the polymer network through the newly formed CC bonds and form alkali metal-containing fluorides (such as lithium fluoride (LiF)). Additional polymer network crosslinking resulting in uniform formation of alkali metal-containing fluorides can thereby inhibit alkali metal dendrite formation 740 associated with the anode 702, thereby improving battery performance and life. In one implementation, grafting fluorinated methyl / acrylate (FMA) to one or more exposed graphene surfaces of the carbonaceous material in layer 714 can be performed in an organic solution, for example, resulting in the formation of graphene-grafted-poly-FMA, etc. The incorporation of carbon-fluorine bonds on the exposed graphene surface can enable the Woods reaction 750 to occur between the carbon-fluorine bonds and the metal surface of the alkali metal (e.g., lithium) provided by the anode 702. In this manner, completing the Woods reaction 750 can result in the formation of a polymer network 710. In some aspects, the polymer network 710 can include a density gradient 716 after completing the Woods reaction 750. The density gradient 716 can include interconnected graphene sheets and can be infused with one or more in situ formed metal fluoride salts. Additionally, layer porosity and / or mechanical properties can be tuned by a combination of carbon loading and / or functionalized carbons, each having a unique and / or different physical structure.

[0211] In some implementations, the carbonaceous material within the density gradient 716 may include one or more of flat graphene, wrinkled graphene, a plurality of carbon nanotubes (CNTs), or a plurality of carbon nanoonions (CNOs) (e.g., Fig. 8A and / Figure 8B Describe and Figures 9A-9B and Figures 10A-10B ). In one implementation, the graphene nanosheets may be dispersed throughout the polymer network 710 and isolated from each other. The dispersion of the graphene nanosheets includes one or more different concentration levels. In one implementation, the dispersion of the graphene nanosheets may include at least some carbonaceous materials functionalized with at least some fluorinated polymer chains.

[0212] For example, the fluorinated polymer chain may include one or more acrylate or methacrylate monomers including 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate (DFHA), 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl methacrylate (HDFDMA), 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate (OFPMA), tetrafluoropropyl methacrylate (TFPM), 3-[3,3,3-trifluoro-2-hydroxy-2-(trifluoromethyl)propyl]bicyclo[2.2.1]hept-2-yl methacrylate (HFA monomer), or vinyl-based monomers including 2,3,4,5,6-pentafluorostyrene (PFSt).

[0213] In some implementations, the fluorinated polymer chains may be grafted to the surface of the carbonaceous material layer and may thereby chemically interact with one or more surfaces of the alkali metal of the anode via the Woods reaction 750. In organic chemistry, organometallic chemistry, and inorganic main group polymers, the Woods reaction is a coupling reaction in which two alkyl halides react with metallic sodium (or some other metal) in a dry ether solution to form higher alkanes. In this reaction, the alkyl halide is treated with an alkali metal (e.g., metallic sodium) in a dry ether (water-free) solution to produce higher alkanes. In the case of sodium, the intermediate product of the Woods reaction is a highly polar and highly reactive carbon-sodium metal bond, which in turn chemically reacts with a carbon-halogen bond to produce a newly formed CC bond and a sodium halide. The formation of new carbon-carbon bonds allows the use of the Woods reaction to prepare higher alkanes containing an even number of carbon atoms, for example:

[0214] 2R-X+2Na→R-R+2Na + X - (Equation 1)

[0215] Other metals are also used to effect the Woods coupling, especially silver, zinc, iron, activated copper, indium, and mixtures of manganese chloride and cupric chloride. A related reaction that treats aryl halides is called the Wurtz–Fittig reaction. This can be explained by the formation of a free radical intermediate and its subsequent disproportionation to give an olefin. The Woods reaction 750 occurs via a free radical mechanism that enables a side reaction to produce an olefin product. In some implementations, the chemical interactions associated with the Woods reaction as described above can form an alkali metal fluoride, such as lithium fluoride.

[0216] In one implementation, the polymer network 710 may include an interface layer 718 in contact with the anode 702. A protective layer 720 may be disposed on top of the interface layer 718, which may be based on a Woods reaction 750 at the interface between the anode 702 and the polymer network 710. The interface layer 718 may have a relatively high cross-link density (e.g., fluorinated polymers, etc.), a high metal-fluoride concentration, and a relatively low carbon-fluorine bond concentration. The protective layer 720 may have a relatively low cross-link density, a low metal-fluoride concentration, and a high carbon-fluorine bond concentration compared to the interface layer 718.

[0217] In some implementations, the interfacial layer 718 may include a cross-linkable monomer such as methacrylate (MA), acrylate, vinyl functional group, or a combination of epoxy functional group and amine functional group. In one implementation, the protective layer 720 may be characterized by a density gradient 716. In this way, the density gradient 716 may be associated with one or more self-healing properties of the protective layer 720 and / or may strengthen the polymer network 710. In some implementations, the protective layer 720 may further inhibit alkali metal dendrite formation 740 from the anode 702 during battery cycling.

[0218] In operation, the interface layer 718 can inhibit alkali metal dendrite formation 740 associated with the anode 702 by uniformly generating metal fluoride (e.g., lithium fluoride) at the interface across the length of the anode 702. The uniform generation of metal fluoride, such as via conversion to metal fluoride, results in dissolution of the dendrite surface, ultimately inhibiting alkali metal dendrite formation 740. Additionally, cross-linking of the fluorinated polymer chains on the remaining dendrites can further inhibit alkali metal dendrite formation 740. In some implementations, the density gradient 716 can be tuned to control the degree of cross-linking between the fluorinated polymer chains.

[0219] Fig. 8A A simplified cross-sectional view of an exemplary carbonaceous particle 800 having graded porosity according to some implementations is shown. The carbonaceous particle 800 can be synthesized in a reactor and output in a controlled manner to produce Figure 1 The cathode 110 and / or the anode 120, Figure 2 The cathode 210 and / or the anode 220 or Figure 3Electrode 300. Carbonaceous particles 800, which may also be referred to as subject compositions, include multiple regions nested within each other. Each region may include at least a first porosity region 811 and a second porosity region 812. The first porosity region 811 may include a plurality of first pores 801, and the second porosity region 812 may include a plurality of second pores 802. In some aspects, each region may be separated from a directly adjacent region by at least some of the first pores 801. The first pores 801 may be dispersed throughout the first porosity region 811 of the carbonaceous particles 800, and the second pores 802 may be dispersed throughout the second porosity region 812 of the carbonaceous particles 800. In this way, the first pores 801 may be associated with a first pore density, and the second pores 802 may be associated with a second pore density different from the first pore density. In some aspects, the first pore density can be between about 0.0 cubic centimeters (cc) / g and 2.0 cc / g, and the second pore density can be between about 1.5 and 5.0 cc / g. In some aspects, the first pores 801 can be configured to retain polysulfides 820 , and the second pores 802 can provide exit pathways from the carbonaceous particulates 800 .

[0220] A group of carbonaceous particles 800 may be joined together to form a carbonaceous aggregate (not shown for simplicity), and a group of carbonaceous aggregates may be joined together to form a carbonaceous agglomerate (not shown for simplicity). In some implementations, the first pores 801 and the second pores 802 may be dispersed throughout the aggregate formed by the corresponding group of carbonaceous particles 800. In some aspects, the first porosity region 811 may be at least partially encapsulated by the second porosity region 812, so that the corresponding agglomerate may include some first pores 801 and / or some second pores 802.

[0221] In some implementations, the carbonaceous particles 800 may have a major dimension "A" in the approximate range between 20 nm and 150 nm, the aggregates formed by a group of carbonaceous particles 800 may have a major dimension in the approximate range between 20 nm and 10 μm, and the agglomerates formed by a group of aggregates may have a major dimension in the approximate range between 0.1 μm and 1,000 μm. In some aspects, at least some of the first pores 801 and the second pores 802 have a major dimension in the approximate range between 1.3 nm and 32.3 nm. In one implementation, each first pore 801 has a major dimension in the approximate range between 0 nm and 100 nm.

[0222] The carbonaceous particle 800 may also include a plurality of deformable regions 813 distributed along the periphery 810 of the carbonaceous particle 800. The carbonaceous particle 800 may be conductive along a bonded boundary (such as the periphery 810) with one or more other carbonaceous particles. The carbonaceous particle 800 may also confine the polysulfide 820 within the first pore 801 and / or at one or more barrier regions 822, thereby inhibiting the migration of the polysulfide 820 to the anode and increasing the lithium cation (Li + ) can be transferred from the anode to the cathode of the main battery.

[0223] In some implementations, the carbonaceous particles 800 may have a size of 10 m 2 / g to 3,000m 2 / g of exposed carbon surface. In other embodiments, the carbonaceous particulate 800 may have a composite surface area including sulfur 824 microscopically defined within a plurality of first pores 801 and / or a plurality of second pores 802. As used herein, the first pores 801 and / or the second pores 802 that microscopically define the polysulfide 820 may be referred to as "functional pores". In some aspects, one or more of the carbonaceous particulates, aggregates formed by a corresponding group of carbonaceous particulates, or agglomerates formed by a corresponding group of aggregates may include one or more exposed carbon surfaces configured to nucleate sulfur 824. The composite surface area may be approximately 10 m 2 / g to 3,000m 2 / g, and the carbonaceous particulates 800 can have a sulfur to carbon weight ratio of approximately 1:5 to 10: 1. In some aspects, the carbonaceous particulates 800 can have an electrical conductivity in an approximate range of 100 S / m to 20,000 S / m at a pressure of 12,000 pounds per square inch (psi).

[0224] In some implementations, the carbonaceous particles 800 may include a surfactant or polymer, including one or more of styrene butadiene rubber, polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose, polyvinyl pyrrolidone, and / or polyvinyl acetate, which may act as a binder to bond together a group of carbonaceous particles 800. In other implementations, the carbonaceous particles 800 may include a gel-phase electrolyte or a solid-phase electrolyte disposed within at least some of the first pores 801 or the second pores 802.

[0225] Figure 8B Schematic diagram showing an example of a three-segment particle 850 according to some implementations. In various implementations, the three-segment particle 850 can be Fig. 8AAn example of a carbonaceous particle 800 of the present invention. The three-segment particle 850 may include three discrete segments, such as (but not limited to) a first segment 851, a second segment 852, and a third segment 853. In some aspects, each of the segments 851-853 surrounds and / or encapsulates the previous segment. For example, the first segment 851 may be surrounded or encapsulated by the second segment 852, and the second segment 852 may be surrounded or encapsulated by the third segment 853. The first segment 851 may correspond to an inner region of the three-segment particle 850, the second segment 852 may correspond to an intermediate transition region of the three-segment particle 850, and the third segment 853 may correspond to an outer region of the three-segment particle 850. In some aspects, the three-segment particle 850 may include a permeable shell 855 that deforms in response to contact with one or more adjacent non-three-segment particles and / or three-segment particles 850.

[0226] In some implementations, the first segment 851 may have a relatively low density, a relatively low conductivity, and a relatively high porosity, the second segment 852 may have a medium density, a medium conductivity, and a medium porosity, and the third segment 853 may have a relatively high density, a relatively high conductivity, and a relatively low porosity. In some aspects, the first segment 851 may have a carbonaceous material density between about 1.5 g / cc and 5.0 g / cc, the second segment 852 may have a carbonaceous material density between about 0.5 g / cc and 3.0 g / cc, and the third segment 853 may have a carbonaceous material density between about 0.0 and 1.5 g / cc. In other aspects, the first segment 851 may include pores having a width between about 0 and 40 nm, the second segment 852 may include pores having a width between about 0 and 35 nm, and the third segment 853 may include pores having a width between about 0 and 30 nm. In some other implementations, the second segment 852 may not be defined for a three-segment particle 850. In one implementation, the first segment 851 may have a major dimension D1 between approximately 0 nm and 100 nm, the second segment 852 may have a major dimension D2 between approximately 20 nm and 150 nm, and the third segment 853 may have a major dimension D3 of approximately 200 nm.

[0227] Aspects of the present disclosure recognize that the unique layout of the three-segment particle 850 and the relative sizes, porosities, and conductivity of the first segment 851, the second segment 852, and the third segment 853 can be selected and / or modified to achieve a desired balance between minimizing the polysulfide shuttling effect and maximizing the specific capacity of the main battery. Specifically, in some aspects, the pores can decrease in size and volume from one segment to another. In some implementations, the three-segment particle can be composed entirely of one segment with a range of pore sizes and pore distributions (e.g., pore densities). For Figure 8BIn the example, pores 861 associated with the first segment 851 or the first porosity region have a relatively large width and can be defined as macropores, pores 862 associated with the second segment 852 or the second porosity region have a medium width and can be defined as mesopores, and pores 863 associated with the third segment 853 or the third porosity region have a relatively small width and can be defined as micropores.

[0228] A group of three-segment particles 850 may be joined together to form an aggregate (not shown for simplicity), and a group of aggregates may be joined together to form an agglomerate (not shown for simplicity). In some embodiments, a plurality of mesopores may be dispersed throughout the aggregate formed by the corresponding group of carbonaceous particles 800. In some aspects, the first porosity region 811 may be at least partially encapsulated by the second porosity region 812 so that the corresponding aggregate may include one or more mesopores and one or more macropores. In one embodiment, each mesopore may have a major dimension between 3.3 nanometers (nm) and 19.3 nm, and each macropore may have a major dimension between 0.1 μm and 1,000 μm. In some cases, the three-segment particles 850 may include carbon fragments that are intertwined with each other and separated from each other by at least some of the mesopores.

[0229] In some implementations, the three-segment particle 850 may include a surfactant or polymer, including one or more of styrene butadiene rubber, polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose, polyvinyl pyrrolidone, and / or polyvinyl acetate, which may act as a binder to bond a group of carbonaceous materials together. In other implementations, the three-segment particle 850 may include a gel-phase electrolyte or a solid-phase electrolyte disposed within at least some of the pores.

[0230] In some implementations, a three-segment particle 850 may have a 10 m 2 / g to 3,000m 2 The surface area of ​​exposed carbonaceous surface is approximately within the range of 10 m / g and / or 10 m 2 / g to 3,000m 2 In one implementation, the subject composition including a plurality of three-segment particles 850 may have a conductivity in the approximate range of between 100 S / m and 20,000 S / m at a pressure of 12,000 pounds per square inch (psi) and a sulfur to carbon weight ratio of between about 1:5 and 10:1.

[0231] Figure 8C FIG. 1 shows a diagram showing a method according to some implementations. Figure 8BAn exemplary step function 800C of the average pore volume in each region of a three-segment particle 850. As discussed, the pores distributed throughout the three-segment particle 850 may have different sizes, volumes, or distributions. In some implementations, the average pore volume may decrease based on the distance between the center of the three-segment particle 850 and an adjacent segment, such that, for example, pores associated with the first segment 851 or first porosity region have a relatively large volume or pore size, pores associated with the second segment 852 or second porosity region have a medium volume, and pores associated with the third segment 853 or third porosity region have a relatively small volume. The interior regions have a higher pore volume than the regions near the periphery. Regions with higher pore volumes provide higher sulfur loading, while lower pore volume outer regions mitigate migration of polysulfides during cell cycling. Figure 8C In the example of FIG. 5 , the average pore volume in the inner region is about 3 cc / g, the average pore volume in the outermost region is -0.5 cc / g, and the average pore volume in the middle region is between 0.5 cc / g and 3 cc / g.

[0232] Fig.8D A graph 800D depicting an exemplary distribution of pore volume versus pore width for carbonaceous particles described herein is shown. As depicted in graph 800D, pores associated with relatively high pore volumes may have relatively low pore widths, for example, such that when pore volume decreases, pore widths generally increase. In some aspects, pores having pore widths less than about 1.0 nm may be referred to as micropores, pores having pore widths between about 3 and 11 nm may be referred to as mesopores, and pores having pore widths greater than about 24 nm may be referred to as macropores.

[0233] Fig. 9A A micrograph 900 of a plurality of carbonaceous structures 902 is shown according to some implementations. In some implementations, each of the carbonaceous structures 902 can have a substantially hollow core region surrounded by various bulk carbon growths and / or stratifications. In some aspects, the bulk carbon growths and / or stratifications can be referenced to Fig. 8A and Figure 8B Examples of overall carbon growth and / or layering described herein. In some cases, the carbonaceous structure 902 may include multiple concentric multilayer fullerenes organized at different densities and / or concentration levels and / or similarly shaped carbonaceous structures. For example, the actual final shape, size, and graphene configuration of each of the carbonaceous structures 902 may depend on various manufacturing methods. In some aspects, the carbonaceous structure 902 may exhibit poor water solubility. Therefore, in some implementations, non-covalent functionalization may be used to change one or more dispersibility properties of the carbonaceous structure 902 without affecting the intrinsic properties of the underlying carbon nanomaterial. In some aspects, the underlying carbon nanomaterial may be a constituent sp 2In some implementations, each of the carbonaceous structures 902 can have a diameter between approximately 20 and 500 nm. In various implementations, groups of carbonaceous structures 902 can be agglomerated and / or joined together to form aggregates 904. Additionally, groups of aggregates 904 can be agglomerated and / or joined together to form agglomerates 906. In some aspects, one or more of the carbonaceous structures 902, aggregates 904, and / or agglomerates 906 can be used to form Figure 1 Battery 100, Figure 2 Battery 200 or Figure 3 The electrode 300 is an anode and / or a cathode.

[0234] Fig. 9B A micrograph 950 of an aggregate formed from a carbonaceous material according to some implementations is shown. In some implementations, the aggregate 960 may be Fig. 9A In one implementation, the outer carbonaceous shell structure 952 may be fused together with carbon provided by other carbonaceous shell structures 954 to form a carbonaceous structure 956. A group of carbonaceous structures 956 may coalesce and / or join with each other to form an aggregate 1010. In some aspects, the core region 958 of each of the carbonaceous structures 956 may be tunable, for example, because the core region 958 may include interconnected graphene structures at various defined concentration levels, such as reference Fig. 8A and / or Figure 8B In some implementations, some of the carbonaceous structures 956 may have a first concentration of interconnected carbon between approximately 0.1 g / cc and 2.3 g / cc at or near the outer carbonaceous shell structure 952. Each of the carbonaceous structures 956 may have a lithium cation (Li + ) is transmitted to the pores of the core region 1008.

[0235] In some implementations, the pores in each of the carbonaceous structures 956 may have a width or size between about 0.0 nm and 0.5 nm, between about 0.0 and 0.1 nm, between about 0.0 and 6.0 nm, or between about 0.0 and 35 nm. Each carbonaceous structure 956 may also have a second concentration at or near the core region 958 that is different from the first concentration. For example, the second concentration may include a plurality of relatively low density carbonaceous regions arranged concentrically. In one implementation, the second concentration may be lower than the first concentration, between about 0.0 g / cc and 1.0 g / cc or between about 1.0 g / cc and 1.5 g / cc. In some aspects, the relationship between the first concentration and the second concentration may be used to confine sulfur or polysulfide within the respective electrodes and to allow lithium cations (Li +For example, during an operating cycle of the lithium-sulfur battery, sulfur and / or polysulfides may travel through a first concentration and be at least temporarily confined to and / or dispersed throughout a second concentration.

[0236] In some implementations, at least some of the carbonaceous structures 956 may include CNO oxides organized as a monolithic and / or interconnected growth and produced in a thermal reactor. For example, the carbonaceous structures 956 may be decorated with cobalt nanoparticles according to the following example recipe: Cobalt (II) acetate (C4H6CoO4), a cobalt salt of acetic acid (usually in the form of a tetrahydrate Co(CH3CO2)2·4H2O, which may be abbreviated as Co(Oac)2·4H2O, which may be flowed into a thermal reactor at a ratio of approximately 59.60 wt % corresponding to 40.40 wt % carbon (referring to carbon in the form of CNO), resulting in the active sites on the CNO oxide being functionalized with cobalt, correspondingly showing cobalt-decorated CNO at a level of 15,000x. In some implementations, a suitable gas mixture for producing carbon #29 and / or cobalt-decorated CNO may include the following steps:

[0237] 0.75 standard cubic feet per minute (scfm) of Ar purge for 30 minutes;

[0238] Changed to 0.25 scfm Ar purge for operation;

[0239] ● Temperature increase: 25°C to 300°C for 20 min; and

[0240] ●Temperature increase: 300°–500°C for 15 min.

[0241] refer to Fig. 9A and Fig. 9B The carbonaceous material described may include or otherwise be formed from one or more examples of graphene, which may include a monolayer of carbon atoms, wherein each atom is bonded to three adjacent atoms in a honeycomb structure. The monolayer may be a loose material limited to one dimension, such as within a condensed phase or at a surface. For example, graphene may only grow outward in the x and y planes (and not in the z plane). In this way, graphene may be a two-dimensional (2D) material, including one or more layers, wherein the atoms in each layer are strongly bonded to (such as by multiple carbon-carbon bonds) adjacent atoms in the same layer.

[0242] In some implementations, the graphene nanosheets (e.g., the constituent structures included in each carbonaceous structure 956) may include multiple instances of graphene, such as a first graphene layer, a second graphene layer, and a third graphene layer, all stacked on top of each other in a vertical direction. Each of the graphene nanosheets, which may be referred to as GNPs, may have a thickness between 1 nm and 3 nm, and may have a lateral dimension in the range of approximately 100 nm to 100 μm. In some implementations, the graphene nanosheets may be produced by roll-to-roll (R2R) production using multiple plasma spray guns arranged in sequence. In some aspects, R2R production may include deposition on a continuous substrate processed into a rolled sheet, including transferring 2D material to a separate substrate. In some cases, R2R production may be used to form Figure 3 The first film 310 and / or the second film 320 of the electrode 300 may be formed by spraying the first aggregate 312 in the first film 310 at a concentration level different from the concentration level of the second aggregate 322 in the second film 320. That is, the plasma spraying gun used in the R2R process may spray carbonaceous materials at different concentration levels to produce the first film 310 and / or the second film 320 with graphene nanosheets at a specific concentration level. Therefore, the R2R process may be Figure 1 The battery 100 and / or Figure 2 The cell 200 provides a fine level of tunability.

[0243] Fig. 10A and Fig. 10B Shown are corresponding transmission electron microscope (TEM) images 1000 and 1050 of carbonaceous particulates treated with carbon dioxide (CO 2 ) according to some implementations. Fig. 10A and Fig. 10B The carbonaceous particles shown in may include or otherwise be formed from one or more instances of graphene, which may include a monolayer of carbon atoms in which each atom is bonded to three neighboring atoms in a honeycomb structure.

[0244] Fig.11 A graph 1100 is shown depicting carbon porosity types of various carbonaceous aggregates according to some implementations. In various implementations, reference Fig.11 The carbonaceous aggregates described may be Fig. 9A Aggregate 904 and / or Fig. 9B Examples of carbonaceous structures 956. In some aspects, reference Fig.11 The carbonaceous aggregates described can be used to form Figure 3 As discussed, the aggregate may be formed from or may include a group of carbonaceous structures, such as Fig. 9A Carbon structure 902 or Fig. 9B A carbonaceous structure 956. In some aspects, the carbonaceous structure can be CNO.

[0245] The carbonaceous structure can be used to form an electrode having any of the porosity types shown in Figure 1100 (such as Figure 3 Electrode 300). For example, the electrode may include any of porosity type 1 1110, porosity type II 1120, and porosity type III 1130. In some implementations, porosity type 1 110 may include first pores 1111, second pores 1112, and third pores 1113, all of which are sized with a major dimension less than 5 nm to retain polysulfides within the electrode. Some polysulfides may grow in size after forming larger complexes and become immobilely retained within the pores of porosity type I 1110. In some implementations, aggregates may be joined together to create pores of porosity type II 1120 and / or porosity type III 1130, which may retain larger polysulfides and / or polysulfide complexes.

[0246] Fig.12 A graph 1200 depicting the pore size versus porosity distribution of an exemplary electrode according to some implementations is shown. As used herein, "Carbon 1" refers to a structured carbonaceous material that includes primarily micropores (such as less than 5 nm in a major dimension), and "Carbon 2" refers to a structured carbonaceous material that includes primarily mesopores (such as between about 20 nm and 50 nm in a major dimension). In some implementations, an electrode suitable for use in one of the batteries disclosed herein can be prepared to have the pore size versus porosity distribution depicted in graph 1200.

[0247] Fig.13 A first graph 1300 and a second graph 1310 are shown depicting battery performance according to cycle number according to some implementations. Specifically, the first graph 1300 shows the specific discharge capacity of an exemplary battery using the electrolyte 1302 disclosed herein relative to the specific discharge capacity of a conventional battery using a conventional electrolyte. The second graph shows the capacity retention capability of a battery using the electrolyte 1302 relative to the capacity retention capability of a battery using a conventional electrolyte. In some aspects, the electrolyte 1302 can be Figure 1 Electrolyte 130 or Figure 2 An example of an electrolyte 230. In the first graph 1300 and the second graph 1310, a conventional electrolyte was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=1:1:1) with 2 wt% LiNO3.

[0248] Fig.14A bar graph 1400 is shown showing battery performance as a function of cycle number according to some implementations. Specifically, bar graph 1400 depicts the specific discharge capacity as a function of cycle number of an exemplary battery using an electrolyte 1402 disclosed herein relative to the specific discharge capacity as a function of cycle number of a conventional battery using a conventional electrolyte. In some aspects, electrolyte 1402 may be Figure 1 Electrolyte 130 or Figure 2 1400, the conventional electrolyte is prepared as 1M LiTFSI in DME:DOL:TEGDME (volume:volume:volume = 1:1:1). Bar graph 1400 shows that compared with a battery using a conventional electrolyte, in an exemplary battery (such as Figure 1 Battery 100 or Figure 2 Using electrolyte 1402 in battery 200) can increase the specific discharge capacity of the battery by about 28% at the 3rd cycle, by about 30% at the 50th cycle, and by about 39% at the 60th cycle.

[0249] Fig.15 A first graph 1500 and a second graph 1510 are shown depicting battery performance according to some implementations as a function of cycle number. Specifically, the first graph 1500 shows the electrode discharge capacity as a function of cycle number of an exemplary lithium-sulfur button cell using the electrolyte 1502 disclosed herein relative to the electrode discharge capacity as a function of cycle number of an exemplary lithium-sulfur button cell using a conventional electrolyte, and the second graph 1510 shows the capacity retention capability as a function of cycle number of a lithium-sulfur button cell using the electrolyte 1502 relative to the electrode discharge capacity as a function of cycle number of a lithium-sulfur button cell using the conventional electrolyte. In some aspects, the electrolyte 1502 may be Figure 1 Electrolyte 130 or Figure 2 An example of an electrolyte 230 of the invention. A lithium sulfur button cell was cycled at a discharge rate of 1C (such as fully discharged in one hour), at 100% depth of discharge (DOD) and maintained at about room temperature (68°F or 20°C). A conventional electrolyte was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=1:1:1) with 2 wt% LiNO3.

[0250] Fig.16 A graph 1600 depicting electrode discharge capacity as a function of cycle number according to some implementations is shown. Specifically, graph 1600 depicts electrode discharge capacity as a function of cycle number for an exemplary battery using an electrolyte 1602 disclosed herein relative to electrode discharge capacity for a conventional battery using a conventional electrolyte. In some aspects, electrolyte 1602 may be Figure 1 Electrolyte 130 or Figure 2An example of an electrolyte 230. The conventional electrolyte was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=1:1:1) with 2 wt% LiNO3, and the electrolyte 1602 was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=58:29:13) with 2 wt% LiNO3.

[0251] Fig.17 Another graph 1700 depicting the electrode discharge capacity according to some implementations is shown. Specifically, graph 1700 depicts the electrode discharge capacity according to the number of cycles for an exemplary battery using an electrolyte 1702 and a solvent package 1704 disclosed herein relative to the electrode discharge capacity of a conventional battery using a conventional electrolyte and solvent package. The conventional electrolyte was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=1:1:1) with about 2 wt% LiNO3, and the electrolyte 1702 was prepared as 1M LiTFSI in DME:DOL:TEGDME (vol:vol:vol=58:29:13) with 2 wt% LiNO3. Conventional solvent package was prepared as 1 M LiTFSI in DME:DOL:TEGDME (v:v:v = 1:1:1), and solvent package 1704 was prepared as 1 M LiTFSI in DME:DOL:TEGDME (v:v:v = 58:29:13).

[0252] Fig.18 A graph 1800 is shown depicting the specific discharge capacity according to the number of cycles for various TBT-containing electrolyte mixtures according to some implementations. As shown in the graph 1800, "181" indicates an electrolyte without any TBT addition, resulting in a 0MTBT concentration level, "181-25TBT" indicates an electrolyte prepared at a 25M TBT concentration level, and so on. In some implementations, a 5MTBT concentration level can result in an approximate 70 mAh / g discharge capacity increase relative to an electrolyte without any TBT addition.

[0253] Fig.19A first graph 1900 depicting electrode discharge capacity as a function of cycle number and a second graph 1910 depicting electrode capacity retention as a function of cycle number are shown according to some implementations. Specifically, the first graph 1900 depicts the electrode discharge capacity as a function of cycle number for an exemplary battery including the protective lattice disclosed herein relative to the electrode discharge capacity of an exemplary battery not including the protective lattice disclosed herein. The second graph 1910 depicts the electrode capacity retention as a function of cycle number for an exemplary battery including the protective lattice disclosed herein relative to the electrode capacity retention of an exemplary battery not including the protective lattice disclosed herein. In some aspects, the protective lattice may be Figure 4 4. The performance results of the first and second graphs 1900 and 1910 include the use of an electrolyte prepared with 1M LiTFSI in DME:DOL:TEGDME (v:v:v = 58:29:13) having 2 wt% LiNO3.

[0254] Fig. 20 A first graph 2000 depicting the discharge capacity of an electrode according to the number of cycles and a second graph 2010 depicting the capacity retention of an electrode according to the number of cycles are shown according to other implementations. Specifically, the first graph 2000 depicts a graph including Figure 7 The second graph 2010 depicts the electrode discharge capacity according to the number of cycles of an exemplary battery having a polymer network of Figure 7 The discharge capacity retention capability of an exemplary battery of a polymer network according to the number of cycles. The battery may be Figure 1 Battery 100 or Figure 2 2000 and the second graph 2010 include performance results using an electrolyte prepared to have 2 wt % LiNO 3 in DME:DOL:TEGDME (v:v:v = 58:29:13).

[0255] Fig.21 A first graph 2100 depicting the discharge capacity of an electrode according to the number of cycles and a second graph 2110 depicting the capacity retention of an electrode according to the number of cycles are shown according to some other implementations. Specifically, the first graph 2100 depicts a graph including Figure 5 The second graph 2110 depicts the electrode discharge capacity according to the number of cycles for an exemplary battery having a protective layer 516 of Figure 5 The discharge capacity retention capability of an exemplary battery according to the number of cycles of the protective layer 516 of Figure 1 Battery 100 or Figure 219. The performance results of the first graph 1900 and the second graph 1910 include using an electrolyte prepared to have 2 wt% LiNO3 in DME:DOL:TEGDME (v:v:v = 58:29:13).

[0256] Fig. 22 An exemplary cathode 2200 is shown having a body 2201 and a width 2205 according to some implementations. In some implementations, the cathode 2200 can be Figure 3 The cathode 2200 may be similar in many respects to the Figure 3 The cathode 2200 includes a first porous carbonaceous region 2210 and a second porous carbonaceous region 2220 positioned adjacent to the first porous carbonaceous region 2210. The first porous carbonaceous region 2210 may be formed of a carbonaceous material at a first concentration level, and the second porous carbonaceous region 2220 may be formed of a carbonaceous material at a second concentration level different from the carbonaceous material at the first concentration level. For example, the second porous carbonaceous region 2220 may have a lower concentration level of carbonaceous material than the first porous carbonaceous region 2210, such as Fig. 22 In some aspects, the additional porous carbonaceous region (for simplicity, Fig. 22 ) may be coupled to at least a second porous carbonaceous region.

[0257] Specifically, these additional porous carbonaceous regions can be arranged in a direction away from the first porous carbonaceous region 2210 in an order of gradually decreasing concentration levels of carbonaceous materials to provide complete ion transport and current tunability. That is, in one implementation, the second porous carbonaceous region 2220 can face the bulk electrolyte (e.g., provided in a liquid phase), and the first porous carbonaceous region 2210 of the cathode 2200 can be aligned with the current collector (for simplicity, Fig. 22 In this way, a denser carbonaceous region (such as the first porous carbonaceous region 2210) can facilitate a higher level of electrical conductance (between adjacent contact points of the carbonaceous material) relative to conventional lithium-ion batteries. Fig. 22 Indicated as "e - ”), while a sparser carbonaceous region (such as the second porous carbonaceous region 2220) can facilitate a higher level of lithium ion transport associated with increased lithium-sulfur battery discharge-charge cycles. In some implementations, an additional carbonaceous region coupled to and positioned adjacent to the second porous carbonaceous region 2220 can have a lower density of carbonaceous material than the second porous carbonaceous region 2220. In this way, the lower density additional carbonaceous region can accommodate a higher level of lithium ion transport to, for example, allow tuning of various performance characteristics of the electrode 300.

[0258] In one implementation, the first porous carbonaceous region 2210 may include first non-three-segment particles 2211. The configuration of the first non-three-segment particles 2211 within the first porous carbonaceous region is an exemplary configuration. Other arrangements, orientations, alignments, etc. are possible for the non-three-segment particles. In some aspects, each non-three-segment particle may be an example of one or more carbonaceous materials disclosed elsewhere in the present disclosure. The first porous carbonaceous region 2210 may also include, for example, Fig. 22 The first three-segment particles 2212 may be dispersed throughout the first non-three-segment particles 2211 or positioned in any other arrangement, orientation or configuration as shown in FIG. Each first three-segment particle 2212 may be Figure 8B In addition or alternatively, each first three-segment particle 2212 may include first carbon segments 2213 interwoven with each other and separated from each other by mesopores 2214. Each three-segment particle may have a first deformable perimeter 2215 configured to coalesce with an adjacent first non-three-segment particle 2211 and / or a first three-segment particle 2212.

[0259] The first porous carbonaceous region 2210 may also include first aggregates 2216, each of which includes many first three-segment particles 2212 joined together. In one or more specific examples, each first aggregate may have a major dimension in the range between 10 nanometers (nm) and 10 micrometers (μm). Mesopores 2214 may be dispersed throughout the first plurality of aggregates, each of which has a major dimension between 3.3 nanometers (nm) and 19.3nm. In addition, the first porous carbonaceous region 2210 may include first agglomerates 2217, each of which includes many first aggregates 2216 joined to each other. In some aspects, each first agglomerate 2217 may have a major dimension in the approximate range between 0.1μm and 1,000μm. Macropores 2218 may be dispersed throughout the first aggregates 2216, each of which may have a major dimension between 0.1μm and 1,000μm. In some implementations, one or more of the carbonaceous materials, allotropes, and / or structures discussed above may be Fig. 9A and Fig. 9B One or more examples shown in .

[0260] The second porous carbonaceous region 2220 may include second non-three-segment particles 2221, which may be an example of the first non-three-segment particles 2211. The second porous carbonaceous region 2220 may include second three-segment particles 2222, each of which may be an example of each of the first three-segment particles 2212 and / or may be Figure 8BIn addition or alternatively, each second three-segment particle 2222 may include second carbon segments 2223 interwoven with each other and separated from each other by the middle pores 2214. Each second three-segment particle 2222 may have a second deformable periphery 2225 configured to coalesce with one or more adjacent second non-three-segment particles 2221 or second three-segment particles 2222.

[0261] In addition, the second porous carbonaceous region 2220 may include second aggregates 2226, each of which may include many second three-segment particles 2222 joined together. In one or more specific examples, each second aggregate 2226 may have a major dimension in the range between 10 nanometers (nm) and 10 micrometers (μm). Mesopores 2214 may be dispersed throughout the second aggregates 2226, each of which may have a major dimension between 3.3 nanometers (nm) and 19.3nm. In addition, the second porous carbonaceous region 2220 may include second agglomerates 2227, each of which may include many second aggregates 2226 joined to each other, each of which may have a major dimension in the approximate range between 0.1μm and 1,000μm. Macropores 2218 may be dispersed throughout the second plurality of aggregates, each of which has a major dimension between 0.1μm and 1,000μm. In some implementations, one or more of the carbonaceous materials, allotropes, and / or structures discussed above may be Fig. 9A and Fig. 9B One or more examples shown in .

[0262] In one implementation, the first porous carbonaceous region 2210 and / or the second porous carbonaceous region 2220 may include a selectively permeable shell (for simplicity, Fig. 22 ), which may form a separated liquid phase on the first porous carbonaceous region 2210 or the second porous carbonaceous region 2220, respectively. An electrolyte (such as any electrolyte disclosed in the present disclosure) may be dispersed in the first porous carbonaceous region and / or the second porous carbonaceous region for lithium ion transport associated with the discharge-charge operation cycle of the lithium-sulfur battery.

[0263] In one or more specific examples, the first porous carbonaceous region 2210 may have an electrical conductivity in an approximate range of 500 S / m to 20,000 S / m at a pressure of 12,000 pounds per square inch (psi). The second porous carbonaceous region 2220 may have an electrical conductivity in an approximate range of 0 S / m to 500 S / m at a pressure of 12,000 pounds per square inch (psi). The first agglomerates 2217 and / or the second agglomerates 2227 may include aggregates connected to each other by one or more polymer-based binders.

[0264] In some aspects, each first three-segment particle 2212 can have a first porosity region positioned around the center of the first three-segment particle 2212 (for simplicity, Fig. 22 Similarly, each second three-segment particle 2222 may have a first porosity region positioned around the center of the second three-segment particle 2222 (for simplicity, Fig. 22 The first porosity region may include first pores. The second porosity region (for simplicity, Fig. 22 The first porosity region may include a second porosity region. In one implementation, the first porosity region may define a first porosity density, and the second porosity region may define a second porosity density different from the first porosity density.

[0265] In some aspects, the mesopores 2214 can be grouped into first mesopores and second mesopores (for simplicity, both are in Fig. 22 In one or more specific examples, the first mesopores may have a first mesopore density, and the second mesopores may have a second mesopore density different from the first mesopore density. In addition, the macropores 2218 may be grouped into first macropores that may have a first pore density and second macropores that may have a second pore density different from the first pore density (for simplicity, both are shown in FIG. Fig. 22 are not shown).

[0266] In one implementation, the first porous carbonaceous region 2210 and / or the second porous carbonaceous region 2220 can nucleate sulfur, such as is required to facilitate the operational discharge-charge cycle of any of the lithium-sulfur batteries disclosed herein. For example, the cathode 2200 can have a sulfur to carbon weight ratio of between about 1:5 and 10:1. In some aspects, one or more conductive additives can be dispersed within the first porous carbonaceous region 2210 and / or the second porous carbonaceous region 2220, for example, to correspondingly affect the discharge-charge cycle performance of the cathode 2200. Additionally, a protective sheath (such as Figure 4 A protective lattice 402) may be provided on the cathode.

[0267] In one implementation, Fig. 22 The exemplary cathode 2200 and / or any battery configuration presented in the present disclosure (such as battery 100 and / or 200) can be prepared with an electrolyte (such as electrolyte 130 and / or 230) dispersed throughout the corresponding battery configuration. Additionally or alternatively, electrolyte 130, electrolyte 230, etc. can be formulated according to the following numbered examples:

[0268]

[0269]

[0270]

[0271]

[0272] In some aspects, such as when prepared according to any one or more of the examples presented above, the lithium cations (Li + ) The ionic conductivity of electrolyte 125 may depend on the molecular structure of the various component materials of electrolyte 130. For example, a material that is hydrophobic and less polar may have a lower ionic conductivity value. A material that is hydrophilic and more polar may have a higher ionic conductivity value. In this way, the component materials in the above electrolyte formulation examples for electrolyte 130 may be ranked from the lowest ionic conductivity to the highest ionic conductivity according to the following order: DMTS, TOL, TFETFE, MPB, MTBE, TrigDME, THF, TEE, TMU, DMSO, DMF, ACN.

[0273] In the electrolyte components disclosed in Examples 1-20 above, lithium nitrate (LiNO3) can be dissociated into lithium cations (Li + )(Li + ) and nitrate anions (NO3 - In this way, lithium nitrate (LiNO3) can generate nitrogen-oxygen compounds (not shown in the figure for simplicity), which can be derived from and / or based on nitrate anions (NO3 - ). When prepared according to any one or more of the examples presented above, the electrolyte 130 can prevent the diffusion of nitrogen-oxygen compounds generated during the operational discharge-charge cycle of the battery 100. In addition, some nitrate anions (NO3 - ) can form a solvation sheath on the anode 120 (not shown in the figure for simplicity). In this way, the electrolyte 130 can be prepared to allow the nitrogen-oxygen additive to at least partially coat the anode 120 and thereby prevent dendrites from the anode 120 from extending through the electrolyte 130 to the cathode 110. The solvation sheath can be formed between the LiTFSI and the lithium cation (Li + )125 form a coordination complex. The coordination complex may include a central atom or ion (such as a lithium cation (Li + )125) and a surrounding array of bound molecules or ions which may be referred to as ligands or complexing agents.

[0274] The prevention of dendrite formation provided by the solvation sheath may be at least partially compromised by the continued reduction of nitrogen compounds predominantly in nitrogen-oxygen additives, which form, for example, nitrites (NO2 -), which can generate gas that causes bubble pockets in the electrolyte 130. These bubbles can interfere with the lithium cation (Li + )125, which can cause expansion of the battery 100 and can also cause undesirable obstruction of lithium ion transport. To address these limitations, the example 18 of the electrolyte formulation presented above can be prepared without adding lithium nitrate (LiNO3) and / or other types of nitrogen-oxygen additives.

[0275] Fig.23 -25 shows a graph depicting specific discharge capacity by cycle number for one or more of the previously presented Examples 1-20, according to some implementations. Fig.23 Show description Figure 1 A graph 2300 of specific discharge capacity (mAh / g) as a function of cycle number for the performance improvements of the battery 100 of Example A and / or other battery configurations disclosed herein. With respect to graph 2300, "Control" refers to the electrolyte 130 prepared according to Example 1, "Toluene" refers to the electrolyte 130 prepared according to Example 3, and "TMU" refers to the electrolyte 130 prepared according to Example 5. In some aspects, the toluene in the electrolyte 130 prepared according to Example 3 is based on its non-polar nature and correspondingly with, for example, Figure 1 The poor interaction of toluene with the polysulfide 128 of B may provide a beneficial unintended result. That is, toluene has a unique chemical structure that, when prepared according to Example 3, may hinder the easy transport of the polysulfide 128 through the electrolyte 130. The benefits associated with using different concentrations or dilution levels of toluene in, for example, a liquid solvent mixture (also known as a ternary solvent package) may increase significantly in proportion to the cycling rate. That is, relative to a conventional discharge rate of 1C (corresponding to a full battery discharge in a 1 hour period), when looking at a lithium-sulfur battery discharged at a C / 3 rate (corresponding to a full battery discharge in a 3 hour period), the use of toluene may be even more beneficial in terms of cathode capacity retention capability than shown in graph 2300. In this way, toluene may be particularly well suited for end-use applications that may involve longer battery life or discharge times, such as electric vehicles (EVs).

[0276] Based on its chemical structure and non-polar nature, toluene, with an approximate ionic conductivity value (mS / cm) of 5.128026, may be uniquely suited to outperform other solvents. In this way, such as when prepared according to Example 3, toluene in the electrolyte 130 may be used to enhance the performance of the electrolyte 130 during battery cycling by hindering the movement of polysulfides 128 within the electrolyte 130, thereby releasing lithium cations (Li +) 125 in the electrolyte 130 and facilitates higher specific capacity and increased capacity retention. Additionally or alternatively, toluene can act as a favorable solvent for elemental sulfur 126 when pre-loaded (such as by capillary infusion or some other suitable technique) into the cathode 110 or cathode 2200. In one implementation, toluene can help depassivate the cathode 110 or cathode 2200 to pre-condition the cell 100 to prevent a drop below the minimum design voltage (of the cell 100) once the external load 172 is applied.

[0277] By hindering the movement of polysulfide 128 in electrolyte 130, toluene can improve sulfur retention and overall sulfur-related dynamics within cathode 110, that is, in the presence of lithium cations (Li + ) 125 to form a coordination complex. Toluene can also improve the interface area between the anode 120 and the electrolyte 130 by preventing the polysulfide 128 from migrating to contact the anode 120. In addition, toluene can increase the boiling point of the electrolyte 130 and / or reduce its volatility, which can improve the safety and reliability of the electrolyte 130. In addition, toluene can reduce the freezing point of the electrolyte 130, which can contribute to the low temperature performance of the battery 100. Toluene can also reduce the density of the electrolyte 130, which can improve the specific energy, because the quality of the electrolyte 130 can affect the performance and / or efficiency of the battery 100.

[0278] In some implementations, the ability of toluene to improve the performance of the electrolyte 130 may depend at least in part on the ability of toluene to dissolve certain forms of elemental sulfur, such as cyclooctasulfur (S8). In some aspects, at a solubility level of S8 of about 0.0275 (mol / L), toluene may have a normalized first cycle discharge capacity (Ah / g) between about 0.6 (Ah / g) and 0.8 (Ah / g). These values ​​provide a significant improvement when compared to, for example, ACN, which has a normalized first cycle discharge capacity (Ah / g) between about 0.37 (Ah / g) and 0.41 (Ah / g) at a solubility level of S8 of about 0.0075 (mol / L), indicating that toluene tends to better solvate S8 and provide a corresponding improvement in discharge capacity.

[0279] Fig.24 Show description Figure 1 A graph 2400 of specific discharge capacity (mAh / g) as a function of cycle number for the performance improvements of the battery 100 of Example A and / or other battery configurations disclosed herein. With respect to graph 2400, "MPB" refers to the electrolyte 130 prepared according to Example 7, "TrigDME" refers to the electrolyte 130 prepared according to Example 9, and "TEE" refers to the electrolyte 130 prepared according to Example 8.

[0280] Fig.25Show description Figure 1 A graph 2500 of specific discharge capacity (mAh / g) according to cycle number for performance improvements of battery 100 and / or other battery configurations of Example A. With respect to graph 2500, "TFETFE" refers to an electrolyte 130 prepared according to Example 13, "DMTS" refers to an electrolyte 130 prepared according to Example 11, "MTBE" refers to an electrolyte 130 prepared according to Example 10, and "ACN" refers to an electrolyte 130 prepared according to Example 12.

[0281] In some aspects, the cathode (such as Fig. 22 The cathode 2200) can be connected to the anode (such as Figure 1 The cathode 2200 may be positioned relative to the anode 120 and have an overall porosity between 40% and 70%. In one example, the cathode 2200 may include non-hollow carbon spherical (NHCS) particles bonded together. Each NHCS particle may be Fig. 22 The first three sections of particles 2212, Fig. 22 The second and third segment particles 2222, Fig. 8A At least some of the NHCS particles may agglomerate together and thereby collectively form a tubular NHCS particle agglomerate, which may be Fig. 9B Each NCHS particle may have a diameter between 30 nanometers (nm) and 60 nm and may include a first region and a second region. In one implementation, the first region may be Fig. 8A The first pore 801 is defined by the second region. Fig. 8A The first region may be adjacent to the center of the corresponding NHCS particle and may have a first density of carbonaceous material, and the second region may be adjacent to the surface of the corresponding NHCS particle. The second region may encapsulate the first region and have a second density of carbonaceous material that is lower than the first density of carbonaceous material. The first region and the second region may be in fluid communication with each other.

[0282] Additionally, cathode 2200 may include interconnected channels defined in shape by adjacent NHCS particles (for simplicity, Fig. 22 Some of the interconnecting channels may be preloaded with elemental sulfur and hold polysulfides (PS) based on one or more of the carbonaceous material of the first density or the carbonaceous material of the second density. An electrolyte that may be prepared by any of the formulations presented in Examples 1-20 may be dispersed throughout the cathode and in contact with the anode. A separator may be positioned between the anode and the cathode.

[0283] Fig.26AAn exemplary battery 2600A according to some other implementations is shown. Battery 2600A may be an example of other battery configurations disclosed herein. In one implementation, battery 2600A may be implemented as a lithium-sulfur battery and may include an anode 2620 (e.g., an anode active material comprising lithium foil), a cathode 2610, and a solid electrolyte 2630. In some cases, solid electrolyte 2630 may replace one or more electrolyte solution compositions presented in Examples 1-20. Cathode 2610 may be an example of other cathode configurations disclosed herein, such as Figure 1 The cathode 110, Figure 2 The cathode 210 and / or Fig. 22 In some aspects, the cathode may be loaded with 3 mg / cm3. 3 ) of elemental sulfur. In other aspects, cathode 2610 can be loaded with 3 milligrams (mg) / cubic centimeter (cm3) of sulfur suitable for maximizing the discharge-charge cycle efficiency of battery 2600A. 3 ) other concentrations of elemental sulfur. In some aspects, cathode 2610 can be porous and comprised of a subject composition including a plurality of pores 2612 (for simplicity, Fig.26A The subject composition may be an example of various carbonaceous materials and / or structures disclosed herein, such as Fig. 22 The first three sections of particles 2212, Fig. 22 The second and third segment particles 2222, Fig. 8A Carbonaceous particles 800, Fig. 9B One or more examples of aggregate 960, etc.

[0284] Solid electrolyte 2630 can be dispersed throughout at least pores 2612 of cathode 2610 and can also be in contact with anode 2620. In some aspects, solid electrolyte 2630 can be formed as a membrane, thereby providing a barrier to a separator (e.g., Figure 1 In one implementation, the solid electrolyte 2630 may be formed of and / or include a polymer matrix 2631, which may be formed of interconnected glass fibers 2633. In some aspects, the polymer matrix 2631 may have ionic conductivity (e.g., conduct lithium cations (Li + )) and may include between 8 weight percent (wt.%) and 12 weight percent of polyethylene oxide (PEO) 2632, between 13 weight percent and 17 weight percent of polyvinylidene fluoride (PVDF) 2634, between 3 weight percent and 7 weight percent of repeating oxypropylene units in its backbone (for simplicity, Fig.26A ) and between 5 wt % and 10 wt % of one or more lithium-containing salts (for simplicity, Fig.26AIn some embodiments, at least some of the lithium-containing salts may be dissociated into lithium cations (Li + ) and thereby facilitate lithium ion transport between the anode 2620 and the cathode 2610 during the operational discharge-charge cycle of the battery 2600A.

[0285] Similar to various other lithium-sulfur battery configurations disclosed herein, during the operational discharge-charge cycle of the battery 2600A, the battery 2600A may generate undesirable lithium-containing polysulfide species (for simplicity, Fig.26A 2600A). In some cases, cathode 2610 can at least partially entrap and / or retain lithium-containing polysulfide species, thereby preventing blockage of lithium transport channels (e.g., as shown as charging cycle flow 2625) within solid electrolyte 2630. In some aspects, anode 2620 can be formed to provide lithium cations (Li + ) of the lithium layer. In this way, during the discharge-charge cycle of operation of the battery 2600A, the lithium layer can provide lithium cations (Li + ). In other aspects, during the operating charge cycle of the battery 2600A, the cavity 2622 can receive lithium deposits from the cathode 2610. That is, the lithium cations (Li + ) can travel along the charge cycle flow 2624 from the cathode 2610 to the cavity 2622, which can be associated with the return of the electrons 2674 to the battery 2600A, which can be related to or associated with conditions encountered in the battery charge and / or recharge cycle. In this way, the cavity 2622 can be transformed into the anode 2620, which can again be capable of converting lithium cations (Li + ) are provided to their corresponding electrochemically favorable positions in the cathode 2610.

[0286] In one implementation, the subject composition for forming cathode 2610 may be formed from and / or include one or more non-three-segment particles, three-segment particles, aggregates, or agglomerates as disclosed herein. In some aspects, cathode 2610 may be Fig. 22An example of a cathode 2200 of . That is, each three-segment particle used in cathode 2610 may include carbon fragments intertwined with each other. At least some of the carbon fragments may be separated from each other by mesopores. The deformable periphery may be defined after the agglomeration of one or more adjacent non-three-segment particles or three-segment particles. Each aggregate may include many three-segment particles joined together and have a major dimension in the range between 10 nanometers (nm) and 10 micrometers (μm). Mesopores may be dispersed throughout the aggregate. Each mesopore may have a major dimension between 3.3 nanometers (nm) and 19.3nm. Each agglomerate may be formed by many aggregates joined to each other and have a major dimension in the approximate range between 0.1μm and 1,000μm. Macropores may be dispersed throughout the aggregate, wherein each macropore has a major dimension between 0.1μm and 1,000μm.

[0287] In some implementations, when formed and / or deposited as a film on the anode 2620 (for simplicity, Fig.26A When the ionic conductivity of the solid electrolyte 2630 is 0.97×10 -3 Siemens per foot (S / m) is 1.03×10 -3 In other implementations, the membrane may be coated on the anode 2620 such that the ionic conductivity of the membrane at a temperature between 18 degrees Celsius (° C.) and 22° C. is between 3.97×10 -6 Siemens per foot (S / m) is 4.03×10 -6 In some aspects, higher amounts of one or more lithium-containing salts can be associated with increased ionic conductivity of the polymer matrix 2631 .

[0288] In one implementation, the solid electrolyte 2630, when formed into a film, has a thickness between 10 micrometers (μm) and 50 μm, and may have a uniform density throughout its thickness. For example, in some cases, the solid electrolyte 2630 may have a density of 2 grams per cubic centimeter (g / cm 3 ) and 3g / cm 3 In some aspects, the membrane can be coated onto a sacrificial polymer (for simplicity, Fig.26A 26), the polymer may be disposed on the anode 2620 facing the solid electrolyte 2630. In this way, the solid electrolyte 2630 may prevent electrons from traveling from the anode 2620 to the cathode 2610 through the solid electrolyte 2630. In addition, the contact point between the solid electrolyte 2630 and the anode 2620 may prevent the impedance of the battery 2600A from increasing.

[0289] In one implementation, cathode 2610 has a thickness between 50 micrometers (μm) and 150 μm, and a density of 5 grams per cubic centimeter (g / cm 3 ) and 15g / cm 3 In some aspects, the solid electrolyte 2360 may be prepared without a liquid electrolyte, such as Examples 1-20 disclosed herein. Additionally or alternatively, the solid electrolyte 2630 may locate lithium-containing polysulfide species within the cathode 2610 and / or prevent the growth of lithium-containing dendrite structures from the anode 2620. In some aspects, during the operating discharge-charge cycle of the battery 2600A, the anode 2620 may expand in volume by between 5% and 20% of its initial size. In some cases, during the operating discharge-charge cycle of the battery 2600A, the solid electrolyte 2630 may provide interfacial stability between the anode 2620 and the solid electrolyte 2630, for example to reduce or limit the volume expansion of the anode 2620.

[0290] Fig.26B Another exemplary battery 2600B is shown according to some other implementations. In one implementation, battery 2600B can be another example of battery 2600A. In some aspects, cavity 2622 can replace anode 2620 and can be gradually filled with lithium provided from cathode 2610 during the operational discharge-charge cycle of battery 2600B. In this way, once Fig.26B The cavity 2622 is filled with lithium to become Fig.26A With anode 2620, battery 2600B can function in a manner similar or identical to battery 2600A.

[0291] Fig. 27 A depiction according to some implementations is shown Fig.26A Graph 2700 of voltage drop according to specific capacity for an exemplary configuration of battery 2600A. With respect to graph 2700, battery 2600A is charged at 3 mg / cm3. 3 ) sulfur loading level and in button cell form. In addition, battery 2600A was prepared with solid electrolyte 2630 at a thickness level of 18 micrometers (μm). Region 2702 may represent a unique voltage drop behavior associated with the formation and / or dissociation of lithium-containing polysulfide intermediates generated during the discharge-charge operation cycle of battery 2600A.

[0292] Fig.28Another exemplary battery 2800 is shown according to some other implementations. Battery 2800 may be an example of other battery configurations disclosed herein. In one implementation, battery 2800 may be implemented as a lithium-sulfur battery and may include a cathode 2810, an anode structure 2822 including an anode 2820 (e.g., an anode active material including lithium foil) positioned opposite the cathode, a separator 2850 positioned between the anode 2820 and the cathode 2810, and an electrolyte 2830. In some aspects, the electrolyte 2830 may be prepared by mixing at least two or more solvents, such as the solvents disclosed in Examples 1-20 presented previously. The electrolyte 2830 may be dispersed throughout the cathode 2810 and in contact with the anode 2820. In some aspects, the anode 2820 may be a single solid metallic lithium foil. In this way, at least some of the lithium cations (Li ions) output by the anode 2820 are + ) 2825 can participate in dissociation reactions and / or combination reactions during the operating discharge-charge cycle of the battery 2800. That is, during the discharge cycle of the battery 2800, the lithium cations (Li + ) 2825 can be transported by the electrolyte 2830 and maintained in its electrochemically favorable position within the cathode 2810 (for simplicity, Fig.28 Then, during a charge cycle of the battery 2800, upon exposure to an external current source, the lithium cations (Li + )2825 returns to the anode 2820.

[0293] In addition, the solid electrolyte interface phase 2840 can be formed on the anode 2820. In this way, the protective layer 2860 can be at least partially formed within and / or on the solid electrolyte interface phase 2840 and facing the cathode 2810. In some aspects, based on the lithium cation (Li + ) and one or more redox reactions of one or more solvents of the electrolyte 2830, the solid electrolyte interface phase 2840 may form one or more compounds on the anode 2820. In some implementations, the protective layer 2860 may be at least partially formed of a carbonaceous material including one or more of flat graphene, wrinkled graphene, carbon nanotubes (CNTs), carbon nano onions (CNOs), or non-hollow carbon spherical particles (NHCS), one or more of which may be Fig. 9B An example of a carbonaceous structure 956.

[0294] Fig.29 A diagram depicting an exemplary cathode 2900 according to some implementations is shown. Cathode 2900 can be an example of other cathode configurations disclosed herein, such as Fig. 22 The cathode 2200 and / or Fig.28In some implementations, cathode 2900 may include a porous structure 2915 having interconnected channels 2916 defined by adjacent and interconnected non-hollow carbon spherical particles (NHCS) particles 2917, each of which may be Figure 8B Three-segment particles 850, Fig. 9B An example of an aggregate 960 and / or other carbonaceous materials described in the present disclosure. In this way, in e.g. Fig.28 Prior to activation and discharge-charge cycles of the battery 2800, at least some of the interconnecting channels 2916 may be loaded with elemental sulfur 2926 in the cathode 2900. The elemental sulfur 2926 may react with at least some of the lithium cations (Li + ) 2825 to form a coordination complex to increase the specific capacity of cathode 2900, for example, compared to conventional lithium ion chemistry. In some aspects, cathode 2900 can have a width 2910 formed by a first region 2911 disposed on substrate 2902 (e.g., copper or other metal current collector), and can have multiple additional regions, such as a second region 2912 positioned adjacent to first region 2911. The first region 2911, the second region 2912, and / or additional subsequent regions positioned adjacent to the second region 2912 (for simplicity, Fig.29 Each of the regions (not shown) can be defined in shape, size, and orientation by a corresponding concentration level of NHCS particles 2917. That is, in some aspects, the first region 2911 can be prepared with a relatively high concentration of NHCS particles 2917, thereby resulting in increased conductance between adjacent graphene sheets within each NHCS particle, as may be desired near or at the substrate 2902. In contrast, the second region 2912 can be prepared with a relatively low concentration of NHCS particles 2917, thereby allowing lithium ions (Li + )2925 is additionally transported into the width 2910 of the cathode 2900 to complex with elemental sulfur 2926 contained within the interconnecting channels 2916.

[0295] Fig.30 FIG. 1 shows a diagram depicting an embodiment of an embodiment of the present invention according to some implementations. Fig.28 FIG3000 is a diagram of a region “A” of a protective layer 2860 of a battery of FIG3000. In some aspects, region “A” can be an example of various anode protective layers disclosed herein, including protective layer 2860. In one implementation, region “A” can be at least partially formed of a polymer material, such as a first polymer chain 3010 having carbon atoms 3014 provided by at least some carbonaceous material. Oxygen anions (O 2- )3022、Fluoride anion (F - )3012 and nitrate anion (NO 3-) 3024 can be uniformly dispersed throughout region "A" and grafted to one or more of the carbon atoms 3014. Region "A" can also include a second polymer chain 3020, which includes at least some carbon atoms 3014, which can also be provided by a carbonaceous material. Similar to the first polymer chain 3010, the carbon atoms 3014 of the second polymer chain 3020 can also be grafted to the oxygen anion (O 2- )3022、Fluoride anion (F - )3012 and nitrate anion (NO 3- ) 3024, one or more of which can be uniformly dispersed throughout the protective layer 2860. In some aspects, the second polymer chain 3020 can be positioned relative to the first polymer chain 3010. In addition, in one implementation, the first polymer chain 3010 and the second polymer chain 3020 can be configured based on exposure to one or more nitrogen-containing groups such as nitrate anions (NO 3- )3024 and cross-linked with each other.

[0296] In some aspects, inorganic and / or ionic conductors 3018, such as lithium-containing salts including lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), can be uniformly dispersed throughout electrolyte 2830 and / or protective layer 2860 and then dissociate into lithium cations (Li + )2825 and TFSI - anion 2826. Additionally, upon exposure to environment 3050, first polymer chain 3010 and second polymer chain 3020 can at least partially cross-link with each other and form carbon-carbon bonds 3026. In some cases, environment 3050 can include a polymerization initiator and / or ultraviolet (UV) radiation.

[0297] Specifically, exposing the first polymer chain 3010 and the second polymer chain 3020 to a polymerization initiator and / or UV radiation can cause the region "A" to form a three-dimensional (3D) lattice having a crosslink density defined by the number of crosslinks per unit volume. In some aspects, the crosslinks can be configured to at least partially entrap the TFSI generated after the dissociation of LiTFSI. -anion 2826. For example, the number of cross-linking points per unit volume can limit the redissolution of the lithium-containing additive in region "A" into the electrolyte 2830. In some aspects, the cross-linking density of the protective layer 2860 can inhibit swelling exceeding 10% of the initial volume of the protective layer 2860, for example, by preventing absorption of at least one of the solvents in the electrolyte 2830. In some other aspects, the cross-linking density of the protective layer 2860 can control swelling between 10%-50% of the initial volume of the protective layer 2860 by controlling the absorption of at least one solvent. In this way, the cross-linking density of the protective layer 2860 can improve the transport of lithium ions (Li+) in the entire anode structure 2822 and the electrolyte 2830 and / or can be associated with an improvement in the transport.

[0298] In one implementation, the protective layer 2860 may have an elastic modulus between 3 GPa and 100 GPa, a glass transition temperature above 60 degrees Celsius (° C.), and may be cured at a temperature below 81 degrees Celsius (° C.). After activating the battery 2800, the lithium fluoride (LiF) may be based on one or more chemical reactions (e.g., Figure 7 For example, lithium fluoride (LiF) can be configured based on fluoride anions (F-) and lithium cations (Li + In some aspects, the fluoride anion (F-) and the lithium cation (Li + ) can produce lithium oxide (Li2O), lithium nitrate (LiNO3) and / or nitrogen-oxygen compounds. In one implementation, lithium fluoride (LiF) can be produced based on the lithium cations (Li + ) 2825 and fluoride anions (F-) 3012 ( grafted to the first polymer chain 3010 and / or the second polymer chain 3020 Fig.30 ) are formed by a combination of. In some aspects, the lithium cation (Li + )2825 and fluoride anion (F - )3012 can consume at least some of the lithium cations (Li + ) 2825, thereby reducing the growth of lithium-containing dendrites from the anode 2820 (for simplicity, Fig.28 2800). Reducing the growth of lithium-containing dendrites from the anode can in turn increase the charge rate, discharge rate, energy density, cycle life, or any combination thereof of the battery 2800. Additionally, lithium fluoride (LiF), lithium oxide (Li2O), lithium nitrate (LiNO3), or nitrogen-oxygen-containing additives can form one or more regions across one or more of the anode 2820 or the solid electrolyte interface phase 2840.

[0299] In some aspects, the inorganic and / or ionic conductor 3018 of the protective layer 2860 may include additives such as lithium salts, including lithium nitrate (LiNO3), and / or inorganic ion conductive ceramics, including lithium lanthanum zirconium oxide (LLZO), NASICON-type oxides Li 1+x Al x Ti 2–x (PO4)3 (LATP) and / or lithium tin phosphorus sulfide (LSPS), and / or nitrogen-oxygen containing additives. At least some of these additives dispersed throughout region "A" and / or protective layer 2860 may dissociate to produce lithium cations (Li + )2825. In this way, the presence of at least some additives within the protective layer 2860 can increase the charge rate, discharge rate and / or energy density of the lithium-sulfur battery 2800.

[0300] In one implementation, the first polymer chain 3010 may be composed of a first plurality of interconnected monomer units "C" (e.g., Fig.36 and 37 ) is formed, and the second polymer chain 3020 can be formed by a second plurality of interconnected monomer units "D". In some aspects, the first plurality of interconnected monomer units "C" and the second plurality of interconnected monomer units "D" can be the same. In other aspects, the first plurality of interconnected monomer units "C" and the second plurality of interconnected monomer units "D" can be different from each other.

[0301] In some aspects, the first polymer chain 3010 and the second polymer chain 3020 can be based on exposure to nitrogen-containing groups (e.g., nitrate ions NO3 - ) and cross-linked with each other, some of the nitrogen-containing groups can be cured in epoxy resin and / or include amine-containing groups. Additionally or alternatively, the first polymer chain 3010 and / or the second polymer chain 3020 can be prepared to include a liquid bisphenol A epichlorohydrin-based epoxy resin, a 500 average M n For example, in one implementation, the protective layer 2860 may be prepared to include between 2 wt% and 5 wt% of a bifunctional bisphenol A / epichlorohydrin derived liquid epoxy resin, between 15 wt% and 25 wt% of a 500 average M n%, 5 wt % to 15 wt % of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 40 wt % to 60 wt % of lithium lanthanum zirconium oxide (LLZO). In some other aspects, protective layer 2860 can be prepared to include between 2 wt % and 5 wt % of a difunctional bisphenol A / epichlorohydrin derived liquid epoxy resin, between 15 wt % and 25 wt % of a 500 average M n %, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (ECC) between 5 wt % and 15 wt %, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) between 15 wt % and 20 wt %, lithium lanthanum zirconium oxide (LLZO) between 40 wt % and 60 wt %, and diphenyl iodonium hexafluorophosphate (DPIHFP) between 1 wt % and 5 wt %. In addition, the protective layer 2860 can be coated and / or deposited on the anode 2820 by a roll-to-roll device. For example, the protective layer is one or more of spray coating, gravure coating, micro-gravure coating, slot die coating, doctor blade coating, and / or Meyer rod spiral coating on the anode.

[0302] In some implementations, the cell 2800 can be arranged in one or more additional configurations. For example, upon exposure to one or more ultraviolet (UV) curing accelerators (including one or more cationic photoinitiators), the first polymer chain 3010 and the second polymer chain 3020 can participate in one or more cross-linking polymerization reactions with each other and form the protective layer 2860. As discussed, the UV curing accelerator can be provided by the environment 3050, which can include an ultraviolet (UV) radiation source.

[0303] In some aspects, one or more cross-linking polymerization reactions may include ring-opening polymerization (ROP). In addition, one or more ultraviolet (UV) curing accelerators include a variety of onium salts, which may include one or more triphenylsulfonium salts, one or more diazonium salts, one or more diaryl iodonium salts, one or more ferrocenium salts and / or one or more metallocene compounds. In some aspects, one or more ultraviolet (UV) curing accelerators may include one or more antimony salts and / or polyols that may serve as reactive diluents.

[0304] In some aspects, protective layer 2860 can be formed from multiple polymers that are uniformly mixed together and / or cross-linked (e.g., via cationic polymerization and / or ultraviolet (UV) curing) to form a three-dimensional (3D) lattice. Protective layer 2860 can be formulated according to one or more of the formulations disclosed in the following formulation examples 21-22:

[0305] Example 21: For amine-curable epoxy-based film compositions

[0306]

[0307] Example 22: For amine-curable epoxy-based film compositions

[0308]

[0309] In some aspects, protective layer 2860 can be prepared following the steps of Example 23, which is an exemplary procedure for preparing a 30 milliliter (mL) sample scale dispersion of any one or more of the formulation formulas provided by Examples 21-22 and / or 24-28 disclosed herein.

[0310] Example 23: Procedure for preparing a protective layer

[0311]

[0312] When prepared according to Example 21, the protective layer 2860 has an initial curing temperature of 68° C. and a glass transition temperature (T g ). In some aspects, the protective layer 2860 can have one or more openings, also referred to as "pinholes," formed by Fig.31A As shown in the pinhole 3102A in FIG. 2 , a protective layer 2860 is formed to allow polysulfide 2882 to Fig.28 The polysulfide 2882 may at least partially coat the anode 2820 and thereby hinder the lithium cations (Li + ) 2825 can be freely moved and / or transported between the anode 2820 and the cathode 2810, which can facilitate the discharge-charge cycle operation of the battery 2800. In order to solve the undesirable formation of pinholes in the protective layer 2860 when prepared according to Example 21, the protective layer 2860 can be prepared according to Example 22. In this configuration, the protective layer 2860 has an initial curing temperature of 81°C, a curing peak temperature of 124°C, a curing heat enthalpy of 104 J / g, and a T of 63°C. g Variations of Example 21 or Example 22 are possible where the component loading levels are adjusted to + / - 3% of the listed levels. However, any formulation of protective layer 2860 may be prepared such that protective layer 2860 produces a T greater than 60°C. g and an initial curing temperature of less than 81° C. or a curing peak of less than 124° C. to cure at room temperature (eg, 18° C.-22° C.). In addition, the protective layer 2860 may be disposed on the anode 2820 according to Example 23 with a thickness between 100 nm and 3 μm.

[0313] The protective layer 2860 can be formulated according to either of Example 21 or Example 22 by following the procedure listed in Example 23 to address operational challenges commonly encountered with conventional lithium-sulfur batteries. For example, in conventional lithium-sulfur batteries using liquid electrolyte solutions, unnecessary and uncontrolled dissolution of polysulfides due to polysulfide shuttling can cause battery failure. In one or more specific examples, polysulfide attack on lithium can result in rapid battery capacity reduction due to continuous solid electrolyte interface phase (SEI) growth. This growth consumes lithium cations, thereby resulting in less lithium available for transfer to the cathode for a healthy discharge-charge operating cycle in a conventional lithium-sulfur battery. In addition, due to, for example, a gradient in electrochemical potential that is beneficial to lithium-lithium metal bonding, the remaining lithium cations can adhere to other lithium cations, thereby generating lithium-containing dendrite structures that grow from the anode and extend from the anode to the cathode and can thereby cause short circuiting of conventional lithium-sulfur batteries.

[0314] In order to protect the lithium contained in the anode 2820 from the influence of polysulfide migration from the cathode 2810 to the anode 2820, and to inhibit the formation of lithium-containing dendrites, the protective layer 2860 can be directly coated on the anode 2820 before activation and operating the discharge-charge cycle of the battery 2800. Therefore, the protective layer 2860 can be prepared to include the first polymer chain 3010 and the second polymer chain 3020. Each of the first polymer chain 3010 and the second polymer chain 3020 can have (for example, Fig.36 and 37 ) repeating monomer units, and may be the same or different from each other. In addition, in some aspects, when the protective layer 2860 is formulated according to Example 21 or Example 22, at least some of the carbon atoms 3014 on each polymer chain can form carbon-carbon bonds with each other via ring-opening (ROP) cationic polymerization (e.g., optionally based on a catalyst), and an amine-curable epoxy-based film can be formed thereby. In some other aspects, when the protective layer 2860 is formulated according to one of Examples 24 to 28 (presented below), at least some of the carbon atoms 3014 on each polymer chain can form carbon-carbon bonds 3026 with each other via ultraviolet (UV) curable ROP cationic polymerization.

[0315] In addition, catalyst-based or UV curing of the difunctional component and / or the multifunctional component can initiate and / or facilitate crosslinking of the first polymer chain 3010 and the second polymer chain 3020 via carbon-carbon bonds 3026 to effectively protect the anode 2820. Fig.28 or Fig.303018) may be attached to at least some of the inorganic and / or ionic conductors 3018 to enable additional tunability of the protective layer 2860. In this way, the protective layer 2860, when formulated by any of the formulations disclosed in Examples 21 to 28, can provide multiple advantages relative to conventional anode protective layers that typically have only one component.

[0316] In some implementations, the protective layer 2860 can be formulated to include multiple polymer components, such as where the first polymer chain 3010 and the second polymer chain 3020 are different from each other, so that the protective layer 2860 is relatively more flexible to cure on and over the anode 2820 after spray coating. This flexibility can prevent the protective layer 2860 from disintegrating during the manufacturing process. In addition, coating the protective layer 2860 directly on the anode 2820 can uniformly strip and plate at least some lithium cations (Li+) 2825 during the operating discharge-charge cycle of the battery 2800, thereby minimizing lithium dendrite formation. In some aspects, the inorganic and / or ionic conductor 3018 (such as LLZO) dispersed throughout the protective layer 2860 can be ionically conductive and designed to minimize the impedance growth of the battery 2800. In addition, UV curing can be used to replace the conventional heat drying process to accelerate the curing of the protective layer 2860 and minimize the potential adverse effects of the processing time of the protective layer 2860 on the anode 2820.

[0317] Fig.31A A micrograph of an exemplary baseline protective layer 3100A according to some implementations is shown. The baseline protective layer 3100A may be Fig.28 An example of a protective layer 2860 of and prepared according to Example 21 provided previously, thereby resulting in the formation of pinhole 3102A. In some aspects, pinhole 3102A can be as Fig.31A In some other aspects, the pinhole 3102A may be smaller or larger than Fig.31A Additionally, the baseline protective layer 3100A may have multiple instances of pinholes 3102A that may collectively adversely interfere with healthy operating discharge-charge cycles of the battery 2800. For example, the pinholes 3102A may allow at least some polysulfides 2882 to pass through the pinholes 3102 to contact the anode 2820 and / or otherwise interfere with the formation of the solid electrolyte interface phase 2840, thereby reducing the cycling efficiency of the battery 2800.

[0318] Fig.31B A micrograph of an exemplary protective layer 3100B according to some implementations is shown. The protective layer 3100B may be prepared according to Example 22 by the method disclosed in Example 23. Fig.28The protective layer 3100B can minimize pinhole formation so that there are no pinholes or one or more smaller pinholes 3102B, thereby reducing the risk of at least some polysulfide 2882 contacting the anode 2820 and correspondingly improving the operational discharge-charge performance of the battery 2800.

[0319] Fig.32 According to some implementations, Fig.28 3200 is a micrograph of a cross-sectional view of a protective layer 2860 of a battery 2800. The protective layer 2860 can be prepared according to Example 21 by the method disclosed in Example 23. In some other aspects, the protective layer 2860 can be prepared according to other formulations disclosed in the examples (including Example 22).

[0320] Fig.33A According to some implementations, Fig.28 2800 of the battery 2800. The crosslink density 3300A can be an example of the crosslink density of the protective layer 2860 when prepared according to Example 21 by the method disclosed in Example 23, and thus has a certain number (e.g., 9) of crosslink points 3306A per unit area 3302A. In this way, each crosslink point 3306A can be separated from an adjacent crosslink point 3306A by a dimension 3304A.

[0321] Fig.33B According to some implementations, Fig.28 Another exemplary crosslink density 3300B of protective layer 2860 of battery 2800. Crosslink density 3300B may be an example of a crosslink density of protective layer 2860 when prepared according to Example 22 by the method disclosed in Example 23, and thus having a certain number (e.g., 25) of crosslink points 3306B per unit area 3302B. In this way, each crosslink point 3306B may be separated from an adjacent crosslink point 3306B by a dimension 3304B that may be smaller than dimension 3304A, and thus is configured to trap at least some TFSI after dissociation of LiTFSI in electrolyte 2830 and / or included in protective layer 2860. - Anion 2826. By trapping at least some TFSI - The anion 2826 is within the crosslink density 3300B, and the protective layer 2860 can play a role in preventing the trapped TFSI - Anion 2826 blocks lithium cation (L + )2825 is delivered and / or contacted to the anode 2820, thereby improving the operational discharge-charge cycle performance of the battery 2800.

[0322] Fig.34A triarylsulfonium salt (Ar3S + XOtM - ) is an exemplary ring opening (ROP) mechanism 3400 of the present invention. In general, the use of a UV initiator to initiate ROP polymerization via crosslinking of a first polymer chain 3010 with a second polymer chain 3020 can accelerate the curing of the protective layer 2860 from a maximum of 24 hours to 1 to 3 seconds, which may be desirable for large-scale manufacturing processes. In some aspects, the use of a UV initiator can accelerate epoxy crosslinking of existing epoxy systems (e.g., Examples 21-22 and / or Examples 24-28 to be disclosed herein) without the need for additional introduction of new chemicals. In addition, the UV initiator selected to achieve epoxy crosslinking can be a cationic UV initiator. In this way, when various epoxy compounds are exposed to UV radiation, they can produce relatively strong Lewis acids and / or Brunst-Lowry acids ( -Lowry acid), which can then correspondingly initiate the ROP of the epoxy groups.

[0323] For triarylsulfonium salts (Ar3S + XOtM - ), showing the ROP mechanism 3400. In some aspects, HMtXn is a Lewis acid (e.g., HBF4, HPF6, HAsF6, HSbF6) and M is a monomer (e.g., Fig.36 and 37 and / or including epoxy groups). Unlike free radical polymerization, cationic polymerization (e.g., including UV-initiated cationic ROP) is not inhibited by oxygen. However, polymer chain growth and crosslinking reactions can be inhibited by trace amounts (e.g., less than 0.1 wt %) of water and or chemicals (e.g., amines and / or urethanes). However, the initiating moiety in UV-initiated cationic ROP is relatively chemically stable for a long duration (e.g., greater than 24 h). In this way, polymerization in UV-initiated cationic ROP can continue even in the absence of visible light. In addition, depending on the amount of protective layer 2860 being attempted to be prepared, some monomers (e.g., Fig.36 and 37 ) and / or oligomers can be cured with lower UV doses.

[0324] Fig.35 According to some implementations, a device suitable for use as Fig.28A variety of exemplary onium salts 3500 of cationic photoinitiators for the protective layer 2860 of the battery. The onium salt 3500 can be an example of an inorganic and / or ionic conductor 3018 and can thus be used to initiate crosslinking of the first polymer chain 3010 with the second polymer chain 3020 to form the protective layer 2860. In some aspects, the onium salt 3500 can include a diphenyl iodonium salt and / or a triphenyl sulfonium salt (both in Fig.35 ), as well as diazonium salts, diaryl iodonium salts, ferrocenium salts and / or various other metallocene compounds (for simplicity, Fig.35 3500). The efficiency of the onium salt 3500 as a cationic photoinitiator may depend, at least in part, on its corresponding solubility in the protective layer 2860 (e.g., when formed into a resin) and / or its corresponding polarity and / or surface charge. In general, solubility increases with increasing size of the anion in the corresponding onium salt 3500 because the charge is dissipated over the relatively large surface area of ​​the anion, thereby reducing the hydrophilicity of the corresponding onium salt 3500. In this way, the solubility and reactivity of at least some onium salts 3500 in non-ionic resins may be determined in accordance with tetrafluoroborate (BF 4- )<hexafluorophosphate (PF 6- )<Hexafluoroarsenate (AsF 6- )<Fluoronium(SbF 6- ). In some aspects, antimony salts (e.g., including fluorinium anions) can be most commonly selected as cationic photoinitiators due to their relatively higher solubility and reactivity over the other listed salts. Additionally, in addition to solubility alone, spectral properties such as light absorption range and / or bond cleavage efficiency can affect the initiation rate of polymerization of monomers in the first polymer chain 3010 and / or the second polymer chain 3020.

[0325] Fig.36 According to some implementations, a suitable Fig.28 A variety of exemplary monomers 3600 of various cationic photopolymerizable compositions for the protective layer of a battery. The monomers 3600 may each be Fig.30 The first polymer chain 3010 and the second polymer chain 3020 may be used to initiate crosslinking of the first polymer chain 3010 and the second polymer chain 3020 to form the protective layer 2860. That is, multiple instances of the repeating monomer unit "C" may be attached to the exposed carbon and / or other atoms to form the protective layer 2860. Fig.30 and Fig.36 The first polymer chain 3010 of a plurality of units is formed in the manner shown in FIG. 3 , for example, “C”-“C”-“C”-…, etc. The repeating monomer unit “D” may be the same as or different from the repeating monomer unit “C”, and thus Fig.30 and 36The second polymer chain is formed in a similar manner to the first polymer chain by attaching to additional instances of the repeating monomer unit "D", such as "D"-"D"-"D"-..., etc.

[0326] In some aspects, the cationic UV resin formulation formed from at least some of the monomers 3600 may include one or more examples of alicyclic epoxy compounds, any of which may be used as epoxy groups. Compared to linear aliphatic groups or aromatic epoxy molecules, alicyclic epoxy compounds tend to have relatively greater reactivity, so that when any one or more of the monomers 3600 are used to produce the protective layer 2860, a tight network of polar groups may be formed to produce a relatively brittle polymer-based final product. In order to reduce undesirable brittleness, some UV cationic resin formulations may be prepared to include polyols (for simplicity, Fig.36 2860) as a reactive diluent and performance modifier. In some aspects, the polyol can act as a monomer material that reacts to form an epoxy-based network. Compared to alicyclic epoxy groups alone, many different polyols can be utilized, ranging from difunctional and trifunctional diols, polycaprolactone oligomers, and even higher order dendritic polyols. Selecting between a relatively higher number of available polyols can help fine-tune the end-use properties of protective layer 2860.

[0327] Fig.37 According to some implementations, a suitable Fig.28 The ultraviolet (UV) curable monomer 3700 of the protective layer 2860 of the battery 2800. The monomer 3700 may be Fig.30 An example of monomer "B" and / or monomer "C" and may include diglycidyl 1,2-cyclohexanedicarboxylate (DG-CHDC), 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate (ECC), triphenylsulfonium trifluoromethanesulfonate (TPS-TF), diphenyliodonium trifluoromethanesulfonate (DPI-TF), diphenyliodonium hexafluorophosphate (DPI-HFP), poly[(phenyl glycidyl ether)-co-formaldehyde] (PPGEF) and / or glycidyl 2,2,3,3-tetrafluoropropyl ether (GTFEP).

[0328] In some aspects, protective layer 2860 can be formed from a plurality of polymers (e.g., formed from monomer 3700) that are uniformly mixed together and / or cross-linked (e.g., via ultraviolet light (UV curing) having a UV curing wavelength of 254 nanometers (nm)) to form a three-dimensional (3D) lattice disposed on anode 2820. The protective layer (e.g., when formed as a 3D lattice) can be formulated according to one or more of the formulations disclosed in Examples 24-28 below:

[0329] Example 24: UV Curable Formulation

[0330]

[0331] Example 25: UV Curable Formulation

[0332]

[0333]

[0334] Example 26: UV Curable Formulation

[0335]

[0336] Example 27: UV Curable Formulation

[0337]

[0338] In some aspects, polyethylene glycol (PEG), other polyethers and / or other polyols may be used and / or substituted for any of the components listed in Examples 23-27, depending on the performance requirements of the protective layer 2860. In addition, variations of Examples 24-27 are possible when the component loading levels are adjusted to + / - 3% of the listed levels. In addition, in addition to polyoxypropylene diamine (e.g., D-230), all listed components are compatible with UV-catalyzed cationic ROP. In this way, the first polymer chain 3010 can initiate crosslinking with the second polymer chain 3020 to form a carbon-carbon bond 3026 and produce a 3D lattice disposed on the anode 2820. The 3D lattice can be formed by the various components listed in each example, wherein the components are uniformly mixed together, interconnected with each other, and dispersed throughout the protective layer 2860. That is, the first polymer chain 3010 and the second polymer chain 3020 are exemplary, and according to the example, additional polymer chains are possible. Some examples may also include additional polymer chains that are crosslinked to each other in addition to one or more of the first polymer chain 3010 or the second polymer chain 3020. In addition, each component listed in any one or more of Examples 21-22 and / or 24-28 may be formed by a corresponding polymer chain.

[0339] That is, in Example 26 representing another example, the average M n Polyoxyethylene bis(glycidyl ether) (PEG-DEG-500) can be represented as monomer "B" in the first polymer chain 3010 and diglycidyl 1,2-cyclohexanedicarboxylate (DG-CHDC) can be represented as monomer "C" in the second polymer chain 3010. Monomer "B" can be bonded to additional instances of monomer "B" in 3D and also to one or more instances of monomer "C" to form a 3D lattice. Additional components (for simplicity, Fig.30) may be represented as monomer "D", etc. For example, in Example 26, PPGEF (number average molecular weight (Mn) = 345) may be represented as monomer "D" and bonded in 3D to additional examples of itself and monomer "B" and / or monomer "C" to form a 3D lattice, where lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and / or lithium lanthanum zirconium oxide (LLZO) (500 nm particle size) may be depicted as inorganic and / or ionic conductors 3018 and dispersed throughout the protective layer 2860.

[0340] Certain fast curing alicyclic epoxy monomers such as those included in Examples 25 and 27 above (e.g., 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate (ECC)) can be incorporated into protective layer 2860 to provide a more crosslinked structure at higher crosslink density levels such as Fig.33B The crosslink density of 3300B is rapidly crosslinked together through a cationic polymerization process to produce a network of polar groups, thereby at least partially entrapping TFSI. - Anions 2826 are present in protective layer 2860. In addition, in some aspects, various UV initiators (e.g., hexafluorophosphate onium salts (PF6 - ) can replace the photoinitiators disclosed in Examples 24-27. In some other aspects, the anion of fluoroantimonic acid (SbF6 - ) can replace the photoinitiators disclosed in Examples 24-27. The anion of fluoroantimonate (SbF6 - ) can be dissolved in the electrolyte 2830 and can be advantageously used with at least some lithium cations (Li + ) 2825 alloys at least some regions of the protective layer 2860. In this way, the alloying of some regions of the protective layer 2860 can consume at least some of the lithium cations (Li + )2825, thereby removing the consumed lithium cations to prevent them from participating in lithium-lithium metal bonding, thereby forming undesirable dendrites from the anode 2820 toward the cathode 2810.

[0341] Additionally, in one implementation, once UV curing has been initiated (e.g., by any of the photoinitiators listed in Examples 24-27), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) can act as a co-initiator, thereby increasing the cure rate. For example, activation of the ROP reaction of the exemplary monomer poly(ethylene glycol) diglycidyl ether (DGEPEG) can be achieved using lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a subsequent propagation step. In the activation step, lithium cations (e.g., provided by LiTFSI) attack the carbon-oxygen bonds on one or more epoxy groups of DGEPEG. When this reaction occurs under acidic conditions, the epoxy groups are converted to hydroxyl ions. During the initiation and propagation steps, the hydroxyl ions react with the epoxy groups and other hydroxyl ions via nucleophilic reactions to produce chain extension via the formation of C-O-C bonds.

[0342] As an alternative to previously presented examples 24-27, protective layer 2860 can be formulated to include a fluorinated material (e.g., a fluoropolymer such as glycidyl 2,2,3,3 tetrafluoropropyl ether (GTFEP)) so as to be at least partially grafted onto carbon atoms 3014. In this way, GTFEP can be used as a fluoride ion (F - )3012, which can later dissociate from its corresponding carbon atom to react with lithium cations (Li + )2825 combination, thereby producing lithium fluoride (LiF), as discussed elsewhere in this disclosure. Example 28 can be prepared according to the procedure provided by Example 23, including the following components:

[0343] Example 28: Fluorinated polymer

[0344]

[0345]

[0346] Example 28, as presented above, may not be initiated by UV curing because the polyoxypropylene diamine (e.g., D-230) may not be compatible with UV-catalyzed cationic ROPs. However, in some aspects, polyoxypropylene diamines (e.g., D-230) can be replaced with 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate (ECC), thereby making Example 28 UV curable, similar to Examples 23-27.

[0347] Fig.38 According to some implementations, a suitable Fig.37Various exemplary non-reactive diluents 3800 of dilution levels in UV-curable formulations prepared from UV-curable monomers of 1,2-dimethoxyethane (DME) and / or triethylene glycol dimethyl ether (TEGDME). In some aspects, non-reactive diluent 3800 can be removed from protective layer 2860 by baking at 100° C. after cross-linking. In some other aspects, non-reactive diluent 3800 can remain in protective layer 2860 to enhance lithium cation (Li + )2825’s spread.

[0348] Fig.39 According to some implementations, a suitable Fig.37 In some aspects, the reactive diluents 3900 may act as toughening agents to release stress of at least some carbon atoms 3014 (e.g., which may be cross-linked with each other) within the protective layer 2860 to thereby minimize pinhole formation. Additionally, in some aspects, the non-reactive diluents 3800 and / or the reactive diluents 3900 may be or include materials used as additives to the UV-curable formulation in an amount between 1% and 50% by weight of the formulation to adjust the viscosity according to the deposition method (e.g., low viscosity for spray coating, compared to high viscosity for slot die or drawdown coating methods). In this way, the remaining components are reduced in proportion to the amount of diluent added.

[0349] Fig.40A Graph 4000A showing capacity (% of initial) versus cycle number according to some implementations. Graph 4000A depicts the performance of a cell 2800 prepared according to Example 22 relative to Example 21 and an unprotected 40 μm lithium anode (e.g., provided as a reference, "Ref."). Example 22 shows consistently higher capacity retention (e.g., as % of initial) as a function of the number of operating discharge-charge cycles compared to Example 21 and an unprotected 40 μm lithium anode.

[0350] Fig.40BA graph showing capacity (mAh / g) versus number of cycles according to some implementations. Graph 4000A depicts the performance of a cell 2800 prepared according to Example 22 relative to Example 21 and an unprotected 40 μm lithium anode (e.g., provided as a reference, “Ref.”). Example 22 shows consistently higher capacity retention (e.g., in milliampere hours per gram mAh / g) as a function of the number of operating discharge-charge cycles compared to Example 21 and an unprotected 40 μm lithium anode. Graph 4000A depicts the performance of a cell 2800 prepared according to Example 22 relative to Example 21 and an unprotected 40 μm lithium anode (e.g., provided as a reference, “Ref.”). Example 22 shows consistently higher capacity retention (e.g., in % of initial) as a function of the number of operating discharge-charge cycles compared to Example 21 and an unprotected 40 μm lithium anode.

[0351] Fig.41A Another graph showing capacity (% of initial) versus cycle number according to some implementations. Graph 4100A depicts the performance of a cell 2800 prepared according to Example 28 relative to Example 21 and an unprotected 40 μm lithium anode (e.g., provided as a reference, "Ref."). Example 22 shows consistently higher capacity retention (e.g., as % of initial) as a function of the number of operating discharge-charge cycles compared to Example 21 and an unprotected 40 μm lithium anode.

[0352] Fig.41B Another graph showing capacity (mAh / g) versus cycle number according to some implementations. Graph 4100B depicts the performance of a cell 2800 prepared according to Example 28 relative to Example 21 and an unprotected 40 μm lithium anode (e.g., provided as a reference, “Ref.”). Example 22 shows consistently higher capacity retention (e.g., mAh / g) as a function of the number of operating discharge-charge cycles compared to Example 21 and an unprotected 40 μm lithium anode.

[0353] Fig.42AAnother exemplary battery 4200A according to some other implementations is shown. Battery 4200A may be an example of other battery configurations disclosed herein. In one implementation, battery 4200A may be implemented as a lithium-sulfur battery and may include a cathode 4210, an anode structure 4222 including an anode 4220 positioned relative to the cathode, a separator 4250 positioned between the anode 4220 and the cathode 4210, and an electrolyte 4230. Anode 4220 may be disposed on and / or coupled to a substrate 4201, such as a metal current collector formed of nickel (Ni) or aluminum (Al), etc. Cathode 4210 may be disposed on and / or coupled to a substrate 4202, such as a metal current collector formed of nickel (Ni) or aluminum (Al), etc. In some aspects, electrolyte 4230 may be prepared by mixing at least two or more solvents, such as the solvents disclosed in Examples 1-20 presented previously. Electrolyte 4230 may be dispersed throughout cathode 4210 and in contact with anode 4220. In some aspects, anode 4220 can be a single solid lithium metal foil. In this way, at least some of the lithium cations (Li + ) 2825 can participate in dissociation reactions and / or combination reactions during the operational discharge-charge cycle of the battery 4200A. That is, during the discharge cycle of the battery 4200A, the lithium cations (Li + ) 4225 can be transported by the electrolyte 4230 and maintained in its electrochemically favorable position within the cathode 4210 (for simplicity, Fig.42A ). Then, during a charge cycle of the battery 4200A, upon exposure to an external current source, the lithium cations (Li + )4225 returns to anode 4220.

[0354] Additionally, a solid electrolyte interface (SEI) layer 4240 may be formed on anode 4220. In some aspects, protective layer 4260 may be formed at least partially within and / or on SEI layer 4240 and facing cathode 4210. In some aspects, in response to a reaction involving lithium cations (Li + ) and one or more redox reactions of one or more solvents of the electrolyte 4230, the SEI layer 4240 may be formed of one or more compounds on the anode 4220. In some implementations, the protective layer 4260 may be at least partially formed of a carbonaceous material including one or more of flat graphene, wrinkled graphene, carbon nanotubes (CNTs), carbon nano onions (CNOs), or non-hollow carbon spherical particles (NHCS), one or more of which may be Fig. 9B An example of a carbonaceous structure 956.

[0355] In one implementation, the anode 4220 of the anode structure 4222 can be formed as a solid lithium monolayer that can output lithium cations (Li ions) during an operating discharge cycle of the lithium-sulfur battery. + ). The SEI layer 4240 may be formed on the solid lithium monolayer, and the protective layer 4260 may be formed on and at least partially disposed within the SEI layer 4240 in response to the operating discharge-charge cycle of the lithium-sulfur battery 4200A. The protective layer 4260 may be an example of other protective layer configurations disclosed herein, including Fig.28 Protective layer 2860.

[0356] Additionally or alternatively, the protective layer 4260 may include a polymer backbone 4262 formed of interconnected carbon atoms 4263. In this way, at least some of the interconnected carbon atoms 4263 may move during the operating discharge-charge cycle of the battery 4200A and define the cooperative segmental mobility (also referred to as "segmental motion") of the protective layer 4260. Additional polymer chains 4264 may be cross-linked to each other and to at least some of the interconnected carbon atoms 4263 of the polymer backbone 4262. Each of the additional polymer chains 4264 may be formed of interconnected monomer units 4266. In some aspects, the plasticizer 4268 may be dispersed throughout the protective layer 4260 without being covalently bonded to at least some of the interconnected carbon atoms 4263 of the polymer backbone 4262. In some aspects, the plasticizer 4268 may be formed of and / or may include one or more of a polyethylene glycol (PEG or PEO)-based oligomer, a nitrile (e.g., succinonitrile, glutaronitrile, adiponitrile). Additionally or alternatively, plasticizer 4268 may be formed from and / or may include a solvent including dimethoxyethane (DME), tetrahydrofuran (THF), diethyl ether, dioxolane (DOL), tetraethylene glycol dimethyl ether (TEGDME), toluene, bis(2,2-trifluoroethyl ether) (TEE), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC), and / or ethylene carbonate (EC). Plasticizer 4268 may separate adjacent monomer units of interconnected monomer units 4266 of at least some of the additional polymer chains 4264 (e.g., by Fig.42B Increasing the spacing between adjacent monomer units can increase the cooperative segmental mobility of at least some of the additional polymer chains 4264, thereby increasing the ionic conductivity of the protective layer 4260. In addition, in some aspects, increasing the concentration level of the plasticizer 4268 in the protective layer 4260 can increase the lithium cation (Li + ) conductivity. In some other aspects, the linear polymer and / or oligomer chain (for simplicity, Fig.42A4265 to at least some of the interconnected carbon atoms 4263 of the polymer backbone 4262). In this way, the linear polymer and / or oligomer chains can increase the cooperative segmental mobility (e.g., the maximum cooperative segmental mobility) of the protective layer 4260, which can increase the lithium cation (Li cation) passing through the protective layer 4260. + ) conductivity. For example, oligomeric substances such as polyoxypropylene diamine (e.g., M-600) can increase the cooperative segmental mobility (eg, maximum cooperative segmental mobility) of the protection layer 4260.

[0357] In some cases, protective layer 4260 can be configured to be resistant to corrosion at a glass transition temperature (T g ) melts at a temperature lower than 4200°, so that increasing the glass transition temperature causes the cooperative segmental mobility (e.g., the maximum cooperative segmental mobility) of the polymer chains to decrease. In addition, reducing the cooperative segmental mobility (e.g., the maximum cooperative segmental mobility) of the polymer chains can reduce the lithium cations (Li + ) conductivity. In this way, aspects of the present disclosure can make lithium cations (Li + ) to maximize electrical conductivity.

[0358] In some aspects, protective layer 4260 can be prepared by Example 23 according to the formulation provided by Example 29 disclosed below:

[0359] Example 29: Formulation containing plasticizers

[0360]

[0361] In some other implementations, the protective layer 4260 can be formed on the anode as a three-dimensional (3D) polymer lattice (for simplicity, Fig.42A In some aspects, the first polymer chain and the second polymer chain may be respectively Fig.30 3000 of the diagram of the first polymer chain 3010 and the second polymer chain 3020 in the region "A" shown in FIG. In some implementations, each of the first polymer chain and the second polymer chain may include at least temporarily chemically bonded to an oxygen anion (O 2- ), fluoride anion (F - ) and / or nitrate anions (NO3 - ) carbon atom. Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) (for simplicity, Fig.42A ) can be dispersed throughout the 3D polymer lattice to dissociate into lithium cations (Li+ ) 4225 and TFSI-anions 4226. In this way, the first polymer chains and the second polymer chains can form a 3D polymer lattice with a crosslink density sufficient to entrap the TFSI-anions 4226 by crosslinking 4265 with each other. For example, the crosslinks 4265 can be initiated upon exposure to a high energy environment including ultraviolet (UV) energy and LiTFSI, where LiTFSI can be used as a polymerization co-initiator compound.

[0362] In other implementations, the first polymer chain and the second polymer chain can form a 3D polymer lattice by cross-linking polymerization, and the cross-linking polymerization reaction can include ultraviolet (UV) curing that can be performed at a curing rate. In some aspects, the polymerizing co-initiator compound can increase the curing rate. In some cases, the additive is uniformly dispersed throughout the 3D polymer lattice and may include lithium nitrate (LiNO3), inorganic ion conductive ceramics (including lithium lanthanum zirconium oxide (LLZO), NASICON-type oxide Li 1+x Al x Ti 2–x (PO4)3 (LATP) or lithium tin phosphorus sulfide (LSPS)) or nitrogen-oxygen containing additives. In this way, the inorganic ion conductive ceramic can be uniformly embedded in the 3D polymer lattice and / or uniformly distributed in the protective layer 4260. In some aspects, the protective layer 4260 can include a dry solvent.

[0363] In some additional or alternative implementations, the protective layer 4260 can intercept various types of anions (for simplicity, Fig.42A 4260). For example, the protective layer 4260 can be formed of a plurality of components including relatively flexible oligomeric epoxy resin and / or polyol-based compounds, relatively rigid polymeric epoxy resin-based compounds, and / or photoinitiator molecules. In some aspects, at least some of the relatively flexible oligomeric epoxy resin and / or polyol-based compounds can prevent pinholes from forming in the protective layer 4260. The lithium-containing salt uniformly dispersed throughout the protective layer 4260 can dissociate into lithium (Li+) cations and various types of anions.

[0364] In addition, in some cases, the protective layer 4260 may be formed on the anode in response to exposure to an ultraviolet (UV) energy source that facilitates UV curing of at least some components of the protective layer 4260. In addition, in some aspects, the protective layer 4260 may include a non-reactive diluent including 1,2-dimethoxyethane (DME), tetrahydrofuran (THF), triethylene glycol dimethyl ether (TEGDME) or 2-methyl-2-oxazoline (MOZ). In some other aspects, the protective layer 4260 may include a reactive diluent including 1,3-dioxolane (DOL), 3,3-dimethyloxetane (DMO), 2-ethyl-2-oxazoline (EOZ) or ε-caprolactone (CL). In this way, the per unit formulation weight of the protective layer 4260 can be based on the concentration level of the non-reactive diluent or the reactive diluent relative to the components of the protective layer 4260. In some aspects, the reactive diluent can reduce the mechanical stress of at least some cross-linked units within the protective layer 4260.

[0365] In some aspects, the reactive diluent can be removed from the protective layer 4260. In some other aspects, after at least some of the multiple components (e.g., relatively flexible oligomeric epoxy resin and / or polyol-based compounds, relatively rigid polymeric epoxy resin-based compounds, and / or photoinitiator molecules) are cross-linked 4265 with each other, the reactive diluent can remain in the protective layer 4260. The retention of the reactive diluent in the protective layer 4260 after cross-linking two or more components can increase the amount of lithium cations (Li + ) 4225 through the diffusion of electrolyte 4230. In one implementation, a relatively rigid polymerized epoxy resin-based compound can be formed from several repeating epoxy monomer units. For example, each repeating epoxy monomer unit is 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (ECC), which can crosslink with additional ECC monomer units and produce a polar group network (for simplicity, Fig.42A The network of polar groups can entrap at least some of the anions generated when the lithium-containing salt dissociates.

[0366] Fig.42B According to some implementations, Fig.42A FIG4200B is an enlarged view of portion “E” of battery 4200A. In some aspects, plasticizer 4268 can be cross-linked with additional monomer units (e.g., via crosslinks 3265) and not chemically (e.g., covalently) bonded to interconnected carbon atoms 4263 of polymer backbone 4262. At least some crosslinks 4265 of plasticizer 4268 can expand and / or contract in volume to impart flexibility to protective layer 4260. In this way, protective layer 4260 can expand and / or contract as needed to accommodate volume expansion of anode 4220 caused by operational discharge-charge cycles of battery 4200A.

[0367] In one implementation, the plasticizer 4268 can affect the cooperative segmental mobility (e.g., the maximum cooperative segmental mobility) of the protective layer 4260. For example, in the absence of the plasticizer 4268, the 3D lattice of the protective layer 4260 can be relatively rigid due to the higher degree of crosslinking 4265, which in turn can minimize the spacing 4267 between adjacent monomer units of the interconnected monomer units 4266. Introducing the plasticizer 4268 between adjacent monomer units can increase the spacing 4267, which provides more moving volume for additional polymer chains, thereby resulting in additional segmental motion of the protective layer 4260. For example, because the plasticizer 4268 is not covalently bonded to the interconnected carbon atoms 4263 of the polymer backbone 4262, the plasticizer can be able to maintain a relatively high degree of freedom of migration within the 3D lattice of the protective layer. The relatively high freedom of migration of the plasticizer 4268 can expand the spacing 4267 between adjacent monomer units, thereby increasing the flexibility of the protective layer 4260, which may be necessary to accommodate the volume expansion of the anode 4220 associated with the operating discharge-charge cycle of the battery 4200A.

[0368] Fig.43 An exemplary battery pack 4300 is shown that can be assembled according to one or more implementations of the subject matter disclosed herein. Exemplary applications of the disclosed battery pack 4300 include providing power for electric vehicles (EVs), portable electronic devices, aerospace applications, and energy storage systems. Battery pack 4300 is shown as including three battery modules 4310, 4320, and 4330. In some aspects, battery pack 4300 can include other numbers of battery modules assembled with each other. One or more battery modules can be configured in series, such as Fig.43 As shown, or may be configured to be stacked on top of each other. Each of the one or more battery modules may be in the shape of a cuboid or any other three-dimensional (3D) geometry. Each of the battery modules 4310, 4320, and / or 4330 may include one or more lithium-sulfur batteries 4312, each of which may be an example of one or more batteries disclosed herein. The batteries 4312 may be connected to each other, for example, in series, in parallel, or a mixture of both. In some implementations, the batteries 4312 may be welded to each other via conductive components 4314 and by using mechanical welding methods. In this way, the battery 112 may be prepared to deliver sufficient voltage and power for a desired end-use application area (e.g., EV). In some other aspects, the battery 112 may be welded to each other using an electronic conductive glue (for simplicity, Figure 1 The electronic conductive glue may be formed of any carbonaceous material disclosed herein. For example, in some aspects, the electronic conductive glue may include a carbonaceous material (e.g., Fig. 9B4300) can each have an exposed carbon-containing surface functionalized with a complementary pair of functional groups. In this way, cells 4312 can be conductively connected to each other without conductive components 4314. Removing conductive components 114 reduces the weight of battery pack 4300, thereby increasing the energy density of battery pack 4300 (e.g., measured in milliampere hours per gram (mAh / g)). In addition, battery pack 4300 may include additional systems and / or components built into battery pack 4300 (for simplicity, Figure 1 ), such as one or more protection units, monitoring units and sensors.

[0369] Fig.44 A method for manufacturing a Fig.43 When prepared in a jellyroll configuration, battery 4400 may be an example of any battery previously disclosed herein, such as Fig.28 Battery 2800 or Fig.42A Battery 4200A. For example, battery 4400 may have a cylindrical form factor that matches the size of an 18650 battery. In some aspects, battery 4400 may have a length between 65.1 millimeters (mm) and 65.3 mm and a circular cross-section with a diameter between 18.4 mm and 18.6 mm. In some other aspects, battery 4400 may have a rectangular cross-section and a prismatic form factor that may match the size of a CP3553 battery. For example, battery 4400 may have a height between 56 mm and 58 mm, a length between 34 mm and 36 mm, and a width between 6 mm and 8 mm. Battery 4400 is shown as including shell 4410 and roll core 4420. In general, the term "roll core" may imply designs for various types of cylindrical rechargeable batteries, including nickel-cadmium (Ni-Cd), nickel-metal hydride (Ni-MH), and lithium ion (Li-ion), wherein the type of battery design is named "roll core" because its cross-section resembles a curled sponge cake. Shell 4410 may have Fig.44 In this way, the winding core 4420 can be arranged in the shell 4410 along the longitudinal axis.

[0370] The winding core 4420 may be formed to have a cross-section having a circular, rectangular, square, triangular, or any other geometric shape. Fig.44As shown, the jellyroll 4420 can be formed by cylindrically rolling together various battery components including the anode 4422, the anode current collector 4402, the first barrier layer 4424, the cathode 4426, and the second barrier layer 4428. In addition, the anode 4422, the first barrier layer 4424, the cathode 4426, and the second barrier layer 4428 (collectively referred to as "internal battery components") can be laminated to each other. In some aspects, one or more of the first barrier layer 4426 and the second barrier layer 4428 can be Fig.28 The first barrier layer 4426 and the second barrier layer 4428 may be an example of one or more of the protective layer 2860 or the solid electrolyte interface phase (SEI) 2840 of the battery 2800. In some other aspects, one or more of the first barrier layer 4426 and the second barrier layer 4428 may be an example of one or more of the protective layer 4260 or the SEI 4240.

[0371] In some aspects, the inner battery components can be radially wound around axis AA' to form the winding core 4420. In some other aspects, the center pin (for simplicity, Figure 2 Anode 4422 (not shown) may be attached to the inner edge of anode 4422, and one or more of the various listed internal battery components may be laminated, radially wound, or rolled around a center pin to form a jellyroll 4420. In this manner, jellyroll 4420 may be formed such that anode 4422 and cathode 4426 are separated by first barrier layer 4424 and second barrier layer 4428 to avoid an undesirable “short circuit” type condition within battery 200.

[0372] The anode 4422, the first barrier layer 4424, the cathode 4426, and the second barrier layer 4428 can each be formed as a rectangular sheet so as to have similar or identical physical dimensions to one another. In this way, in some aspects, when formed as sheets, these internal battery components can be aligned with one another during rolling so that no sheet extends longitudinally from the winding core 4420 parallel to the axis AA'. Alternatively, in some other aspects, the anode 4422 or the cathode 4426 may include a tab 4423 extending longitudinally from the winding core 4420 parallel to the axis AA', such as Fig.44 Typically, the battery tabs provide electrical connections between the multi-layer current collector and an external target source, such as wiring of an electric vehicle (EV). Fig.44 In the configuration of the battery 4400 shown, in some aspects, the tab 4423 can be welded to one or more current collectors (for convenience, Fig.444426 to extend longitudinally along the axis AA'. In this way, the tab 4423 can connect the anode 4422 or the cathode 4426 to the negative terminal or the positive terminal of the shell 4410, respectively (for simplicity, the tab 4423 can be attached to the surface of the cathode 4426 to extend longitudinally along the axis AA') after the various internal battery components, for example, formed as thin sheets, are wound and / or laminated together to form the core 4420. In this way, the tab 4423 can connect the anode 4422 or the cathode 4426 to the negative terminal or the positive terminal of the shell 4410, respectively (for simplicity, Figure 2 not shown).

[0373] In one or more configurations of the alternatives discussed above, the electrode sheet (anode 4422 or cathode 4426) can be intentionally arranged to be offset from other internal battery components and / or the first barrier layer 4424 and the second barrier layer 4428 during the rolling process, so that the portion 4425 can extend longitudinally along the axis AA' of the winding core 4420. In some aspects, the conductive adhesive, such as glue or any carbonaceous material disclosed herein (for simplicity, Figure 2 4410) can be disposed on and near portion 4425 disposed within shell 4410, for example, at the top and bottom of shell 4410. In this way, portion 4425 can be electrically connected to the negative terminal and / or the positive terminal of shell 4410, thereby eliminating the need for mechanical welding methods.

[0374] In general, some non-lithium sulfur batteries (e.g., lead acid, lithium ion, nickel manganese cobalt (NMC), and / or lithium iron phosphate (LFP) batteries, etc.) can benefit from increased energy density and reduced cell impedance. Battery discharge-charge cycle performance can be increased by reducing battery weight, which can be achieved by removing or reducing the weight of various inactive components. Such inactive components can include anode connection tabs (e.g., Fig.44 The battery discharge-charge cycle performance can also be improved by increasing the external load ( Fig.44 The total contact area between the electrical connection of the anode current collector 4402 and / or the anode 4422 (not shown) can be increased, and the anode can be formed as a thin sheet and spans the entire length of the anode current collector 4402. Both goals, such as reducing the weight of the battery by removing non-moving parts and increasing the total contact area between the anode current collector 4402, can be achieved by coating at least a portion 4425 with a conductive carbon layer formed of an interconnected graphene material, which can be Fig. 8A An example of the carbonaceous particles 800, Fig. 9B One or more examples of interconnected aggregates 960 and / or the like described elsewhere herein.

[0375] Anode 4422 may be formed of any suitable material commonly used and / or used as an anode in a Li-S battery (e.g., a lithium single foil or a lithium-containing substrate), and may be an example of any other anode disclosed herein, such as Fig.28 Anode 2820 of battery 2800 or Fig.42A Anode 4220 of battery 4200A. In addition, anode 4422 can be coupled to anode current collector 4402 to support, for example, anode 4422. Cathode 4426 can be an example of any cathode disclosed herein, such as Fig. 22 Cathode 2200, Fig.26A or Fig.26B Cathode 2610, Fig.28 Cathode 2810, Fig.42A In some cases, cathode 4426 may be formed by, coupled to, and / or otherwise include electrode film 4204, which may be prepared to at least temporarily microscopically confine an electroactive material, such as elemental sulfur or other suitable sulfur-containing material, such as lithium sulfide. For example, in some cases, the electroactive material may be preloaded into the pores of electrode film 4204 and / or cathode 4426 to later interact with lithium ions (Li ions) during an operational discharge-charge cycle of battery 4400. + ) to form a coordination complex. In addition, in some aspects, the electrode film 4404 can be coated (e.g., spray-coated) onto a current collector (for simplicity, Figure 2 4426) on both sides of a (not shown) such as an aluminum foil, thereby providing the desired cathode capacity. Alternatively, in some other aspects, the electrode film 4404 is used as a current collector, thereby eliminating the need for a separate cathode current collector coupled to the cathode 4426. In this way, the cathode 4426 can be a stand-alone cathode.

[0376] The electrode film 4404 may be composed of a plurality of carbonaceous aggregates (for simplicity, Figure 2 (not shown) to form, for example, non-hollow carbon spherical (NHCS) particles joined together. Each NHCS particle may be Fig. 22 The first three sections of particles 2212, Fig. 22 The second and third segment particles 2222, Fig. 8A At least some of the NHCS particles may agglomerate together and thereby collectively form a tubular NHCS particle agglomerate, which may be Fig. 9BAn example of an aggregate 960 of. In this way, one or more of the described carbonaceous aggregates and / or other carbon-based materials presented in the present disclosure can be aggregated together to collectively define an electrode film 204 having pores (e.g., micropores, mesopores, and / or macropore channels) of various sizes and / or major dimensions. The carbonaceous aggregates and / or materials used to form the electrode film 4404 may have exposed surfaces decorated with silicon and / or silicon-containing materials. In one or more specific examples, the electroactive material may constitute between 60 weight percent (wt%) and 90 wt% of the electrode film 4404.

[0377] Electrolyte (for simplicity, Fig.44 4426 and in contact with the anode 4422, thereby providing a suitable + ) is an ion-conducting substance. The electrolyte may be an example of any electrolyte disclosed in the present disclosure, such as electrolyte 130, electrolyte 230, etc. formulated according to Examples 1-20 presented previously. In some cases, the electrolyte may be a liquid-phase electrolyte or a gel-phase electrolyte and may be added after the core 4420 is formed. In this configuration, in some aspects, the first barrier layer 4424 and the second barrier layer 4428 may be used as a separator. For example, the first barrier layer 4424 and the second barrier layer 4428 may be formed of materials different from each other, so that one barrier layer may be used as a separator and the other barrier layer may be used as a non-aqueous electrolyte membrane. In some other cases, each of the first barrier layer 4424 and the second barrier layer 4428 may be used as a separator and a non-aqueous electrolyte membrane. In addition, in some other aspects, the battery 4400 may be Fig.26B In this manner, battery 4400 may thus include solid electrolyte 2630 incorporated into battery 4400 during formation of jellyroll 4420 .

[0378] Fig.45A According to some implementations, Fig.44 4400 of the battery 4400. Cathode 4500A can be an example of one or more cathodes disclosed in the present disclosure, such as Fig. 22 Cathode 2200, Fig.29 Cathode 2900, Fig.42A Cathode 4210 or Fig.44 Cathode 4500A may include a current collector 4510, a top electrode film 4520A coated on a first surface of the current collector 310, and a bottom electrode film 4530A coated on a second surface opposite to the first surface of the current collector 4510. Figure 2When the top side electrode film 4520A is wound about the axis AA' of the battery 4400, the top side electrode film 4520A may face outward, for example, away from the axis AA' and toward the shell 4410 of the battery 4400, and the bottom side electrode film 4530A may face inward, for example, toward the axis AA' and away from the shell 4410 of the battery 4400. In this way, the top side electrode film 4520 may be subjected to tensile stress when it is wound around the axis AA' to form the winding core 4240. The tensile stress may stretch the top side electrode film 4520 from the opposite direction, and thus may undesirably propagate pre-existing cracks in the top side electrode film 4520. In some aspects, the propagation of the pre-existing cracks may cause at least a portion of the top side electrode film 4520 to delaminate from the current collector 4510. Simultaneously with the stretching of the top side electrode film 4520, the bottom side electrode film 4530 may be subjected to a compressive stress corresponding to the tensile stress of the top side electrode film 4520. In some aspects, the compressive stress may cause buckling delamination of the bottom film 4530 from the current collector 4510.

[0379] To address the undesirable delamination as described above, one or both of the topside electrode film 4520A and / or the bottomside electrode film 4530A can be formed of interconnected agglomerates 4532. In some aspects, one or more of the agglomerates 4532 can be an example of any carbonaceous aggregate, agglomerate, and / or material disclosed in the present disclosure, such as Fig. 22 The first three zones of particles 2212, Fig. 22 The second and third zone particles 2222, Fig. 8A In one implementation, at least some of the agglomerates 4532 may be non-hollow carbon spherical (NHCS) particles as described previously, which may aggregate together to form tubular NHCS particle agglomerates, which may be Fig. 9B The carbonaceous material described may be formed by sp atoms bonded to each other by carbon-carbon bonds. 2 Hybrid and / or sp 3 Hybridized carbon atoms form wrinkle points and / or flexure regions ( Fig.45A 4520A) to abut against each other. During the curling process, the carbon atoms at such flexure regions may have a relatively high level of mobility relative to conventional two-dimensional (2D) graphene materials or conventional carbonaceous structures (e.g., carbon nano-onions (CNO)). In this way, the use of such relatively flexible carbonaceous materials characterized by flexure regions may limit or eliminate undesirable crack-induced delamination of the top-side electrode film 4520A and / or buckling-related delamination of the bottom-side electrode film 4530A. In this way, the top-side electrode film 4520A and the bottom-side electrode film 4530A may both remain attached to the current collector 4510 during the curling process without being undesirably transferred to, for example, Fig.44The first barrier layer 4424 and the second barrier layer 4428 of the embodiment of the present invention may be formed on the surface of the first barrier layer 4424 and the second barrier layer 4428, thereby potentially causing an internal short circuit condition. The relatively flexible and strong mechanical structure provided by the agglomerate 4532 also provides electrical conductivity, thereby allowing the production of the core 4420 with a desired energy density value.

[0380] Fig.45B A side view of an exemplary unwound cathode 4500B is shown according to some implementations. Cathode 4500B may be Fig.44 The cathode 4426 and / or Fig.45A An example of cathode 4500A and / or any other cathode disclosed in the present disclosure. Fig.45B In the configuration shown, cathode 4500B may include current collector 4510, electrode film 4520B that may be laminated on one side of current collector 4510, and electrode film 4530B laminated on the opposite side of current collector 4510. Electrode films 4520B and 4530B may be an example of top-side electrode film 4520A and bottom-side electrode film 4530A, respectively, and thus may also be formed of interconnected agglomerates 4532. In this way, when the electrode film is laminated around axis AA' (for simplicity, Fig.45B When rolled (not shown), the film 4520B may form Fig.45A The top side electrode film 4520A and the film 4530B may be formed Fig.45A The bottom electrode film 4530A. Fig.45B In the embodiment of the present invention, the top side electrode film 4520A and the bottom side electrode film 4530A may have thicknesses indicated as "H1" and "H2", respectively. In some cases, the thickness H1 is the same as the thickness H2. In addition, the thickness may be between 10 micrometers (μm) and 250 μm.

[0381] At least some of the interconnected agglomerates 4522 may have a uniform shape relative to each other. In some cases, the uniform shape may be a spherical, elliptical, or other well-defined three-dimensional (3D) shape that may be arranged in a closely packed orientation, such as without voids formed between adjacent instances of the interconnected agglomerates 4532. In some other cases, the uniform shape may have pores 4524 formed and uniformly distributed between at least some of the interconnected agglomerates 4532. In this way, at least some of the pores 4524 may be interconnected with each other to form one or more channels (for simplicity, Fig.45B 4500B). A solvent, such as a liquid phase substance, used to produce cathode 4500B can be exposed to the surrounding atmosphere and thereby dried and / or evaporated through the channels during the slurry drying process of topside electrode film 4520B and bottomside electrode film 4530B. For example, the channels can provide defined paths for the solvent to escape cathode 4500B during the slurry drying process, thereby reducing or eliminating the development of uncontrolled drying-induced cracks between adjacent instances of interconnected agglomerates 4532.

[0382] In addition, the uniform distribution of pores 4524 can correspond to the uniform distribution of channels, so that the solvent can escape the top electrode film 4520B and the bottom electrode film 4530B uniformly without generating drying-induced cracks between adjacent examples of the interconnected agglomerates 4532. In some aspects, the top electrode film 4520B and the bottom electrode film 4530B can each be formed as a conductive matrix, wherein the formation of undesired cracks or fractures within the matrix may destroy the structural conductivity of the cathode 4500B, thereby resulting in a lower than desired specific capacity value. The cathode 4500B can be produced as a desired structural conductivity with a relatively high area load for an electroactive material such as elemental sulfur by providing a more robust mechanical structure through various configurations of the interconnected agglomerates 4532. In addition, at least some of the interconnected agglomerates 4532 can have a flexure area that can increase flexibility relative to conventional carbonaceous materials. In this way, the cathode 4500B can be curled during the production of the roll core 4420 without being subjected to tensile stress and / or compressive stress sufficient to cause crack propagation and / or delamination, respectively.

[0383] Additionally, in some aspects, at least some of the interconnected agglomerates 4522 may have different diameters relative to each other. For example, the diameter of a given agglomerate may be determined based on the thickness (e.g., H1 and / or H2) of the film containing the agglomerate (e.g., topside electrode film 4520B and / or bottomside electrode film 4530B). In some aspects, relatively large agglomerates within film 4520B may be generated during the manufacturing process to have a size that is proportional to the thickness of topside electrode film 4520B. For example, the size of relatively large agglomerates 4522 may be one-fifth the thickness of film 4520B (" 1 / 5"). Relatively smaller agglomerates 4522 may be produced during the manufacturing process to have a size that is a fraction of the size of relatively larger agglomerates. In some cases, the size of relatively smaller agglomerates 4522 may be one-third the size of relatively larger agglomerates (" 1 / 3"). In this way, the size ratio between relatively smaller agglomerates and relatively larger agglomerates can be between 1:1 and 1:3.3.

[0384] The size difference between at least some interconnected agglomerates 4532 can help increase the packing density level of the agglomerates within the defined volume. For example, relatively small agglomerates can at least partially fill some pores 4524 between adjacent examples of interconnected agglomerates. In this way, the cathode 4500B can be produced as an electroactive material (e.g., elemental sulfur) with an increased level of infiltration in the channels formed between agglomerates of various sizes relative to conventional cathode configurations, and the agglomerates can be stacked together at an increased density level, thereby resulting in an increase in the specific capacity of the cathode 4500B. In addition, the approximate size ratio of 1:1 to 1:3.3 can result in relatively few connection points in each of the top electrode film 4520B and the bottom electrode film 4530B. Since stress concentration tends to accumulate at the connection points between the individual agglomerates, the fewer connection points in each of the top electrode film 4520B and the bottom electrode film 4530B can reduce the overall stress concentration level of the interconnected agglomerates 4532, especially in the agglomerates located away from the collector 4510. In this manner, cathode 4500B can experience increased flexure throughout the winding process without cracking or delamination to form core 4420.

[0385] Additionally, in some aspects, cathode 4500B can have cathode electroactive material embedded within each of topside electrode film 4520B and bottomside electrode film 4530B (for simplicity, Figure 3 4522). For example, the electroactive material may be infiltrated into various pores 4524 dispersed in at least some of the interconnected agglomerates 4522. In some other aspects, each of the interconnected agglomerates 4532 may include secondary particles (for simplicity, Figure 3 The second plurality of pores (for simplicity, Figure 3 ) may be interconnected to provide one or more channels (for simplicity, Figure 3 4500B). Thus, the solvent can evaporate along these additional channels. These additional porosities can be correspondingly distorted within the top electrode film 4520B and / or the bottom electrode film 4530B, thereby at least preventing the formation of drying-induced cracks in the cathode 4500B.

[0386] Fig.46 According to some implementations, Fig.45B A micrograph of an exemplary electrode film 4600 of a cathode 4500B of FIG. Electrode film 4600 may be an example of a top side electrode film 4520B and / or a bottom side and / or 4530B, depicting at least some interconnected agglomerates 4522 and pores 4524. Fig.46As shown, each interconnected agglomerate 4522 may be porous. In this way, in some cases, at least some of the interconnected agglomerates 4522 may include overlapping secondary carbonaceous particles (for simplicity, Figure 4 The second pores (not shown in FIG. Figure 4 (not shown in the figure). Fig.46 The average size of the pores 4524 shown can be larger than the average size of the second pores. The second plurality of pores can be large enough to allow lithium ions (Li + ions) and electrolyte are able to wet the interconnected agglomerates 4522 and reach the cathode electroactive material confined within the plurality of secondary particles.

[0387] Fig.47 A method for manufacturing a Fig.45A and Fig.45B 4520B and / or bottom electrode film 4530B of the top side electrode film 4520B and / or bottom side electrode film 4530B. Agglomerate 4700 may be an example of one of interconnected agglomerates 4532, shown as including porous particles 4710, carbon layer 4720, and functional layer 4730. Agglomerate 4700 may have a spherical, elliptical, or other well-defined three-dimensional (3D) shape. In some cases, the shape of agglomerate 4700 may help to interlock with additional instances of positioned agglomerate 4700. That is, multiple instances of agglomerate 4700 may be seamlessly interconnected with each other to form any electrode disclosed in the present disclosure. For example, in some aspects, agglomerate 4700 may be deposited (e.g., spray coated) onto Fig.45A and Fig.45B on the current collector 4510. In some implementations, the agglomerate 4700 can have a diameter between 2 μm and 50 μm. In this way, multiple instances of the agglomerate can be interconnected with each other to form, for example Fig.45B The top electrode film 4520B and / or the bottom electrode film 4530B of the agglomerate 4700 may be relatively low in torsion compared to conventional carbonaceous films due to the densely packed nature of multiple examples of the agglomerate 4700. The low torsion may in turn provide a relatively direct path for evaporation of the solvent in the drying process used during the battery manufacturing process (for simplicity, Fig.47 ). In addition, the topside electrode film 4520B and / or the bottomside electrode film 4530B may be subjected to lower drying stress during the drying process due to its low distortion. In this way, the lower drying stress may prevent the formation of undesired drying-induced cracks in the topside electrode film 4520B and / or the bottomside electrode film 4530B, respectively.

[0388] In some aspects, the particle 4710 can be formed as an agglomeration of a plurality of interconnected secondary particles 4712. In addition, each secondary particle 4712 can be formed as an aggregate of a plurality of primary particles (for simplicity, Figure 5 Each primary particle may be Fig. 8A An example of the carbonaceous particles 800, Fig. 9B One or more examples of interconnected aggregates 960 and / or the like described elsewhere herein. Each primary particle may include a plurality of graphene surfaces (e.g., exposed surfaces of graphene nanosheets adjacent to each other) including a plurality of carbon atoms. These carbon atoms may be covalently bonded (e.g., via sp 2 -Hybridized bond or sp 3 -hybrid bond) to form secondary particles 4712 together. In some cases, such as Figure 5 As shown, particle 4710 can be formed by a plurality of interconnected secondary particles 4712. A second plurality of pores 4714 can be defined by void spaces formed between adjacent secondary particles 4712. In some aspects, secondary particles 4712 can overlap each other and create at least some void spaces between adjacent secondary particles 4712. Additionally, in some aspects, second plurality of pores 4714 can be uniformly distributed throughout particle 4710. Alternatively, in some other aspects, second plurality of pores 4714 can be concentrated in one or more regions within particle 4710. For example, the average size of second plurality of pores 4714 can be less than Fig.46 The average size of the pores 4524 of the secondary particles 4712 can be 4714. In addition to the second plurality of pores 4714, each secondary particle 4712 can have one or more peripheral pores 4716 located at or near the periphery of the particle, the size and / or location of which can be defined by, for example, a carbon dioxide etching process. In addition, other suitable processing techniques can be used to produce the peripheral pores 4716 and the particles 4710. For example, the particles 4710 can be spray dried by spray drying and / or formed by an atomization process, as well as by other suitable solution-based methods.

[0389] Additionally, in some aspects, the carbon layer 4720 can conformally coat the exposed surface of the particle 4710 and at least partially secure the secondary particles 4712 within the particle 4710. The carbon layer 4720 can be prepared to avoid blocking ions such as lithium ions (Li) associated with the battery discharge-charge operation cycle. + ) transport. In some aspects, the carbon layer 4720 can be formed of monolithic and 3D amorphous carbon-containing growths and / or structures. In addition, the carbon layer 4720 can be formed of multiple graphene, graphite, fullerene, carbon nanotubes, and / or carbon onions. interconnectionExample formation. Carbon layer 4720 can act to bind the contents of agglomerate 4700 together, thereby increasing the mechanical robustness of agglomerate 4700 relative to conventional carbonaceous materials (e.g., CNO). In this way, agglomerate 4700 can also be relatively more resistant to internal collapse, which may be caused by the slurry casting and subsequent spray drying process, relative to conventional carbonaceous materials. Increased structural rigidity, hardness, and / or toughness of the agglomerates can be beneficial for accommodating higher area loading levels of electroactive materials within agglomerates 4700. In this way, the energy density of any currently disclosed jellyroll configuration incorporating agglomerate 4700 can be relatively higher than the energy density of a battery using, for example, conventional cathode materials.

[0390] In addition, the agglomerate 4700 may further have a functional layer 4730 deposited on top of the carbon layer 4720. The functional layer 4730 may coat the carbon layer 4720 along the outer edge of the carbon layer 4720 so that at least some of the second plurality of pores 4714 can be unblocked by adding the functional layer 4730. In some implementations, the functional layer 4730 may have a thickness of less than about 300 nm. In some implementations, the functional layer 4730 may be an ion conductive layer configured to enhance the ionic conductivity of the agglomerate 4700. In some cases, the functional layer 4730 may include one or more functional groups, one or more polar and ion conductive additives, or a combination thereof. Examples of one or more polar and ion conductive additives include lithium lanthanum zirconium oxide (LLZO), lithium phosphorus oxynitride (LIPON), or a combination thereof. Examples of one or more functional groups include amine groups, oxygen-containing groups, sulfur-containing groups, or any combination thereof.

[0391] Fig.48A A method for manufacturing a Fig.47 A micrograph of an exemplary secondary particle 4800A of agglomerate 4700 of Fig.47 As shown, secondary particles 4800A can be formed from primary particles 4802A, at least some of which can have carbon atoms covalently bonded to each other, such as between adjacent secondary particles 4800A. In this way, in some aspects, secondary particles 4800A can be Fig.48A Alternatively, in some other aspects, secondary particles 4800A can be formed into other 3D shapes, including multiple interconnected instances of primary particles 4802A, which can include graphite, graphene flakes, spherical fullerenes, carbon nanotubes, carbon nano-onions (CNO), and / or amorphous carbon. Each of primary particles 4802A can have a diameter between about 50nm and 100nm and include nanoscale pores, which can each have a diameter between 0nm and about 25nm. In this way, the electroactive material (for simplicity, Fig.48AThe electroactive material may be elemental sulfur and / or other suitable sulfur-containing materials, such as lithium sulfide.

[0392] Fig.48B A method for manufacturing a Fig.47 4800A. Similar to secondary particle 4800A, secondary particle 4800B may include a plurality of primary particles 4802B covalently bonded together to form secondary particle 4800B. As shown, secondary particle 4800B may have a shape containing one or more branches, rather than a string or chain as shown in 4800A. In this way, the surface area of ​​secondary particle 4800B may be relatively larger than the surface area of ​​secondary particle 4800A. Therefore, the electroactive material residing in the plurality of nanoscale pores of secondary particle 4800B may be relatively more exposed to the infiltrating Li+ ions and electrolyte during battery operation, thereby accelerating the desired electrochemical reaction of the battery.

[0393] Fig.49A and Fig.49BA flow chart depicting an exemplary operation 4900 for manufacturing a cathode of a jellyroll for a lithium-sulfur battery according to some implementations is shown. In various implementations, operation 4900 may be performed in one or more reactors, and the one or more reactors may include a thermal reactor chamber, a plasma reactor, a spray dryer, an atomizer, or any other suitable chemical processing device. In some implementations, operation 4900 may be used to manufacture a cathode having 60% by weight and 90% by weight elemental sulfur or sulfur-containing electroactive material embedded in an electrode film, the electrode film being formed by a plurality of agglomerates deposited on a current collector, and each of the plurality of agglomerates including a plurality of primary particles covalently bonded into a plurality of secondary particles and the plurality of secondary particles being joined together by a carbon layer, for example, as disclosed elsewhere in the present disclosure. In some aspects, operation 4900 begins at box 4902, with feeding a plurality of primary particles into a thermal reactor. Operation 4900 continues at box 4904, with agglomerating the plurality of primary particles into a plurality of secondary particles. Operation 4900 continues at frame 4906, introducing one or more pores into a plurality of secondary particles. Operation 700 continues at frame 4908, mixing a plurality of secondary particles with a first binder in a first solvent. Operation 4900 continues at frame 4910, agglomerating a plurality of secondary particles into a plurality of agglomerates, wherein the first binder coats each of the plurality of agglomerates. Operation 4900 continues at frame 4912, carbonizing the plurality of agglomerates. Operation 4900 continues at frame 4914, injecting sulfur into a plurality of nanoscale pores of each of the plurality of agglomerates. Operation 4900 continues at frame 4916, preparing a slurry including a plurality of agglomerates and a second binder in a second solvent. Operation 4900 continues at frame 4918, casting the slurry onto a current collector surface in a film form. Operation 4900 continues at frame 4920, removing the second solvent from the cast slurry.

[0394] In some implementations, the plurality of primary particles may include graphite, graphene flakes, spherical fullerenes, carbon nanotubes, carbon nano onions (CNO), amorphous carbon, or any combination thereof. In some implementations, the plurality of primary particles may have a diameter between about 50 nm and 100 nm. In various implementations, each of the plurality of primary particles may have a plurality of nanoscale pores. The plurality of nanoscale pores may have a diameter between 0 nm and about 25 nm. In various implementations, the electroactive material may be confined within at least some of the plurality of nanoscale pores. In some cases, the electroactive material may be elemental sulfur. In other cases, the electroactive material may be other suitable sulfur-containing materials, such as lithium sulfide.

[0395] In some implementations, the first binder may include a polymeric material that can bind adjacent carbonaceous materials (e.g., graphene nanosheets) together during carbonization of the plurality of agglomerates in block 4912 as described in reference Fig.47The one or more carbon layers. For example, the first binder may be polyacrylonitrile (PAN), asphalt, a formaldehyde-based resin, or any combination thereof.

[0396] In various implementations, the plurality of agglomerates may have a spherical, elliptical, or other well-defined three-dimensional shape that is suitable for leaving void spaces between adjacent agglomerates when cast on a current collector. In some implementations, each of the plurality of agglomerates may have a diameter between about 2 μm and about 50 μm.

[0397] Fig.49C A flow chart depicting another exemplary operation for manufacturing a cathode of a jellyroll for a lithium-sulfur battery according to some implementations is shown. Figure 7 After carbonizing the plurality of agglomerates in block 4912 of A, operation 4930 is performed. In other implementations, operation 730 may be performed in conjunction with Figure 7 In frame 4916 of B, a slurry including a plurality of agglomerates and a second adhesive is prepared in a second solvent and performed simultaneously. For example, operation 730 starts at frame 4932, and each of the plurality of agglomerates is coated with a functional layer along the outer edge without blocking the plurality of pores of each of the plurality of agglomerates. In some implementations, the functional layer has a thickness of less than about 300nm. In some implementations, the functional layer may be an ion conductive layer. In some cases, the functional layer 4730 may include one or more functional groups, one or more polar and ion conductive additives, or a combination thereof. Examples of one or more polar and ion conductive additives include lithium lanthanum zirconium oxide (LLZO), lithium phosphorus oxynitride (LIPON), or a combination thereof. Examples of one or more functional groups include amine groups, oxygen-containing groups, sulfur-containing groups, or any combination thereof.

[0398] Fig.50A A flowchart depicting exemplary operations for manufacturing a roll core for a lithium-sulfur battery according to some other implementations is shown. In various implementations, operation 5000 can be performed with any suitable winding machine or by hand to manufacture a roll core for a lithium-sulfur battery. In some implementations, operation 5000 can be used to wind a laminate containing an anode sheet, a first barrier layer, a cathode sheet, and a second barrier layer into a roll core having various cross-sectional shapes. In various implementations, operation 5000 starts at box 5002, stacking the first barrier layer on top of the anode sheet. Operation 5000 continues at box 5004, stacking the cathode sheet on top of the first barrier layer. Operation continues at box 5006, stacking the second barrier layer on top of the cathode sheet. Operation continues at box 5008, winding the laminate into a roll core. Operation continues at box 5010, inserting the roll core into a metal shell. Operation continues at box 5012, sealing the metal shell to obtain a roll core for a lithium-sulfur battery.

[0399] The first barrier layer and the second barrier layer may comprise the same material and both are used as a typical separator. In some other aspects, the first barrier layer and the second barrier layer may contain different materials for specific purposes. For example, one barrier layer may be used as a typical separator, while the other barrier layer may be used as a non-aqueous electrolyte membrane. Each of the first barrier layer and the second barrier layer may be used as a separator and a non-aqueous electrolyte membrane. The core may have a cross-section of a circular, rectangular, square, triangular, or any other geometric shape.

[0400] Fig.50B A flowchart depicting another exemplary operation 5020 for manufacturing a jellyroll Li-S battery according to some implementations is shown. In various implementations, operation 5020 may be performed at Fig.50A In another implementation, operation 5020 may be performed after inserting the winding core into the metal shell in block 5010. Fig.50A One or more processes of the exemplary operation 5000 of 5020 are performed simultaneously. For example, operation 5020 begins at block 5022 with adding electrolyte to the winding core. In some implementations, the electrolyte may be a solid electrolyte, a polymer electrolyte, or other suitable non-aqueous electrolyte that may be sandwiched within the laminate and subjected to winding. In other implementations, the electrolyte may be aqueous and may be added to the laminate before or after the winding process.

[0401] Fig.50C A flowchart depicting another exemplary operation 5030 for manufacturing a roll core for a lithium-sulfur battery according to some implementations is shown. In various implementations, operation 5030 may be performed at Figure 8B In other implementations, operation 5030 may be performed after electrolyte is added to the core in block 5022 of the embodiment. Fig.50A One or more processes of the exemplary operation 5000 are performed simultaneously. For example, the operation 5030 starts at box 5032 and welds a plurality of batteries into one or more battery modules. The operation 5030 continues at box 5034 and assembles the one or more battery modules into one or more battery packs.

[0402] Fig.51 A diagram of a lithium-sulfur battery 5100 is shown according to some implementations. The lithium-sulfur battery 5100 can be an example of one or more batteries and / or battery configurations disclosed herein, such as Figure 1 Battery 100, Figure 2 Battery 200, Fig.28 Battery 2800 and / or Fig.42ABattery 4200A. Various aspects of the present disclosure recognize that increased energy density (e.g., specific capacity) and reduced cell impedance are desirable properties in an electrochemical cell. For example, replacing certain inactive cell components (e.g., anode tabs) with conductive materials can reduce the overall weight of the battery while also increasing the contact area between the anode current collector and the surface of the container inside the cell, resulting in rapid current flow and / or power delivery. Removing the anode tab, resulting in a "tabless" lithium-sulfur battery 5100, can also improve battery reliability because conventional anode tabs can be spot welded to the cell container. Spot weld areas can easily overheat, thereby exacerbating battery degradation under daily and / or high-intensity use conditions. Carbonaceous material 5160, such as Fig.47 Particles 4710, Fig. 8A Carbonaceous particles 800 and / or Fig. 9B Multiple examples of aggregates 960 of the invention may be interconnected and positioned between the conductive components of the lithium-sulfur battery 5100 and the anode container 5122 to replace conventional anode tabs welded to the battery can. In some cases, the various components of the carbonaceous material 5160 may coat the entire bottom-facing surface of the roll core 5190. In addition, certain components may be selected for inclusion in the carbonaceous material 5160 to increase the flexibility and / or elasticity of the carbonaceous material 5160. In this way, the carbonaceous material 5160 may be produced as a relatively compressed and responsive contact area compared to conventional viscous and / or conductive anode glues.

[0403] Compared to spot welding or contact welding and some conductive epoxy materials filled with metal flakes, the use of carbonaceous material 5160 can result in the lithium sulfur battery 5100 being more easily connected to an electrical load (for simplicity, Fig.51 The contact resistance between the first carbon component and the second carbon component is low. In some aspects, the carbonaceous material 5160 can be formed from a first carbon component and a second carbon component. The first carbon component and the second carbon component are combined into a uniform mixture (for simplicity, Fig.51 (not shown) the carbonaceous material 5160 may be formed into a sticky layer after the carbon atoms in each of the first carbon component and the second carbon component are cross-linked. In this way, a dual-purpose region and / or layer capable of conducting electricity and adhesion may be generated and realized within the lithium-sulfur battery 5100. In addition, in some aspects, the carbonaceous material 5160 may be formed by combining various carbon allotropes with each other (for simplicity, Fig.51 not shown).

[0404] At least some of the carbon allotropes of the carbonaceous material 5160 may include surfaces functionalized with amine-containing groups. These carbon allotropes may be mixed with other carbon allotropes that may be functionalized with epoxy-containing groups and / or thermal crosslinking agents. In some implementations, the thermal crosslinking agent may be an example of any suitable thermal crosslinking agent and / or crosslinking compound, moiety, free radical initiator, and / or high energy environment disclosed in the present disclosure. Any of the carbon allotropes may be controlled in terms of density, porosity, thermal conductivity to provide desired physical, chemical, and / or mechanical properties and / or characteristics. In this way, the carbonaceous material 5160 may have increased mechanical robustness, flexibility, and electronic conductivity compared to conventional viscous and / or conductive materials.

[0405] In some aspects, the lithium-sulfur battery 5100 may include a jellyroll 5190 that may be formed into one or more cell types, such as a 18650 cell, a 26650 cell, and / or a 21700 cell. The jellyroll 5190 of the lithium-sulfur battery 5100 may include an anode 5122 (e.g., formed without an anode tab), a solid electrolyte interface phase (SEI) 5104 formed on the anode 5102, a protective layer 5110, a cathode 5140, and a separator 5130 located between the cathode 5140 and the anode 5102. In one implementation, the anode 5122 may be formed of a single solid layer of metallic lithium having a thickness between 60 micrometers (μm) and 85 μm. In addition, the protective layer 5110 may have a thickness between 2 μm and 5 μm and may act as a natural insulator to prevent internal short circuits within the lithium-sulfur battery 5100 by blocking viscous materials (e.g., carbonaceous material 5160) from penetrating into the separator 5130. In addition, in some aspects, the separator 5130 can be configured to have a porosity at the edge of the jellyroll 5190 (e.g., near the cathode cap 5180 or the anode container 5122) that is different from the porosity of the separator 5130 at the center region adjacent to the anode 5102 and / or cathode 5140. In one implementation, the separator 5130 can be formed to have a porosity that can be at least partially penetrated by the protective layer 5110 so that the separator 5130 can adhere to the anode 5102 but not to the current collector of the cathode 5140 (for simplicity, Fig.51 not shown).

[0406] The jelly roll 5190 may be formed by winding at least the anode 5122 and the cathode 5140 together. The electrolyte 5170 may be in contact with the anode 5102 and dispersed throughout the cathode 5140, which may be formed as a three-dimensional scaffold of interconnected carbonaceous materials. Fig.51Anode 5102 may be formed as a solid lithium monolayer, thereby outputting lithium cations (Li ions) during the operation discharge cycle of the lithium-sulfur battery. + ). An anode current collector (eg, such as and / or including an anode lead 5120) can be coupled to the anode 5102 such that the protective layer 5110 can prevent delamination of lithium from the anode current collector.

[0407] In response to the operating discharge-charge cycle of the lithium-sulfur battery 5100, the SEI 5104 can be formed on the anode 5102. The protective layer 5110 can be at least partially formed within and on the SEI 5104 and positioned proximate to the anode 5102. In this way, the protective layer 5110 can be associated with protecting one or more edges of the anode 5120 exposed to the electrolyte 5170 from lithium corrosion. In some cases, the protective layer 5110 can be an example of one or more anode protective layers disclosed in the present disclosure, such as Figure 2 Polymer network 285, Figure 5 The grading layer 514 and / or the protective layer 516, Figure 7 The carbonaceous material layer 714 grafted with fluorinated polymer chains, Fig.28 The protective layer 2860 or Fig.42A Protective layer 4260.

[0408] In some cases, the winding core 5190 can be formed so that the cathode 5140 and the anode 5102 are offset relative to each other. In addition, the active material of the cathode 5140 can be patterned. In some aspects, the offset between the cathode 5140 and the anode 5102 can allow the edge of the anode 5102 near the cathode cover 5180 to be aligned with the cathode 5140. In contrast, the edge of the anode 5102 near the anode container 5122 can extend longitudinally beyond the cathode 5140 at a ratio between 1:1 and 1:1.5. That is, the anode 5102 can extend longitudinally toward the anode container 5122 up to 1.5 times (x) the length of the cathode 5140. The resulting offset configuration can increase the current delivery from the anode 5102 to the carbonaceous material 5160, which can contact at least some of the exposed surfaces of the anode 5102.

[0409] Additionally, in some aspects, the roll core 5190 may be formed as a cylindrical cell including a shell defining an internal volume, such that the shell has a diameter between 18.4 millimeters (mm) and 18.6 mm and a length between 65.1 mm and 65.3 mm, and thus may be consistent with a 18560 cell. In some other aspects, the roll core 5190 may be formed as a prismatic cell including a shell defining an internal volume, such that the shell has a height between 56 millimeters (mm) and 58 mm, a length between 34 mm and 36 mm, and a width between 6 mm and 8 mm, and thus may be consistent with a CP3553 cell.

[0410] In some aspects, the protective layer 5110 may have a thickness between approximately 0.001 μm and 5 μm. In addition, the protective layer 5110 may be formed of graphene nanosheets 5112 adjacent to each other through flex points 5114, wherein each flex point may provide exposed carbon atoms. In some aspects, the flex points may include and / or be referred to as "wrinkled graphene," meaning that multiple graphene nanosheets are adjacent to each other at angles including right angles, forming a relatively jagged or "wrinkled" profile. The flex points 5114 and / or "wrinkles" may provide exposed carbon atoms suitable for grafting additional chemicals. In this way, a fluorinated poly (meth) acrylate 5116 (e.g., one or more of which may terminate in fluoride ions) may be grafted onto at least some of the exposed carbon atoms at one or more grafting points 5118, such as Fig.51 For example, in some aspects, the protective layer 5110 can be produced to have between 5 weight percent (wt%) and 100 weight percent carbonaceous material, for example, which can be an example of any carbonaceous material disclosed in the present disclosure. Additionally or alternatively, the protective layer 5110 can be produced to have between 95 weight percent and 0 weight percent fluorinated poly (meth) acrylate 5116.

[0411] Grafting of at least some of the fluorinated poly(meth)acrylate 5116 may be initiated by a free radical initiator including one or more of benzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN). In this manner, in one implementation, the protective layer 5110 may be formed from between approximately 0.001 wt % and 2 wt % of the fluorinated poly(meth)acrylate 5116, which is uniformly dispersed and / or chemically bonded to other substances, such as exposed carbon atoms provided by any carbonaceous material disclosed elsewhere in the present disclosure. In one or more specific examples, the fluorinated poly (meth) acrylate 5116 may include monomers such as 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate (DFHA), 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl methacrylate (HDFDMA), 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate (OFPMA), tetrafluoropropyl methacrylate (TFPM), 3-[3,3,3-trifluoro-2-hydroxy-2-(trifluoromethyl)propyl]bicyclo[2.2.1]hept-2-yl methacrylate (HFA monomer), or vinyl-based monomers including 2,3,4,5,6-pentafluorostyrene (PFSt).

[0412] In this way, in some aspects, at least some monomers of the fluorinated poly(meth)acrylate 5116 and / or the fluorinated poly(meth)acrylate 5116 (e.g., in their respective ensembles) can be compatible with polymerization and crosslinking in response to exposure to one or more free radical initiators or ultraviolet (UV) high energy environments. For example, in some aspects, at least some fluoride ions can dissociate from their corresponding fluorinated poly(meth)acrylate 5116 by participating in the Woods reaction occurring within the protective layer to produce dissociated fluoride ions, which can then react with at least some lithium cations (Li ions) outputted by the anode. + ) combination to produce lithium fluoride (LiF) within the protective layer 5110.

[0413] In one implementation, the 3D scaffold of cathode 5140 may include and / or be otherwise formed of a first region and a second region. The first region may have a first concentration level of interconnected non-hollow carbon spherical (NHCS) particles, and the second region may have a second concentration level of NHCS particles. The NHCS particles may be Fig.29 In some aspects, the second concentration level of the NHCS particles is lower than the first concentration level of the interconnected non-hollow carbon spherical (NHCS) particles. The 3D scaffold may further include porous channels formed between adjacent NHCS particles and within individual NHCS particles (for simplicity, Fig.51), such that one or more porous channels can microscopically confine elemental sulfur.

[0414] In some implementations, the protective layer 5110 may further include an interface layer in contact with the anode 5120 (for simplicity, Fig.51 ) and a cover layer disposed on top of the interface layer (for simplicity, Fig.51 The cover layer and the interface layer of the protective layer 5110 may be an example of the cover layer and the interface layer disclosed herein, for example, at least Figure 7 For example, Figure 7 The layer 714 may be an interface layer (for simplicity, Fig.51 The polymer layer 710 may be an example of a cover layer of the protective layer 5110. In this way, the interface layer and the cover layer of the protec...

Claims

1. A lithium-sulfur battery comprising: a cover circumferentially welded to the cylindrical housing; A cylindrical winding core, the cylindrical winding core comprising: Mandrel; an anode laminate comprising an anode coupled to an anode current collector; and a cathode laminate comprising a cathode coupled to a cathode current collector, the cathode comprising one or more structured layers of agglomerates of carbonaceous particles disposed on opposite sides of the cathode current collector; a negative terminal disposed along the length of the cylindrical case and longitudinally welded to the anode current collector, wherein a portion of the negative terminal is exposed outside the case; and A positive terminal includes the mandrel, is longitudinally welded to the cathode current collector, and is separated from the casing by an insulator disposed in the cover.

2. The lithium-sulfur battery of claim 1, wherein the opposite sides of the cathode current collector comprise: a first side, the first side being disposed proximate to the housing; as well as A second side is opposite to the first side and is close to the mandrel.

3. The lithium-sulfur battery of claim 2, wherein at least one of the one or more structured layers of agglomerates comprises sulfur.

4. The lithium-sulfur battery of claim 3, wherein the sulfur loading in the one or more structured layers of agglomerates disposed on the first side of the cathode current collector is different from the sulfur loading in the one or more structured layers of agglomerates disposed on the second side of the cathode current collector.

5. The lithium-sulfur battery of claim 2, wherein the one or more structured layers of agglomerates of carbonaceous particles comprise substantially spherical agglomerates.

6. The lithium-sulfur battery of claim 5, wherein the one or more structured layers of agglomerates of carbonaceous particles disposed on the first side of the cathode current collector include agglomerates of similar size to one another.

7. The lithium-sulfur battery of claim 5, wherein the one or more structured layers of agglomerates of carbonaceous particles disposed on the second side of the cathode current collector include agglomerates of similar size to one another.

8. The lithium-sulfur battery of claim 5, wherein an average size of the agglomerates of carbonaceous particles disposed on the first side of the cathode current collector is greater than an average size of the agglomerates of carbonaceous particles disposed on the second side of the cathode current collector.

9. The lithium-sulfur battery of claim 5, wherein the thickness of the one or more structured layers of agglomerates disposed on the first side of the cathode current collector is greater than the thickness of the one or more structured layers of agglomerates disposed on the second side of the cathode current collector.

10. The lithium-sulfur battery according to claim 5, wherein: The first side of the cathode current collector comprises one or more structured layers of agglomerates of carbonaceous particles, wherein each structured layer comprises agglomerates of similar size to one another; and The second side of the cathode current collector includes one or more structured layers of agglomerates of carbonaceous particles, wherein each structured layer includes agglomerates of similar size to one another.

11. The lithium-sulfur battery of claim 10, wherein an average size of the agglomerates of carbonaceous particles disposed on the first side of the cathode current collector is greater than an average size of the agglomerates of carbonaceous particles disposed on the second side of the cathode current collector.

12. The lithium-sulfur battery of claim 10, wherein an average size of the agglomerates of carbonaceous particles associated with the corresponding structured layer disposed on the first side of the cathode current collector is proportional to a distance between the first side of the cathode current collector and the corresponding structured layer.

13. The lithium-sulfur battery of claim 10, wherein an average size of the agglomerates of carbonaceous particles associated with the corresponding structured layer disposed on the second side of the cathode current collector is proportional to a distance between the second side of the cathode current collector and the corresponding structured layer.

14. The lithium-sulfur battery of claim 2, wherein the one or more structured layers of agglomerates of carbonaceous particles comprise substantially non-spherical agglomerates. 15 . The lithium-sulfur battery of claim 1 , wherein each of the carbonaceous particles comprises a plurality of interconnected non-hollow carbonaceous particles.

16. The lithium-sulfur battery of claim 15, wherein the plurality of interconnected non-hollow carbonaceous particles collectively define a plurality of porous channels, at least some of the plurality of porous channels being configured to retain elemental sulfur. 17 . The lithium-sulfur battery according to claim 1 , further comprising a separator disposed between the anode laminate and the cathode laminate.

18. The lithium-sulfur battery of claim 17, wherein the separator comprises a material containing ceramic.

19. The lithium-sulfur battery of claim 1, wherein the negative terminal is formed of nickel.

20. A lithium-sulfur battery comprising: a housing having a length and a width, the housing comprising at least an anode and a cathode wound into a core oriented parallel to the length of the housing; An electrolyte, wherein the electrolyte is disposed in the lithium-sulfur battery; a negative terminal extending along the length of the housing; as well as A positive terminal extends along the length of the housing, the positive terminal and the negative terminal being parallel to each other.

21. The lithium-sulfur battery of claim 20, wherein the electrolyte is configured to inhibit transport of lithium-containing polysulfide intermediates from the cathode to the anode.

22. The lithium-sulfur battery of claim 20, wherein the jellyroll is welded to one or both of the negative terminal and the positive terminal along the length of the casing.

23. The lithium-sulfur battery of claim 20, wherein one or both of the negative terminal and the positive terminal are formed of nickel.

24. The lithium-sulfur battery of claim 20, wherein the plurality of components further comprises: an anode current collector coupled to the anode; a cathode current collector coupled to the cathode; as well as A ceramic separator is disposed between the anode and the cathode.

25. The lithium-sulfur battery of claim 24, wherein the cathode current collector comprises a carbonaceous scaffold formed of a material oriented at one or more defined angles relative to the cathode.

26. The lithium-sulfur battery of claim 24, wherein the ceramic separator comprises a plurality of pores configured to allow lithium ions to propagate between the anode and the cathode via the ceramic separator.

27. The lithium-sulfur battery of claim 24, wherein the positive terminal is welded to the cathode current collector longitudinally along the length of the casing.

28. The lithium-sulfur battery of claim 24, wherein the negative terminal is welded to the anode current collector longitudinally along the length of the casing.

29. The lithium-sulfur battery of claim 24, wherein: The negative terminal includes a first side terminal configured to provide an increased contact area with the anode current collector; and The positive terminal includes a second side terminal configured to provide an increased contact area with the cathode current collector.

30. The lithium-sulfur battery of claim 24, further comprising a separator bag shorter than the length of the housing, wherein the ceramic separator is accommodated in the separator bag.

31. The lithium-sulfur battery of claim 24, wherein the anode is a solid lithium layer and the anode current collector is a copper foil.

32. The lithium-sulfur battery of claim 24, wherein the anode is configured to be folded into the anode current collector, and the cathode is configured to be folded into the cathode current collector.

33. The lithium-sulfur battery of claim 20, wherein the jellyroll is wound using one or more mandrels.

34. The lithium-sulfur battery of claim 20, wherein one or both of the negative terminal and the positive terminal have an "L" shape.

35. The lithium-sulfur battery of claim 20, wherein one or both of the negative terminal and the positive terminal have a trapezoidal shape extending along the length of the casing and along the width of the casing.

36. The lithium-sulfur battery of claim 20, wherein the anode and the cathode each include a plurality of edges configured to be welded together.

37. The lithium-sulfur battery of claim 20, wherein one or both of the anode and the cathode has a length of 548 mm and a width of 100 mm.

38. The lithium-sulfur battery of claim 20, wherein the cathode is formed of a plurality of interconnected non-hollow carbonaceous particles.

39. The lithium-sulfur battery of claim 20, wherein the plurality of interconnected non-hollow carbonaceous particles collectively define a plurality of porous channels, at least some of the plurality of porous channels being configured to retain elemental sulfur.

40. A lithium-sulfur battery comprising: case; a top cover, the top cover being circumferentially welded to the shell; a negative contact surface, the negative contact surface being positioned opposite the top cover; a positive terminal disposed within the housing and welded to the top cover, the positive terminal being configured as a mandrel; a glass insulator, the glass insulator being wound circumferentially around the mandrel; as well as A winding core, the winding core comprising at least an anode and a cathode wound around the mandrel, the winding core comprising: a top surface not in contact with the top cover; a bottom surface at least partially in contact with the negative contact surface; and A plurality of non-hollow carbonaceous spherical particles are disposed between the bottom surface of the core and the negative contact surface, at least some of the non-hollow carbonaceous spherical particles being configured to provide one or more conductive pathways between the positive terminal and the negative contact surface.

41. The lithium sulfur battery of claim 40, wherein the housing is formed from one or more of aluminum or steel.

42. The lithium-sulfur battery of claim 40, further comprising an electroactive material dispersed throughout the shell and within at least some of the plurality of non-hollow carbonaceous spherical particles.

43. The lithium-sulfur battery of claim 42, wherein the electroactive material is sulfur.

44. The lithium-sulfur battery of claim 40, further comprising a glass insulator wound around the mandrel and disposed within the housing.

45. The lithium-sulfur battery of claim 40, wherein the winding core further comprises: an anode current collector coupled to the anode; a cathode current collector coupled to the cathode; as well as A ceramic separator is disposed between the anode and the cathode.

46. ​​The lithium-sulfur battery of claim 45, wherein the cathode current collector comprises a carbonaceous scaffold formed of a material oriented at one or more defined angles relative to the cathode.

47. The lithium-sulfur battery of claim 45, wherein the ceramic separator comprises a plurality of pores configured to allow lithium ions to propagate between the anode and the cathode via the ceramic separator.

48. The lithium-sulfur battery of claim 45, wherein the anode current collector is a copper foil and the anode is a solid lithium layer.

49. The lithium-sulfur battery of claim 45, wherein the negative contact surface is welded to the anode current collector.

50. The lithium-sulfur battery of claim 45, wherein the anode is configured to be folded into the anode current collector and the cathode is configured to be folded into the cathode current collector.

51. The lithium-sulfur battery of claim 45, further comprising a separator bag configured to accommodate the ceramic separator.

52. The lithium-sulfur battery of claim 45, wherein the positive terminal is welded to the cathode current collector and the negative contact surface is welded to the anode current collector.

53. The lithium-sulfur battery of claim 40, further comprising an electrolyte configured to inhibit transport of lithium-containing polysulfide intermediate species from the cathode to the anode.

54. The lithium-sulfur battery of claim 40, wherein the anode is configured to output a plurality of lithium ions during an operational discharge-charge cycle of the lithium-sulfur battery.

55. The lithium-sulfur battery of claim 40, wherein one or both of the anode and the cathode has a length of 548 mm and a width of 100 mm.

56. The lithium-sulfur battery of claim 40, wherein the cathode is formed of a plurality of interconnected non-hollow carbonaceous particles.

57. The lithium-sulfur battery of claim 56, wherein the plurality of interconnected non-hollow carbonaceous particles collectively define a plurality of porous channels.

58. The lithium-sulfur battery of claim 57, wherein at least some of the plurality of porous channels are configured to retain elemental sulfur.

59. The lithium-sulfur battery of claim 58, wherein the anode and the cathode each include a plurality of edges configured to be welded together.

Citation Information

Patent Citations

  • Carbonaceous materials for lithium-sulfur batteries

    US11309545B2

  • Solid-state electrolyte for lithium-sulfur batteries

    US11367895B1

  • Lithium-sulfur battery cathode formed from multiple carbonaceous regions

    US11404692B1

  • Lithium-sulfur battery electrolyte compositions

    US12249690B2

  • Polymeric-inorganic hybrid layer for a lithium anode

    US20220263111A1